Communicating flood risk: Looking back and forward at traditional and social media outlets - Feldman, David; Contreras, Santina; Karlin, Beth; Basolo, Victoria; Matthew, Richard; Sanders, Brett; Houston, Douglas; Cheung, Wing; Goodrich, Kristen; Reyes, Abigail; Serrano, Kimberly; Schubert, Jochen; et al. (International Journal of Disaster Risk Reduction, 2016)
The communication of information about natural hazard risks to the public is a difficult task for decision makers. Research suggests that newer forms of technology present useful options for building disaster resilience. However, how effectively these newer forms of media can be used to inform populations of the potential hazard risks in their community remains unclear. This research uses primary data from an in-person survey of 164 residents of Newport Beach, California during the spring of 2014 to ascertain the current and preferred mechanisms through which individuals receive information on flood risks in their community. Factor analysis of survey data identified two predominant routes of dissemination for risk information: older traditional media and newer social media sources. A logistic regression model was specified to identify predictors for choosing a particular communication route. This analysis revealed that age is the central factor in predicting the sources people use to receive risk information. We follow the analysis by discussing this finding and its policy implications.

The Use of Remotely Sensed Information within a Flood Risk Management and Analysis Tool (GARI) - Chokmani, Karem; Oubennaceur, Khalid; Tanguy, Marion; Poulin, Jimmy; Gauthier, Yves; Latapie, Romain; Bernier, Monique (IGARSS 2019 - 2019 IEEE International Geoscience and Remote Sensing Symposium, 2019)
Floods are the most common natural hazard worldwide. GARI is a flood risk management and analysis tool that is being developed by the Environmental and Nordic Remote Sensing Group (TENOR) of INRS in Quebec City (Canada). Beyond mapping the flooded areas and water levels, GARI allows for the estimation, analysis and visualization of flood risks for individuals, residential buildings, and population. Information can therefore be used during the different phases of flood risk management. In the operational phase, GARI can use satellite radar images to map in near real-time the flooded areas and water levels. It uses an innovative approach that combines Radarsat-2 and hydraulic data, specifically flood return period data. Information from the GARI enable municipalities and individuals to anticipate the impacts of a flood in a given area, to mitigate these impacts, to prepare, and to better coordinate their actions during a flood.

Global Diversification of Natural Hazards: An analysis of the space- time dynamics of floods and tropical cyclones - Boudreault, M; Carozza, D (AXA-XL, 2019)

Using the CAUSE Model to Understand Public Communication about Water Risks: Perspectives from Texas Groundwater District Officials on Drought and Availability - VanDyke, Matthew S.; King, Andy J. (Risk Analysis, 2018)
Abstract Public communication about drought and water availability risks poses challenges to a potentially disinterested public. Water management professionals, though, have a responsibility to work with the public to engage in communication about water and environmental risks. Because limited research in water management examines organizational communication practices and perceptions, insights into research and practice can be gained through investigation of current applications of these risk communication efforts. Guided by the CAUSE model, which explains common goals in communicating risk information to the public (e.g., creating Confidence, generating Awareness, enhancing Understanding, gaining Satisfaction, and motivating Enactment), semistructured interviews of professionals ( N = 25) employed by Texas groundwater conservation districts were conducted. The interviews examined how CAUSE model considerations factor in to communication about drought and water availability risks. These data suggest that many work to build constituents’ confidence in their districts. Although audiences and constituents living in drought‐prone areas were reported as being engaged with water availability risks and solutions, many district officials noted constituents’ lack of perceived risk and engagement. Some managers also indicated that public understanding was a secondary concern of their primary responsibilities and that the public often seemed apathetic about technical details related to water conservation risks. Overall, results suggest complicated dynamics between officials and the public regarding information access and motivation. The article also outlines extensions of the CAUSE model and implications for improving public communication about drought and water availability risks.

The influence of impact-based severe weather warnings on risk perceptions and intended protective actions - Potter, Sally H.; Kreft, Peter V.; Milojev, Petar; Noble, Chris; Montz, Burrell; Dhellemmes, Amandine; Woods, Richard J.; Gauden-Ing, Sarah (International Journal of Disaster Risk Reduction, 2018)

Fiscal decentralization and natural hazard risks - Escaleras, Monica; Register, Charles A. (Public Choice, 2012)
At least to some extent due to pressure from international donors, many countries have become more fiscally decentralized the underlying premise being that greater decentralization might improve the provision of local public goods and services. We test this proposition by determining whether relatively more decentralized countries fare better when natural disasters strike in terms of its effects on the population. Overall, we find evidence supporting our maintained hypothesis, though the effect appears much more robust in developing countries.

Disaster disparities and differential recovery in New Orleans - Finch, Christina; Emrich, Christopher T.; Cutter, Susan L. (Population and Environment, 2010)
The historical disparities in the socio-demographic structure of New Orleans shaped the social vulnerability of local residents and their responses to Hurricane Katrina and its aftermath. These disparities, derived from race, class, gender, and age differences, have resulted in the uneven impact of the catastrophe on various communities in New Orleans, and importantly, their ability to recover. This article examines how the pre-existing social vulnerabilities within New Orleans interacted with the level of flood exposure to produce inequities in the socio-spatial patterns of recovery. Utilizing a combination of statistical and spatial approaches, we found a distinct geographic pattern to the recovery suggesting that the social burdens and impacts from Hurricane Katrina are uneven—the less flooded and less vulnerable areas are recovering faster than tracts with more vulnerable populations and higher levels of flooding. However, there is a more nuanced story, which suggests that it is neighborhoods in the mid-range of social vulnerability where recovery is lagging. While private resources and government programs help groups in the high and low categories of social vulnerability, the middle group shows the slowest rates of recovery. Further, it appears that the congressionally funded State of Louisiana Road Home Program (designed to provide compensation to Louisiana’s homeowners who suffered impacts by Hurricanes Katrina and Rita for the damage to their home) is not having a significant effect in stimulating recovery within the city.

Loss and damage attribution - Huggel, Christian; Stone, Dáithí; Auffhammer, Maximilian; Cramer, Wolfgang; Hansen, Gerrit (Nature Climate Change, 2013)
If research on attribution of extreme weather events is to inform emerging climate change policies, it needs to diagnose all of the components of risk.

Global mortality from storm surges is decreasing - Laurens M. Bouwer; Bouwer, Laurens M.; Sebastiaan N. Jonkman; Jonkman, Sebastiaan N. (Environmental Research Letters, 2018)
Changes in society's vulnerability to natural hazards are important to understand, as they determine current and future risks, and the need to improve protection. Very large impacts including high numbers of fatalities occur due to single storm surge flood events. Here, we report on impacts of global coastal storm surge events since the year 1900, based on a compilation of events and data on loss of life. We find that over the past, more than eight thousand people are killed and 1.5 million people are affected annually by storm surges. The occurrence of very substantial loss of life (g10000 persons) from single events has however decreased over time. Moreover, there is a consistent decrease in event mortality, measured by the fraction of exposed people that are killed, for all global regions, except South East Asia. Average mortality for storm surges is slightly higher than for river floods, but lower than for flash floods. We also find that for the same coastal surge water level, mortality has decreased over time. This indicates that risk reduction efforts have been successful, but need to be continued with projected climate change, increased rates of sea-level rise and urbanisation in coastal zones.

Evaluating Hydrologic Response in Tile‐Drained Landscapes: Implications for Phosphorus Transport - Macrae, M. L.; Ali, G. A.; King, K. W.; Plach, J. M.; Pluer, W. T.; Williams, M.; Morison, M. Q.; Tang, W. (Journal of Environmental Quality, 2019)
Phosphorus (P) loss in agricultural discharge has typically been associated with surface runoff; however, tile drains have been identified as a key P pathway due to preferential transport. Identifying when and where these pathways are active may establish high‐risk periods and regions that are vulnerable for P loss. A synthesis of high‐frequency, runoff data from eight cropped fields across the Great Lakes region of North America over a 3‐yr period showed that both surface and tile flow occurred year‐round, although tile flow occurred more frequently. The relative timing of surface and tile flow activation was classified into four response types to infer runoff‐generation processes. Response types were found to vary with season and soil texture. In most events across all sites, tile responses preceded surface flow, whereas the occurrence of surface flow prior to tile flow was uncommon. The simultaneous activation of pathways, indicating rapid connectivity through the vadose zone, was seldom observed at the loam sites but occurred at clay sites during spring and summer. Surface flow at the loam sites was often generated as saturation‐excess, a phenomenon rarely observed on the clay sites. Contrary to expectations, significant differences in P loads in tiles were not apparent under the different response types. This may be due to the frequency of the water quality sampling or may indicate that factors other than surface‐tile hydrologic connectivity drive tile P concentrations. This work provides new insight into spatial and temporal differences in runoff mechanisms in tile‐drained landscapes. Core Ideas Activation of surface runoff and tile flow differ with soil texture and season. Timing of flow path activation was used to infer hydrological processes. Connectivity between the surface and tiles exists on clay soil during growing season. Rapid connectivity between the surface and tiles occurs less frequently on loam.

Applying the Theory of Reliability to the Assessment of Hazard, Risk and Safety in a Hydrologic System: A Case Study in the Upper Sola River Catchment, Poland - Ozga-Zielinski, Bogdan; Adamowski, Jan; Ciupak, Maurycy (Water, 2018)

A novel method to estimate the maximization ratio of the Probable Maximum Precipitation (PMP) using regional climate model output - Rouhani, Hassan; Leconte, Robert (Water Resources Research, 2016)
The moisture maximization approach to estimate the Probable Maximum Precipitation (PMP) has a simple technique for controlling the risk of overestimating PMP: the maximization ratio is limited by an upper bound. The upper bound limit depends on storm records and watershed characteristics. However, it is not readily available in many watersheds. A robust scientific justification for limiting the maximization ratio is missing. In this paper, a novel approach is proposed to estimate the maximization ratio which does not impose an upper limit to the ratio. The new approach, which uses regional climate model data, is based on constructing annual maximum precipitable water time series with precipitable water values for which atmospheric variables are similar to the original event to be maximized. These time series are then used to estimate the 100-year return period precipitable water value required to calculate the maximization ratio. The new approach was tested in three watersheds in the province of Quebec, Canada. Results showed that maximization ratio values were lower than the proposed upper bound value for these watersheds. In comparison to the approach using an upper bound, this proposed approach reduced PMP in these watersheds by 11%. This article is protected by copyright. All rights reserved.

Control mechanisms of photosynthetic epibionts on zooplankton: an experimental approach - Bertolo, Andrea; Rodríguez, Marco A.; Lacroix, Gérard (Ecosphere, 2015)
Several top‐down and bottom‐up forces have been put forward to explain variable infestation rates of zooplankton by epibionts. Among top‐down forces, fish predation affects epibiont prevalence on zooplanktonic organisms, either by eliminating more conspicuous, heavily burdened individuals, or by reducing population size of zooplankton hosts, with consequences for substrate availability for epibionts. However, detailed experimental‐based information on the effects of top‐down forces is still lacking. Among bottom‐up forces, light can potentially control populations of photosynthetic epibionts. Therefore, both changes in light penetration in the water column and the vertical position of hosts in the water column could affect the photic conditions in which epibionts live and could thus control their population growth. We tested experimentally the hypothesis that both light limitation and fish predation affect epibiont burden on zooplankton. Moreover, we also tested the hypothesis that zooplanktivorous fish affect the prevalence and burden of the epibiotic alga Colacium sp. (Euglenida) on zooplankton not only by direct predation, but also by affecting the vertical distribution of zooplankton. We analyzed Colacium burden on two zooplankton genera that responded differently to the presence of zooplanktivorous fish by altering their daytime vertical distributions, thus exposing photosynthetic epibionts to different light conditions. Colacium burden on the two zooplankton genera was also compared between enclosures with different degrees of light limitation. Our results suggest that (1) ambient light limitation has the potential to reduce the burden of photosynthetic epibionts on zooplankton in natural conditions, and (2) zooplankton behavior (e.g., daytime refuge use to escape fish predation) can reduce the burden by exposing photosynthetic epibionts to suboptimal light conditions.

Delimitation of groundwater zones under contamination risk using a bagged ensemble of optimized DRASTIC frameworks - Barzegar, Rahim; Asghari Moghaddam, Asghar; Adamowski, Jan; Nazemi, Amir Hossein (Environmental Science and Pollution Research, 2019)

Multi-step water quality forecasting using a boosting ensemble multi-wavelet extreme learning machine model - Barzegar, Rahim; Asghari Moghaddam, Asghar; Adamowski, Jan; Ozga-Zielinski, Bogdan (Stochastic Environmental Research and Risk Assessment, 2018)

Influence of instrumentation on long temperature time series - Acquaotta, Fiorella; Fratianni, Simona; Aguilar, Enric; Fortin, Guillaume (Climatic Change, 2019)
In time series of essential climatological variables, many discontinuities are created not by climate factors but changes in the measuring system, including relocations, changes in instrumentation, exposure or even observation practices. Some of these changes occur due to reorganization, cost-efficiency or innovation. In the last few decades, station movements have often been accompanied by the introduction of an automatic weather station (AWS). Our study identifies the biases in daily maximum and minimum temperatures using parallel records of manual and automated observations. They are selected to minimize the differences in surrounding environment, exposition, distance and difference in elevation. Therefore, the type of instrumentation is the most important biasing factor between both measurements. The pairs of weather stations are located in Piedmont, a region of Italy, and in Gaspe Peninsula, a region of Canada. They have 6years of overlapping period on average, and 5110 daily values. The approach implemented for the comparison is divided in four main parts: a statistical characterization of the daily temperature series; a comparison between the daily series; a comparison between the types of events, heat wave, cold wave and normal events; and a verification of the homogeneity of the difference series. Our results show a higher frequency of warm (+10%) and extremely warm (+35%) days in the automated system, compared with the parallel manual record. Consequently, the use of a composite record could significantly bias the calculation of extreme events.

Strategies for integrating water management and spatial planning: Organising for spatial quality in the Dutch “Room for the River” program - Busscher, T.; Van Den Brink, M.; Verweij, S. (Journal of Flood Risk Management, 2019)
In response to extreme flood events and an increasing awareness that traditional flood control measures alone are inadequate to deal with growing flood risks, spatial flood risk management strategies have been introduced. These strategies do not only aim to reduce the probability and consequences of floods, they also aim to improve local and regional spatial qualities. To date, however, research has been largely ignorant as to how spatial quality, as part of spatial flood risk management strategies, can be successfully achieved in practice. Therefore, this research aims to illuminate how spatial quality is achieved in planning practice. This is done by evaluating the configurations of policy instruments that have been applied in the Dutch Room for the River policy program to successfully achieve spatial quality. This policy program is well known for its dual objective of accommodating higher flood levels as well as improving the spatial quality of the riverine areas. Based on a qualitative comparative analysis, we identified three successful configurations of policy instruments. These constitute three distinct management strategies: the “program‐as‐guardian”, the “project‐as‐driver,” and “going all‐in” strategies. These strategies provide important leads in furthering the development and implementation of spatial flood risk management, both in the Netherlands and abroad.
Keywords: Ouvrage_Collectif_Numéro1

ISO 31000 :. Management du risque – Principes et lignes directrices - International Standards Organisation (ISO) (Organisation internationale de normalisation, 2018)
Keywords: Ouvrage_Collectif_Numéro1

A process-based approach to restoring depositional river valleys to Stage 0, an anastomosing channel network - Powers, Paul D.; Helstab, Matt; Niezgoda, Sue L. (River Research and Applications, 2019)
Stream restoration approaches most often quantify habitat degradation, and therefore recovery objectives, on aquatic habitat metrics based on a narrow range of species needs (e.g., salmon and trout), as well as channel evolution models and channel design tools biased toward single-threaded, and “sediment-balanced” channel patterns. Although this strategy enhances perceived habitat needs, it often fails to properly identify the underlying geomorphological and ecological processes limiting species recovery and ecosystem restoration. In this paper, a unique process-based approach to restoration that strives to restore degraded stream, river, or meadow systems to the premanipulated condition is presented. The proposed relatively simple Geomorphic Grade Line (GGL) design method is based on Geographic Information System (GIS) and field-based analyses and the development of design maps using relative elevation models that expose the relic predisturbance valley surface. Several case studies are presented to both describe the development of the GGL method and to illustrate how the GGL method of evaluating valley surfaces has been applied to Stage 0 restoration design. The paper also summarizes the wide applicability of the GGL method, the advantages and limitations of the method, and key considerations for future designers of Stage 0 systems anywhere in the world. By presenting this ongoing Stage 0 restoration work, the authors hope to inspire other practitioners to embrace the restoration of dynamism and diversity through restoring the processes that create multifaceted river systems that provide long-term resiliency, meta-stability, larger and more complex and diverse habitats, and optimal ecosystem benefits.
Keywords: Ouvrage_Collectif_Numéro1

A systematic review of school‐based interventions and their outcomes for youth exposed to traumatic events - Yohannan, Justina; Carlson, John S. (Psychology in the Schools, 2019)
Abstract Youth exposed to traumatic events are at higher risk for negative developmental outcomes, including low academic performance, poor social skills, and mental health concerns. To best address these risks, school‐based intervention services, and trauma‐informed practices can be provided. The goal of this study was to systematically review the intervention research conducted on school‐based trauma interventions, with specific attention to examine intervention effectiveness, feasibility, and acceptability across studies. It was found that feasibility and acceptability are not frequently examined, though the data available showed that Enhancing Resiliency Amongst Students Experiencing‐Stress (ERASE‐Stress) and school‐based cognitive behavioral therapy (CBT) had high rates of fidelity; and school‐based CBT had high levels of acceptability. The review also examined demographic variables and found that U. S.‐based research reported racially/ethnically diverse samples, and most samples were from low‐income populations. Most studies examined youth exposed to war‐ and terror‐related traumas or natural disaster‐related traumas. Additionally, this review provides future directions for research and reveals the need for further research on intervention feasibility and acceptability. A brief description of practice recommendations based on prior research has also been included. It also exposes the need for studies that examine various student demographic variables that are currently not examined and consistency in rating scale use in school‐based trauma intervention research.
Keywords: Ouvrage_Collectif_Numéro1

Involving children in disaster risk reduction: the importance of participation - Pfefferbaum, Betty; Pfefferbaum, Rose L.; Van Horn, Richard L. (European Journal of Psychotraumatology, 2018)
Keywords: Ouvrage_Collectif_Numéro1

When disaster strikes: Under-insurance in Australian households - Booth, Kate; Tranter, Bruce (Urban Studies, 2018)
In undertaking what we believe is the first national-scale study of its kind, we provide methodologically transparent, statistically robust insights into associations and potential unfolding effects of house and contents under-insurance. We identify new dimensions in the complex relationship between householders and insurance, including the salience of interpersonal – and likely institutional – trust. Under-insurance is (re)produced along socio-economic and geographical lines, with those of lower socio-economic status or living in cities more likely to be under-insured. Should a disaster strike, such communities are likely to suffer further disadvantage, especially if governments continue to shift the responsibility for risk onto households. Our findings support the observation that insurance can contribute to increasing socio-economic urban polarisation in light of natural disasters. We conclude by considering how under-insurance may contribute to growing urban social stratification, as well as how it may produce situated ethical and political responses that exceed neoliberal aspirations.
Keywords: Ouvrage_Collectif_Numéro1

L'approche hydrogéomorphologique : pratiques, valorisations et développement d'une méthode de cartographie des zones inondables - Montané, Antonin (Université Paul Valéry - Montpellier III, 2014)
La connaissance de l’aléa inondation est un enjeu croissant pour la gestion du risque inondation. En France, afin de répondre à la demande des pouvoirs publics de cartographier les zones inondables, la cartographie hydrogéomorphologique émerge. Cette approche naturaliste, développée durant les années 1980, se propagea dans une large partie du Sud de la France. Aujourd’hui, la cartographie hydrogéomorphologique est une méthode reconnue pour sa fiabilité, mais elle stagne en termes d’applications et de développement dans de nouveaux territoires. Afin d’améliorer la connaissance de la prise en compte de la cartographie hydrogéomorphologique dans un cadre règlementaire, une analyse de 282 PPRI a été menée. Cette analyse a permis de dégager les modalités de prise en compte de la cartographie hydrogéomorphologique, mais également d’émettre des hypothèses sur les raisons de leur développement. La réalisation de MNZI (Modèle Numériques de Zones Inondables) sur des cours d’eau français et canadiens, a permis de mettre en avant l’adaptabilité de la cartographie hydrogéomorphologique à des contextes physiques différents, mais aussi d’apporter une réponse à la demande de prise en compte de cartographie de crue extrême de la Directive Inondation. L’évolution cartographique proposée dans ce travail comprend une réflexion autour de la légende des AZI, mais aussi sur le concept de cartographie positive. A travers les aspects cartographiques, règlementaires et géomorphologiques abordés, nous finissons par proposer un modèle de développement de la cartographie hydrogéomorphologique.
Keywords: Ouvrage_Collectif_Numéro1

Global assessment report on disaster risk reduction - Costs and benefits of early warning systems - Rogers, David; Tsirkunov, Vladimir (United Nations International Strategy for Disaster Reduction (UNISDR), 2011)
Keywords: Ouvrage_Collectif_Numéro1

River predisposition to ice jams: a simplified geospatial model - De Munck, Stéphane; Gauthier, Yves; Bernier, Monique; Chokmani, Karem; Légaré, Serge (Natural Hazards and Earth System Sciences, 2017)
Abstract. Floods resulting from river ice jams pose a great risk to many riverside municipalities in Canada. The location of an ice jam is mainly influenced by channel morphology. The goal of this work was therefore to develop a simplified geospatial model to estimate the predisposition of a river channel to ice jams. Rather than predicting the timing of river ice breakup, the main question here was to predict where the broken ice is susceptible to jam based on the river's geomorphological characteristics. Thus, six parameters referred to potential causes for ice jams in the literature were initially selected: presence of an island, narrowing of the channel, high sinuosity, presence of a bridge, confluence of rivers, and slope break. A GIS-based tool was used to generate the aforementioned factors over regular-spaced segments along the entire channel using available geospatial data. An ice jam predisposition index (IJPI) was calculated by combining the weighted optimal factors. Three Canadian rivers (province of Québec) were chosen as test sites. The resulting maps were assessed from historical observations and local knowledge. Results show that 77 % of the observed ice jam sites on record occurred in river sections that the model considered as having high or medium predisposition. This leaves 23 % of false negative errors (missed occurrence). Between 7 and 11 % of the highly predisposed river sections did not have an ice jam on record (false-positive cases). Results, limitations, and potential improvements are discussed.
Keywords: Ouvrage_Collectif_Numéro1

La méthode hydrogéomorphologique de détermination des zones inondables - Ballais, Jean-Louis; Chave, Sylvain; Dupont, Nadia; Masson, Éric; Penven, Marie-Josée (Physio-Géo. Géographie physique et environnement, 2011)
L'ouvrage fait le point sur les développements de la méthode mise au point dans les années 1980 et présentée en détail pour la première fois en 1996. Il s'organise en deux grandes parties : la présentation de la méthode hydrogéomorphologique de détermination des zones inondables et les applications de cette méthode. La première partie justifie d'abord la nécessité de mettre au point et d'utiliser une nouvelle méthode face aux insuffisances des méthodes hydrologiques-hydrauliques utilisées en France (et très généralement dans le monde) pour la prévision et la prévention des risques d'inondation.Elle présente ensuite les principes de la méthode (chapitre II). C'est ainsi qu'elle consacre un long développement au rôle fondamental de la géomorphologie, tout particulièrement aux quatre lits qu'un cours d'eau peut occuper en fonction de son débit, lits déterminés par l'analyse de la microtopographie de la plaine alluviale fonctionnelle complétée par leur caractérisation sédimentologique. L'influence de la lithologie et de la tectonique est ensuite évoquée. Un deuxième sous-chapitre présente les critères complémentaires : la couverture végétale naturelle et l'occupation humaine au travers de la localisation des constructions, des vestiges historiques et archéologiques, de l'adaptation de l'activité agricole aux caractéristiques de la plaine alluviale et de la structure du parcellaire. Un troisième sous-chapitre regroupe les facteurs de variation : les grandes zones climatiques et les facteurs anthropiques (travaux et ouvrages hydrauliques, pratiques agricoles, imperméabilisation des sols due à l'urbanisation). Enfin, l'évolution au cours de la période historique des unités hydrogéomorphologiques principales, lit mineur et lit majeur, est présentée.Le court chapitre III met en relation l'hydrogéomorphologie et le fonctionnement hydraulique à l'échelle des unités hydrogéomorphologiques puis au niveau de la modélisation. La deuxième partie présente les trois principales applications de la méthode : la cartographie des zones inondables, la méthode intégrée et l'aménagement. La cartographie des zones inondables est actuellement la principale application, grâce à son intégration dans la politique de prévision et de prévention des risques d'inondation en France depuis 1995. Le chapitre qui lui est consacré s'articule en trois ensembles. Le premier est un rappel critique des moyens techniques d'acquisition des données : cartes, photographies aériennes, imagerie satellite en plein développement, données relatives aux crues historiques, observations de terrain. Le deuxième sous-chapitre détaille la cartographie des données sous la forme de la carte hydrogéomorphologique ou carte d'inondabilité hydrogéomorphologique en faisant l'historique et la critique de la légende proposée par le Ministère de l'Écologie français, puis en traitant plusieurs problèmes de cartographie : l'exhaussement du lit majeur, l'adoucissement du talus externe de la plaine alluviale fonctionnelle par le ruissellement diffus, le recouvrement du talus de la terrasse alluviale par le colluvionnement, la représentation du lit majeur exceptionnel et de la terrasse alluviale holocène, le cas spécifique des vallons secs. Enfin, les premières cartographies réalisées à l'étranger sont présentées. Un court dernier sous-chapitre traite de l'interprétation, qualitative et semi-quantitative, de la carte hydrogéomorphologique.La méthode intégrée, qui reste pour l'essentiel au stade expérimental, est présentée dans le chapitre II : d'abord ses origines, puis ses principes, puis ses premières applications prometteuses en France.Le chapitre III regroupe les potentialités, importantes mais peu exploitées, de la méthode hydrogéomorphologique pour l'aménagement des plaines alluviales, en insistant sur deux points : les conséquences de l'exhaussement des lits majeurs et le fonctionnement des cours d'eau pendant les crues exceptionnelles. La conclusion générale insiste sur l'efficacité de cette méthode, née de la problématique des risques naturels et hors du champ académique, ainsi que sur sa fécondité, en particulier la découverte de nouveaux objets géomorphologiques comme le lit majeur exceptionnel et de nouveaux concepts comme celui de débit hydrogéomorphologique.
Keywords: Ouvrage_Collectif_Numéro1

Stochastic Richelieu River Flood Modeling - Safari, Maryam (École Polytechnique de Montréal, 2018)
RÉSUMÉ: La modélisation hydrodynamique est un élément fondamental du génie hydraulique. Elle permet de créer des modèles de bassins versants et de rivières pour la prédiction des inondations. La simulation des phénomènes d'inondation est un sujet de plus en plus important dans le domaine de la recherche en hydraulique. Compte tenu des exigences d'évaluation spécifiques dans les plans d'ingénierie des risques d'inondation, la modélisation des inondations devient très importante dans le génie hydraulique. La délimitation probabiliste des zones inondables joue un rôle déterminant dans les plans d'ingénierie des risques. Cette tâche importante est réalisable à l'aide de la simulation post-inondation et de la détermination des limites de l'étendue des inondations avec leurs probabilités d'occurrence correspondantes dans les zones étudiées. ABSTRACT: Hydrodynamic modeling including watershed, river and flood modeling is a fundamental part of hydraulic engineering. In this regard, simulation of flood phenomena is an increasingly important subject in hydraulic research domain. Considering specific evaluation requirements in flood risk engineering plans, flood modeling is becoming highly important based on hydrological method (rainfall-runoff) or hydraulic parameters in Hydraulic engineering.

Livelihood vulnerability to climatic stresses: A study of the northeastern floodplain communities of Bangladesh - Rahman, H.M. (2018)
Climatic stress vulnerability has cross-scaler influences on development interventions, particularly in developing countries. While most of climate adaptation plans and interventions are developed at national or international scales, relatively little attention has been paid to incorporate the contextual properties of climate vulnerability in adaptation-related decision making. Focusing on the wetland ecosystem dominated northeastern floodplain communities of Bangladesh, this exploratory research seeks to better understand how locally-specific socio-economic and biophysical properties serve to compound vulnerability to climatic stresses; how community members use their resources and assets in order to reduce their sensitivity to climatic stresses; and the extent to which government adaptation programmes reflect context-specific adaptation demands. Recognizing that Bangladesh is widely acknowledged to be one of the most climate-vulnerable countries in the world, this dissertation begins with a systematic literature review of the state of knowledge related to climate change impacts in Bangladesh. Results indicate a shortage of context specific scientific studies and identify that northeastern floodplain region is the most understudied area in the country. Issues related to multidisciplinary research approaches and geographic connectedness of research efforts point to potential limitations in the evidence base used to support public policy initiatives on climate change adaptation. A participatory climate stress exposure assessment reveals that local biophysical changes and resource use behaviors significantly contribute to compounding the impacts of climatic stresses. However, these observations are generally poorly represented in local-level climate model-based stress assessments. Results reveal that community stress perceptions are largely determined by the temporal occurrence of a climatic event, with a climatic event considered a stress if it occurs in their production period and causes losses to their productivity. Stress perceptions are also influenced by household resource ownership, local innovation and technological uses. Using the sustainable rural livelihood approach, a mixed method study is then used to better understand the actions taken by households to reduce their livelihood sensitivity to climatic stresses. Households were found to organize, transform and combine their capital assets for generating different livelihood portfolios. Using diverse combinations of assets, two strategies were observed: 1) extending external networks in order to create non-natural resource dependent livelihood opportunities; and 2) extending uses of available natural resources. Both of these strategies required external supports from government programmes or market mechanisms. Finally, a climate change policy analysis of Bangladesh, supported with key informant interviews, is presented to assess how different government policy interventions have supported local adaptation initiatives. The results reveal that despite recent advancements in climate change related policy making and institutional changes for supporting local adaptation actions in Bangladesh, plans and policies often fail to respond to local demands. More specifically, the existing climate change adaptation planning and policy processes tend to lack wider public participation and have inadequate coordination with natural resource management policies. This dissertation considers the diverse socio-economic and social-ecological contexts of climate vulnerability in rural Bangladesh. The results offer important research and policy insights to developing more a systematic understanding of climate vulnerability, and how local knowledge might be better integrated into national and international policy processes.

Caractériser et évaluer la capacité d'adaptation des communautés face aux risques naturels : le cas de Saint-Raymond - Hume, Jonathan (2019)
Les changements climatiques impactent de plus en plus la vie, le développement et la vulnérabilité de plusieurs communautés à travers le monde, lesquelles devant de plus en plus mitiger les risques naturels. Au Québec, la gestion des risques présente une philosophie de « retour à la normale » qui se penche davantage sur les dimensions d’intervention et de rétablissement. Cependant, à la lumière des incertitudes amenées par les changements climatiques, il est impératif que les communautés québécoises aient les capacités d’augmenter leur résilience face aux risques naturels qui s’accentuent rapidement. Ainsi, la capacité d’adaptation doit se retrouver au cœur de la gestion des risques. Cela dit, il existe peu d’outils d’évaluation de la capacité d’adaptation au Québec, entendue comme l’ensemble des ressources dynamiques disponibles et accessibles qui permettent une augmentation de la résilience et une diminution de la vulnérabilité en transformant positivement une communauté et son environnement. La présente recherche vise ainsi à développer une méthode d’analyse de la capacité d’adaptation des individus et des communautés québécoises touchées par les inondations à l’aide de systèmes d’information géographique (SIG), en utilisant la Ville de Saint-Raymond de Portneuf comme étude de cas. Ce projet se base principalement sur les concepts de vulnérabilité, de résilience et d’adaptation pour recenser des indicateurs pouvant servir à caractériser et évaluer la capacité des personnes et municipalités exposées aux inondations à mobiliser les ressources nécessaires pour non seulement atténuer les risques lors de tels événements, mais aussi mieux les prévenir et s’en préparer. Des données socioéconomiques et d’aménagement du territoire sont notamment mises à profit pour des fins d’analyse de même que des données issues d’un sondage effectué en 2014 à la suite d’une inondation majeure par la CAPSA, l’organisme de bassin versant de la région de Portneuf, en collaboration avec le comité Rivière de la Ville de Saint-Raymond.

Gestion intégrée des catastrophes en Afrique Subsaharienne : rôle de l’assurance, pour un système de gestion performant et la résilience des populations au Bénin - Goundjo, Antoine (2018)
Les variabilités et changements climatiques et les incapacités pour faire face à leurs risques, à leurs effets et, plus précisément, à gérer les catastrophes hydrométéorologiques (inondation et sécheresse) qui les accompagnent, viennent en ajouter aux vulnérabilités et aux problèmes, qui sont déjà une préoccupation en Afrique Subsaharienne et au Bénin. Face à leurs manifestations de plus en plus récurrentes – la faiblesse des systèmes de financement local de la gestion des catastrophes et le déficit des systèmes de protection sociale, qui témoignent des limites des capacités de transfert des risques de catastrophe – cette étude a identifié la structure (gouvernance-ressources), comme le problème essentiel de la gestion des catastrophes au Bénin. Une étude synthétique, étude de cas multiples avec trois niveaux d’analyse imbriqués, dans une approche qualitative, a permis de mieux comprendre comment, dans un contexte de pauvreté, l’intégration de la micro assurance climatique, modifie la structure, le processus et le résultat de la gestion des catastrophes et assure la performance du système et la résilience des populations. Elle a documenté les différents aspects de la structure et des vulnérabilités des systèmes et des populations et a identifié l’absence d’intégration de la micro assurance climatique aux systèmes de gestion des catastrophes, comme un problème au coeur de la complexité des déterminants de la résilience, aussi confrontée à une autre complexité, celle de la diversité des interconnexions entre les différentes catégories de risques, qui place la santé au coeur de tous les risques. La nécessité d’une gestion holistique du risque global, ou d’une gestion tout risque, telle que retenue par le Cadre d’Action de Hyōgo et le Cadre d’Action de Sendai; et l’importance d’apporter une réponse en accord au contexte et à son profil de risques, qui prend l’option pour la "démocratisation" d’une micro assurance climatique, gouvernée sur la base de fondements idéologiques d’équité et d’efficience, cette recherche a préconisé – pour une gestion plus rationnelle, pertinente, efficace et efficiente des catastrophes – une intégration de trois systèmes : le système de la gestion des catastrophes; le système de protection sociale, y compris celui de la micro assurance climatique, et le système de la santé; tous reconnus outillés pour la gestion des risques. Elle a retenu, qu’une telle approche saurait aussi assurer une gestion efficace du changement qu’induirait l’intégration de la micro assurance climatique à la gestion des catastrophes; de ii même qu’une meilleure utilisation des outils et méthodes de sensibilisation, de prévention, de prévision et d’évaluation des risques et des dommages dont recèlent les pratiques en micro assurance climatique. Elle constate que la réussite de l’intégration de la MAC et son développement sont essentiellement plus déterminés par les acteurs et leurs intérêts, que par les ressources financières, même si elles sont aussi indispensables. Cette recherche préconise qu’à partir de choix de modèles et de modes d’intégration bien étudiés, son intégration ou sa prise en compte dans les différents programmes d’aide et de protection sociale mis en oeuvre au Bénin pourrait être, à travers les subventions de l’État, un moyen de mobilisation de fonds en faveur de son financement et de sa viabilité/durabilité. Ce financement pourra aussi s’appuyer sur les mécanismes traditionnels de financement de l’assurance, de la micro assurance, des changements climatiques et de la réduction des risques de catastrophe au Bénin, en Afrique et dans le monde. C’est pourquoi, en termes de gouvernance, ce travail soutien une restructuration avec une gestion entièrement centrée sur les communes, dans une approche des services de première ligne avec les réseaux de services ; en termes de ressources, il a aussi analysé les conditions et les possibilités de développement d’une micro assurance climatique, qui dépend avant tout de la qualité de la gestion des catastrophes (capacités à réduire les risques et limiter les pertes ou capacités à induire la résilience des systèmes et des populations). Cette approche puise dans les réalités et pratiques endogènes de gestion des catastrophes et surtout de protection sociale ou de transfert de risques ; elle s’inspire des bonnes pratiques d’ailleurs ; elle contribue à instaurer l’équité, comme principe de la gestion intégrée des catastrophes et, au-delà de la résilience, à susciter une convergence des efforts pour l’autonomisation de la structure et des populations, face aux manifestations catastrophiques des inondations et de la sécheresse. Cette recherche pense qu’il faut oser la micro assurance universelle pour la gestion des catastrophes hydrométéorologiques; qu’elle est réalisable ou faisable, même en contexte de pauvreté; et qu’il est aussi possible de combiner micro assurance climatique universelle et assurance médicale universelle, dans une dynamique qui mobilise des approches efficientes et les intérêts.

Vulnérabilité aux inondations et adaptation villageoise à Hanoi, Vietnam : opportunités et contraintes dans un contexte de périurbanisation rapide - Labelle-Giroux, Francis (2018)
Au Vietnam, l’adaptation aux inondations en milieu rural est indissociable des gestes informels posés par les ménages à l’échelle micro. Dans le contexte de transition urbaine rapide qui caractérise actuellement le pays, ces ménages et les communautés auxquelles ils appartiennent subissent des pressions socio-économiques et environnementales majeures en lien avec l’urbanisation de leur milieu de vie. À travers l’étude de cas d’une communauté villageoise périurbaine de Hanoi, ce mémoire cherche à comprendre comment ces perturbations affectent la vulnérabilité aux inondations des populations préexistantes ainsi que leurs capacités à s’y adapter. L’analyse est centrée sur la micro-échelle, une approche jusqu’ici principalement utilisée dans les études en milieu rural au Vietnam. Appliquée au contexte périurbain de Hanoi, à l’aide d’enquêtes par questionnaire et d’entretiens semi-dirigés, cette approche précise et nuance les conséquences que peut avoir l’urbanisation sur la vulnérabilité et l’adaptation aux inondations. Elle révèle les façons dont les ménages perçoivent leur vulnérabilité et leur capacité à la réduire dans le contexte transitoire actuel. L’analyse démontre que la périurbanisation de Hanoi affecte les moyens de subsistance de manière contrastée au sein des communautés villageoises en cours d’urbanisation. Ces impacts différenciés d’un ménage à l’autre influencent leur capacité d’adaptation et la trajectoire d’adaptation qu’ils empruntent face aux inondations. Certains profitent des nouvelles opportunités économiques liées à l’urbanisation de leur milieu de vie pour réduire leur vulnérabilité et ainsi contrebalancer les effets pervers qu’entraîne ce même processus sur la gravité des inondations. D’autres sont plutôt contraints de vivre dans un état de vulnérabilité exacerbé par leur manque de moyens et la précarité de leurs moyens de subsistance. Finalement, les résultats suggèrent que les opportunités d’adaptation observées dans le présent n’assurent pas automatiquement une préparation adéquate dans un avenir où tant les changements climatiques que l’urbanisation risquent d’être plus soutenus.

Étude des facteurs contrôlant la présence de l’algue Didymosphenia geminata et des impacts de sa présence sur le saumon atlantique juvénile. - Gillis, Carole-Anne (Université du Québec, Institut national de la recherche scientifique, 2018)
L’algue Didymosphenia geminata est une diatomée à potentiel envahissant. Cette algue microscopique, attachée au substrat, peut sécréter des quantités phénoménales de mucilage et créer de vaste amas fibreux tapissant le lit d’une rivière. Autrefois considérée très rare et représentative d’une qualité d’eau impeccable, elle est maintenant répertoriée omniprésente dans les rivières oligotrophes à travers le monde. Au cours des deux dernières décennies, son émergence a créé un intérêt marqué de la part des écologistes et gestionnaires de rivières puisque sa biologie et les facteurs régissant son occurrence et sa sévérité sont méconnus. Au Québec, c’est à l’été 2006 que les premières proliférations massives de l’algue didymo ont été observées dans la rivière Matapédia. Le manque de connaissances à son égard, plus précisément sur sa distribution, les causes de l’apparition des proliférations et de l’impact négatif possible de cet envahissement sur le réseau trophique mais surtout sur le cycle de vie du saumon atlantique en rivière a créé un état de panique chez les gestionnaires et les utilisateurs des rivières à saumon. Il existait dès lors un urgent besoin de combler ces lacunes. Afin de mieux comprendre les facteurs régissant tant la croissance cellulaire que la croissance des amas mucilagineux, un modèle conceptuel a été élaboré grâce à la collaboration de plusieurs chercheurs travaillant au Colorado, à l’île de Vancouver, en Nouvelle-Zélande et au Québec afin de colliger les observations et les données de terrain. Ce travail de synthèse a permis d’identifier les facteurs favorisant sa colonisation, sa croissance et sa persistance en rivière. La dynamique spatio-temporelle de l’algue didymo est dépendante de divers facteurs (ou conditions environnementales) dont les seuils critiques déterminent son comportement de prolifération. En rivière, la croissance d’algues benthiques est principalement déterminée par les variations saisonnières du débit, la température, la lumière et la chimie de l’eau. Ainsi, la connaissance des paramètres d’habitats favorables permet de déterminer si un bassin versant est favorable à la présence cellulaire de l’algue didymo et à la probabilité que celle-ci puisse y proliférer. Le modèle conceptuel permet d’établir la variabilité et la sévérité saisonnière du comportement envahissant de l’algue didymo en rivière. Afin d’appliquer le modèle conceptuel développé à l’échelle du bassin versant, nous avons mis sur pied un réseau de suivi volontaire des proliférations d’algue didymo dans le bassin versant de la rivière Restigouche. Vingt-deux organisations différentes totalisant 70 bénévoles ont été formés à identifier et quantifier les proliférations d’algue didymo. Entre 2010 et 2015, 1 228 observations ont été réalisées. L’analyse de cette base de données, nous a permis de déterminer que 71% de la variabilité de la sévérité des proliférations durant l’été est inversement proportionnelle à l’intensité de la crue printanière. À l’échelle du tronçon, l’analyse des proliférations pour différents types de faciès-substrat a permis de d’identifier une préférence accrue pour les seuils. Par la suite, afin d’appliquer le modèle conceptuel à l’échelle régionale, nous avons comparé la distribution de l’algue didymo dans trois régions de l’est du Québec (i.e. Gaspésie, Bas-St-Laurent et Côte-Nord) avec divers paramètres physico-chimiques de vingt-neuf rivières à saumon. Le principal facteur régissant la présence-absence de cellules est le pH. Les diatomées ont des optimums de pH très spécifiques et la géologie contrastante de la Côte-Nord (Bouclier canadien) par rapport aux basses terres du Saint-Laurent et les Appalaches en Gaspésie, a permis d’identifier que les eaux acides riches en tanins et lignines ne sont pas favorables à la survie et la croissance de l’algue didymo. Grâce à une meilleure connaissance des facteurs de contrôle de l’algue didymo à diverses échelles spatiales, nous pouvons déterminer les rivières à risque de proliférations massives. Au sein des rivières exhibant des proliférations, nous avons déterminé que les préférences d’habitat de l’algue didymo sont identiques à celles du saumon atlantique juvénile (i.e. eaux rapides, peu profondes, claires, froides, faible en nutriments avec un substrat grossier). Afin de déterminer l’ampleur de l’impact de la présence des proliférations sur le réseau trophique, nous avons vérifié son impact sur la communauté algale. La structure dense et fibreuse crée un environnement physique dans lequel plusieurs diatomées peuvent s’y loger. Nos résultats confirment que l’algue crée un habitat de choix pour les plus petites diatomées favorisant ainsi une plus grande diversité taxonomique. Malgré une augmentation de la complexité du biofilm suivant son épaississement, il n’y a pas d’impact supplémentaire sur la structure et la diversité taxonomique des échantillons. Puisque la structure de l’habitat est modifiée par les tapis et que ces derniers sont susceptibles d’altérer la structure et le fonctionnement de l’écosystème, nous avons évalué l’effet des proliférations sur le comportement alimentaire des saumons juvéniles. Grâce à l’observation en apnée du comportement, nous pouvons conclure que les saumons juvéniles effectuent une plus grande proportion de quêtes benthiques en fonction du pourcentage de recouvrement algal. Ce changement de comportement n’est pas attribuable à une diminution des proies disponibles au sein de la dérive. Notre étude confirme la grande plasticité comportementale des saumons juvéniles face aux modifications de l’habitat. Afin de vérifier l’impact des proliférations sur les ressources alimentaires et la diète des saumons juvéniles, nous avons utilisé l’approche par analyse d’isotopes stables. Cette approche permet d’établir un portrait intégré de l’utilisation des ressources par les poissons. Les signatures isotopiques divergentes entre les différents tissus des saumons confirment une modification de la diète saisonnière. Les saumons juvéniles en présence de l’algue didymo ont une diète moins diversifiée et appauvrie en carbone principalement composée de petits chironomides et de trichoptères. Malgré que l’indice de condition physique des saumons juvéniles soit similaire entre les deux sites, leur taille est plus petite dans le site avec proliférations. Les travaux futurs devront tenter de valider l’impact de la diminution de la qualité de la diète par les proliférations d’algue didymo sur le contenu en lipides des juvéniles. Suite aux diverses collaborations internationales et discussions avec les gestionnaires, nous nous sommes rendus à l’évidence qu’il devait y avoir une recommandation sur les mesures de gestion vis-à-vis cette espèce. En fonction des connaissances scientifiques développées au fil des ans et plusieurs cas de gestion dans divers pays, nous avons recommandé aux gestionnaires d’éduquer les utilisateurs à vérifier, nettoyer, sécher et congeler leurs équipements. Que l’algue didymo soit une espèce exotique ou indigène, elle peut être propagée. De plus, la mise en valeur des saines pratiques permettent de limiter la propagation d’autres organismes pouvant potentiellement être plus dévastateurs que l’algue didymo. Les résultats de cette thèse contribuent à l’avancement des connaissances sur les facteurs de contrôle de l’algue didymo tant à l’échelle microscopique que macroscopique. En plus d’avoir contribué à élaborer le modèle conceptuel, nous l’avons amélioré en l’appliquant à diverses échelles spatiales : à l’échelle du tronçon et du bassin versant ainsi qu’à l’échelle régionale. C’est d’ailleurs la première étude à élaborer un réseau de suivi des proliférations par l’implication des acteurs du milieu ainsi qu’une des seules études à avoir examiné la variabilité interannuelle sur une période de six ans. C’est également la première étude à avoir évalué l’impact de l’algue didymo sur les communautés périphytiques dans l’est du Canada. De surcroît, c’est la première étude exhaustive qui a évalué l’effet des proliférations sur l’écologie du saumon atlantique juvénile. Les recherches menées sur le comportement alimentaire est également novateur et contribue considérablement à la compréhension des mécanismes et les interactions entre les divers niveaux trophiques et l’impact sur les salmonidés. Didymosphenia geminata is mat-forming nuisance diatom. This epilithic microscopic alga can secrete copious amounts of mucilage creating thick and extensive mats covering the entire riverbed. Once considered very rare and representative of pristine water quality, it is now ubiquitous in rivers around the world. Over the past two decades, this alga has emerged as a nuisance diatom and generated much interest among freshwater ecologists and river managers alike. Nonetheless, controlling factors governing the occurrence and severity of D. geminata are still not well understood. In Quebec, the first massive proliferations of D. geminata were reported in 2006 in the Matapedia River. There was an urgency to fill this knowledge gap as managers and government agencies panicked at the lack of knowledge regarding its distribution, the causes of its onset and mostly, fear of that this alga would act as an additional stressor to Atlantic salmon populations. To better understand controlling factors of both cell division and mat formation, a conceptual model was developed with the collaboration of several researchers working in Colorado, Vancouver Island, New Zealand and Quebec to collate observations and field data. This synthesis work helped identify the factors favoring its colonization, growth and persistence in rivers. The spatiotemporal dynamics of D. geminata are dependent on various dynamic thresholds of flow, temperature, light and water chemistry within the habitat window. We can therefore test various arrays of these parameters to determine whether rivers are likely to present occasional to persistent D. geminata mats. To test and improve upon the conceptual model at various spatial scales, we developed a monitoring network for D. geminata mat presence. Twenty-two different organizations totaling 70 volunteers were trained to identify and quantify the proliferations of D. geminata. Between 2010 and 2015, 1 228 observations were made. The analysis of this database helped determine that 71% of the variability of D. geminata severity is inversely proportional to the intensity of the spring flood. At the reach scale, habitat type was determinant for presence-absence of mats with a strong significant preference for riffles. At the provincial scale, we compared the distribution of D. geminata in three regions of eastern Quebec (i.e. Gaspesie, Bas-St-Laurent and Cote-Nord) against numerous water chemistry parameters for twentynine rivers. At the broad regional scale, pH was the most important factor governing the presence-absence of cells. Diatoms have very specific pH optima and the contrasting geologies between regions confirmed that low pH and high tannins and lignin are not favorable to the survival and growth of D. geminata. Habitat preferences for D. geminata mats are identical to those of juvenile Atlantic salmon (i.e. shallow, fast, clear, cool, low nutrient and coarse substrate). To determine the extent of the impact of the presence of mats on the food web, we verified its impact on the algal community. The dense interwoven matrix creates a suitable physical environment for small diatoms, thus promoting greater taxonomic diversity. Despite an increase in the complexity of the biofilm with mat accrual, there is no additional impact on the structure and taxonomic diversity of the samples. D. geminata effects to higher trophic levels have been suspected since the structure of the habitat is modified and could alter the structure and functioning of the ecosystem. We studied the foraging behaviour of juvenile Atlantic salmon in contrasting D. geminata severities. With increasing percent cover of the alga, juvenile Atlantic salmon switch from a drift-foray to benthic-foray strategy. This change in behavior is not due to limited drifting prey availability. Our results reinforce the notion that juvenile Atlantic salmon have high behavioral plasticity in response to habitat changes. To test the impact of mats on juvenile salmon diet, we used a stable isotope analysis approach. This approach provides an integrated view of resource use by fish. Contrasting isotopic signatures between the liver and muscle tissues confirm a change in the seasonal diet. Juvenile salmon sampled in the D. geminata impacted site have a less diversified and carbon-depleted diet composed mainly of small chironomids and Trichoptera. Juvenile salmon condition factors and C:N ratios were not different between sites, though their size is smaller in the impacted site. Future work should focus on the effects of reduced prey quality on lipid content of fish. Over various international collaborations and discussions with managers, it became clear that there was a need for a clear and standardized recommendation on management measures for this nuisance species. Based on recent scientific knowledge and several management cases in various countries, we recommended that managers educate users to check, clean, dry and freeze their equipment. Regardless of whether D. geminata is an exotic or native species, it can be spread. In addition, the development of best practices limits the spread of aquatic organisms as others may be far more devastating than D. geminata. The results of this thesis contribute to the advancement of knowledge on the controlling factors of D. geminata for both cells and mats. In addition to contributing to the development of the conceptual model, we have tested and improved it by applying it to a variety of spatial scales: at the reach, watershed and regional scales. This is the first study to develop a monitoring network for mat severity with the involvement of local stakeholders. It is also the first study to evaluate the impact of D. geminata on periphytic communities in eastern Canada. Moreover, it is the first comprehensive study that has evaluated the effect D. geminata mats on juvenile Atlantic salmon ecology. Research on foraging behavior is also innovative and contributes significantly to the understanding of the mechanisms and interactions by which D. geminata impacts various trophic levels and salmonids.

Suivi en temps réel de l’aléa inondation par cameras de surveillance : estimation du niveau de l’eau. - Latapie, Romain (Université du Québec, Institut national de la recherche scientifique, 2018)
Les inondations constituent l’un des risques naturels les plus fréquents. Une inondation historique survenue au Québec s’est produite aux abords de la rivière Richelieu entre avril et juin 2011. Suite aux dommages et aux frais occasionnés par cet épisode, l’INRS s’est engagé avec la ville de Saint-Jean-sur-Richelieu afin de la doter d’un système de Gestion et d’Analyse du Risque d’Inondation (GARI) : le niveau d’eau constitue une donnée essentielle pour l’évaluation de l’ampleur d’une inondation en temps réel. Ce travail de recherche a pour objectif de détecter automatiquement la ligne d’eau sur des images acquises par des caméras placées aux abords de la rivière Richelieu par des méthodes d’analyse d’images et de convertir cette dernière en niveau d’eau par stéréoscopie (transfert des valeurs en pixels en unité métrique). Le premier volet de ce travail de recherche s’intéresse à l’extraction automatique de la ligne d’eau à partir de données acquises par des caméras de surveillance. Afin de répondre à cette exigence, des séquences d’images de durée déterminée (une minute) ont été enregistrées et une image moyenne a été calculée pour chaque séquence. L’image moyenne est ensuite segmentée puis classifiée à l’aide d’une technique supervisée. Pour la première séquence d’images à traiter, des sites d’entraînement décrivant les parties immergées et libres sont créées afin d’obtenir deux classes de sortie correspondant aux surfaces d’eau et au reste de l’image. Une détection de contour permet d’isoler les pixels de la ligne d’eau. Pour les séquences suivantes, l’algorithme utilise automatiquement la ligne d’eau créée à la séquence précédente pour définir les sites d’entraînements à la séquence considérée. Le taux de réussite d’extraction de la ligne d’eau avoisine 90%. Le second volet consiste à convertir les coordonnées des pixels de la ligne d’eau du système bidimensionnel image vers un système tridimensionnel dans un référentiel connu. Les observations par stéréoscopie permettent cette transformation via les procédures d’orientation intérieure des caméras et d’orientation extérieure des couples stéréoscopiques. Pour le modèle de caméra considéré, les tests effectués montrent que les erreurs de positionnement planimétrique de la ligne d’eau sont inférieures au mètre et l’erreur de positionnement altimétrique (niveau d’eau) est inférieure à 10 cm lorsque le rapport entre la base stéréoscopique et la distance avec l’objet à modéliser est supérieur à 0.1. Flooding is one of the most common natural hazards. A historic flood occurred in the vicinity of the Richelieu River (Province of Quebec, Canada) between April and June 2011. After the damages and expenses incurred by this episode, INRS and the city of Saint-Jean-sur-Richelieu decided to create a flood risk management and analysis system : water level is an essential factor for assessing magnitude of a flood in real time. This research project aims to automatically detect the water line on images acquired by cameras located near the Richelieu River with image analysis methods and to convert it to water level by stereoscopy (transfer of values from pixel unit to metric unit). The first part of this research work focuses on automatic extraction of water line from data acquired by surveillance cameras. In order to meet this requirement, fixed-duration (one minute) image sequences were recorded and an average image was calculated for each sequence. Average image is then segmented and classified using a supervised technique. For the first sequence of images to be processed, training sites describing submerged and free portions are created to obtain two output classes corresponding to water and the rest of the image. Then, a contour detection is used to determine water line. For the following sequences, the algorithm automatically uses water line created in the previous sequence to define training sites for the present sequence. Success rate of water line extraction is around 90%. Second part consists in converting pixels coordinates of water line known in a two-dimensional image system to a three-dimensional system in a known reference frame. Stereoscopic observations allow this transformation via interior and exterior orientations procedures. For the camera model considered in this project, tests highlight that planimetric positioning errors of the water line are lower than 1 m and altimetric positioning error (water level) is lower than 10 cm when the ratio between stereoscopic basis and distance to the object to be modeled is higher than 0.1.

Multi-scale temporal variability in meltwater contributions in a tropical glacierized watershed - Saberi, Leila; McLaughlin, Rachel T.; Ng, G.-H. Crystal; La Frenierre, Jeff; Wickert, Andrew D.; Baraer, Michel; Zhi, Wei; Li, Li; Mark, Bryan G. (Hydrology and Earth System Sciences, 2019)
Abstract. Climate models predict amplified warming at high elevations in low latitudes, making tropical glacierized regions some of the most vulnerable hydrological systems in the world. Observations reveal decreasing streamflow due to retreating glaciers in the Andes, which hold 99 % of all tropical glaciers. However, the timescales over which meltwater contributes to streamflow and the pathways it takes – surface and subsurface – remain uncertain, hindering our ability to predict how shrinking glaciers will impact water resources. Two major contributors to this uncertainty are the sparsity of hydrologic measurements in tropical glacierized watersheds and the complication of hydrograph separation where there is year-round glacier melt. We address these challenges using a multi-method approach that employs repeat hydrochemical mixing model analysis, hydroclimatic time series analysis, and integrated watershed modeling. Each of these approaches interrogates distinct timescale relationships among meltwater, groundwater, and stream discharge. Our results challenge the commonly held conceptual model that glaciers buffer discharge variability. Instead, in a subhumid watershed on Volcán Chimborazo, Ecuador, glacier melt drives nearly all the variability in discharge (Pearson correlation coefficient of 0.89 in simulations), with glaciers contributing a broad range of 20 %–60 % or wider of discharge, mostly (86 %) through surface runoff on hourly timescales, but also through infiltration that increases annual groundwater contributions by nearly 20 %. We further found that rainfall may enhance glacier melt contributions to discharge at timescales that complement glacier melt production, possibly explaining why minimum discharge occurred at the study site during warm but dry El Niño conditions, which typically heighten melt in the Andes. Our findings caution against extrapolations from isolated measurements: stream discharge and glacier melt contributions in tropical glacierized systems can change substantially at hourly to interannual timescales, due to climatic variability and surface to subsurface flow processes.
Keywords: Baraer_Michel

A review of the current state of knowledge of proglacial hydrogeology in the Cordillera Blanca, Peru - Glas, Robin; Lautz, Laura; McKenzie, Jeffrey; Mark, Bryan; Baraer, Michel; Chavez, Daniel; Maharaj, Laura (WIREs Water, 2018)
The rapidly melting glaciers of Peru are posing new risks to regional dry season water supplies, and this is evident in the Cordillera Blanca, the mountain range with the world's largest concentration of tropical glaciers. Permanent ice loss is causing reductions to dry season streamflow, which is coupled with shifting demands and control over water access and entitlements in the region. A full evaluation of hydrologic inputs is required to inform future water management in the relative absence of glaciers. Over the last decade, new studies have shown groundwater to be a significant component of the regional water budget during the dry season, and it cannot be ignored when accounting for water quality and quantity downstream of the Cordillera Blanca's alpine catchments. Distinctive common features of the Cordillera Blanca's proglacial catchments are sediment‐filled valleys that were once under proglacial lake conditions. The combination of lake sediments with other alpine depositional features results in storage and interseasonal release of groundwater that comprises up to 80% of the valley's streamflow during the driest months of the year. We summarize the emerging understanding of hydrogeologic processes in proglacial headwater systems of the region's principal river, the Rio Santa, and make suggestions for future research that will more clearly characterize the spatial distribution of stored groundwater within the mountain range. As glaciers continue to recede, differences in aquifer thickness and groundwater residence time between alpine catchments in the region will increasingly control dry season water availability at the local and basin scale. This article is categorized under: Science of Water > Hydrological Processes Science of Water > Water and Environmental Change Engineering Water > Planning Water
Keywords: Baraer_Michel

Assessing microbial risk through event-based pathogen loading and hydrodynamic modelling - Tolouei, Samira; Dewey, Ray; Snodgrass, William J.; Edge, Thomas A.; Andrews, Robert C.; Taghipour, Milad; Prévost, Michèle; Dorner, Sarah (Science of The Total Environment, 2019)
Keywords: Dorner_Sarah

Conflicts between recovery objectives: The case of housing reconstruction after the 2003 earthquake in Bam, Iran - Fayazi, Mahmood; Lizarralde, Gonzalo (International Journal of Disaster Risk Reduction, 2018)
Keywords: Lizarralde_Gonzalo

Effect of Scour on the Natural Frequency Responses of Bridge Piers: Development of a Scour Depth Sensor - Boujia, Nissrine; Schmidt, Franziska; Chevalier, Christophe; Siegert, Dominique; Pham Van Bang, Damien (Infrastructures, 2019)
Local scour is the removal of soil around bridge foundations under the erosive action of flowing water. This hydraulic risk has raised awareness of the need for developing continuous monitoring techniques to estimate scour depth around bridge piers and abutments. One of the emerging techniques is based on monitoring the vibration frequency of either bridge piers or a driven sensor in the riverbed. The sensor proposed in this study falls into the second category. Some unresolved issues are investigated: the effect of the geometry and material of the sensor, the effect of the embedded length and the effect of soil type. To this end, extensive laboratory tests are performed using rods of different materials, with various geometries and lengths. These tests are conducted in both dry sand and a soft clayey soil. Since the sensor will be placed in the riverbed, it is crucial to evaluate the effect of immersed conditions on its response. A numerical 3D finite-element model was developed and compared against experimental data. This model was then used to compute the ‘wet’ frequencies of the sensor. Finally, based on both the experimental and numerical results, an equivalent cantilever model is proposed to correlate the variation of the frequency of the sensor to the scour depth.
Keywords: PhamVanBang_Damien

Adaptation to Climate Change: Risk Management - Simonovic, Slobodan P. (2017)
Adaptation to climate change is a challenge that is complex and involves increasing risk. Efforts to manage these risks involve many decision-makers, conflicting values, competing objectives and methodologies, multiple alternative options, uncertain outcomes, and debatable probabilities. Adaptation occurs at multiple levels in a complex decision environment and is generally evaluated as better–worse, not right–wrong, based on multiple criteria. Identifying the best adaptation response is difficult. Risk management techniques help to overcome these problems. Here, risk management is presented as a decision-making framework that assists in the selection of optimal strategies (according to various criteria) using a systems approach that has been well defined and generally accepted in public decision-making. In the context of adapting to climate change, the risk management process offers a framework for identifying, assessing, and prioritizing climate-related risks and developing appropriate adaptation responses. The theoretical discussion is illustrated with an example from Canada. It includes (a) the assessment of climate change-caused flood risk to the municipal infrastructure for the City of London, Ontario, Canada, and (b) analysis of adaptation options for management of the risk in one of the watersheds within the City of London – Dingman Creek.

Lower Respiratory Symptoms Associated With Environmental and Reconstruction Exposures After Hurricane Sandy - Gargano, Lisa M.; Locke, Sean; Jordan, Hannah T.; Brackbill, Robert M. (Disaster Medicine and Public Health Preparedness, 2018)
Abstract Objective In a population with prior exposure to the World Trade Center (WTC) disaster, this study sought to determine the relationship between Hurricane Sandy-related inhalation exposures and post-Sandy lower respiratory symptoms (LRS). Methods Participants included 3835 WTC Health Registry enrollees who completed Wave 3 (2011-2012) and Hurricane Sandy (2013) surveys. The Sandy-related inhalational exposures examined were: (1) reconstruction exposure; (2) mold or damp environment exposure; and (3) other respiratory irritants exposure. LRS were defined as wheezing, persistent cough, or shortness of breath reported on ≥1 of the 30 days preceding survey completion. Associations between LRS and Sandy exposures, controlling for socio-demographic factors, post-traumatic stress disorder, and previously reported LRS and asthma were examined using multiple logistic regression. Results Over one-third of participants (34.4%) reported post-Sandy LRS. Each of the individual exposures was also independently associated with post-Sandy LRS, each having approximately twice the odds of having post-Sandy LRS. We found a dose-response relationship between the number of types of Sandy-related exposures reported and post-Sandy LRS. Conclusions This study provides evidence that post-hurricane clean-up and reconstruction exposures can increase the risk for LRS. Public health interventions should emphasize the importance of safe remediation practices and recommend use of personal protective equipment. ( Disaster Med Public Health Preparedness . 2018;12:697-702)
Keywords: Ouvrage_Collectif_Numéro1

Le Québec récemment frappé par les crues extrêmes : une manifestation des changements climatiques ? - Leconte, Robert (Le Climatoscope, 2019)
Les printemps 2017 et 2019 auront frappé l’imaginaire collectif en raison de l’ampleur des crues ayant touché de nombreuses rivières du Québec et des dommages qui leur sont associés. En 2019, près de 6700 résidences localisées dans 51 municipalités et distribuées dans presque toutes les principales régions du Québec ont été inondées, sans compter les nombreuses autres résidences qui se sont retrouvées isolées en raison de routes submergées et de glissements de terrain. Le bilan en 2017 était similaire, avec 5371 maisons inondées dans 261 municipalités et 4066 personnes évacuées. Les débits dans plusieurs rivières ont excédé les valeurs mesurées depuis que les stations de jaugeage ont été installées. À titre d’exemple, en 2019, le débit journalier dans la rivière Rouge à la hauteur du Barrage de la Chute-Bell, où Hydro-Québec a craint pour la stabilité de l’ouvrage, a atteint 975 m3/s, la plus forte valeur jamais enregistrée depuis 1964. Une analyse statistique révèle qu’un tel débit a une chance d’être dépassé en moyenne une fois tous les 175 ans. Il s’agit d’un événement exceptionnel. Pourtant, un autre événement extrême se produisait au même endroit en 1998, cette fois-ci avec un débit maximal journalier de 914 m3/s. Deux crues printanières majeures en 20 ans : est-ce la conséquence des changements climatiques ? Cet article propose une genèse des événements hydrologiques extrêmes, puis présente des projections climatiques aux horizons 2050 et 2080 pour différentes rivières au Sud et au Nord du fleuve Saint-Laurent. Puis, est exposée la démarche générale employée pour caractériser le régime hydrologique des bassins versants en climat futur.
Keywords: Ouvrage_Collectif_Numéro1

Espace de liberté: un cadre de gestion intégrée pour la conservation des cours d’eau dans un contexte de changements climatiques - Biron, P.; Buffin-Bélanger, T.; Larocque, M.; Demers, S.; Olsen, T.; Ouellet, M.-A.; Choné, G.; Cloutier, C.-A.; Needelman, M. (OURANOS, 2013)
Les changements climatiques anticipés produiront des crues plus fréquentes et des étiages plus prononcés qui menaceront la sécurité publique et l’état des écosystèmes fluviaux. L’espace de liberté des cours d’eau est un cadre de gestion intégrée considérant l’hydrogéomorphologie des rivières. Il vise à identifier des espaces d’inondabilité et de mobilité du cours d’eau où on accepte de le laisser évoluer plutôt que de le contraindre dans un tracé façonné par les interventions anthropiques. Cette approche apparaît prometteuse pour une gestion durable dans un climat changeant, car elle maintient les fonctions physiques naturelles des cours d’eau (transport de l’eau et des sédiments), ce qui augmente leur résilience. L’espace de liberté reconnaît aussi le rôle majeur de la connectivité entre la rivière et la nappe phréatique, notamment par l'entremise des milieux humides qui contribuent à l’atténuation des crues et des étiages et à une amélioration de la qualité de l’eau. Les objectifs de ce projet consistent à 1) développer l’approche de gestion des cours d’eau basée sur les concepts d’espace de liberté pour les cours d’eau du Québec et examiner sa mise en œuvre pour renforcer la capacité de résilience des rivières dans un contexte de changements climatiques; 2) évaluer la connectivité entre la rivière et la nappe afin de mieux comprendre le rôle des milieux humides dans l'espace de liberté des cours d’eau et 3) effectuer une analyse avantages-coûts de l’implantation d’un espace de liberté. L’espace de liberté a été déterminé par l’approche hydrogéomorphologique et cartographié pour trois cours d’eau contrastés du Québec (rivières de la Roche et Yamaska Sud-Est en Montérégie et rivière Matane en Gaspésie). La démarche consiste 1) d’une analyse de photographies historiques anciennes, de modèles numériques d’altitude et d’observations sur le terrain; 2) de mesures simultanées des niveaux et des températures de la nappe phréatique et du cours d’eau et 3) de simulations numériques pour estimer l’impact des changements climatiques sur la mobilité et l’inondabilité des cours d’eau. La méthodologie développée pour définir l’espace de liberté est robuste et s’applique tant pour les cours d’eau agricoles (rivière de la Roche et Yamaska Sud-Est) que pour les rivières à saumon plus dynamiques comme la rivière Matane. L’espace de liberté inclut trois niveaux d’inondabilité (N1 : très fréquente et/ou avec forts courants, N2 : fréquente de faible courant, N3 : peu fréquente), deux niveaux de mobilité (M1 : à court terme (50 ans) et M2 : basée sur l’amplitude des méandres), ainsi que les milieux humides. Les analyses de sensibilité par simulation numérique révèlent que les limites de l’espace de liberté intègrent adéquatement la mobilité et l’inondabilité attendues dans un climat futur. Une cartographie simplifiée de l’espace de liberté, à deux niveaux, est également produite. L’espace de liberté minimal (L1) inclut les inondations très fréquentes (N1), les milieux humides riverains ainsi que la mobilité à court terme (M1). C’est une zone où il ne devrait pas y avoir d’aménagement. La zone L2 représente quant à elle l’espace fonctionnel de la rivière (N2 et M2) qui devrait être protégé afin que la dynamique naturelle de la rivière puisse opérer en climat actuel et futur. Les aménagements dans cette zone devraient tenir compte des risques d’érosion et d’inondation. Les résultats de l’analyse avantages-coûts suggèrent que l’aménagement d’espaces de liberté serait économiquement avantageux pour les trois cours d’eau. Malgré la perte du droit de construire et de cultiver dans l’espace de liberté, accompagnée par une compensation financière pour les agriculteurs, des gains nets variant entre 0,7 et 3,7 millions de dollars sont estimés sur une période de 50 ans. Ceci est dû aux réductions des coûts de protection des berges déjà stabilisées et qui le seraient à l’avenir, mais aussi aux services écologiques rendus par les milieux humides et les bandes riveraines. Une gestion par espace de liberté des cours d’eau du Québec exige un changement majeur dans nos perceptions et nos représentations des rivières qui, jusqu’à maintenant, ont été considérées comme des entités relativement statiques dans le paysage. Une telle approche apportera notamment comme avantage de faciliter l’adaptation aux risques liés à une plus grande variabilité des débits en climat futur par une gestion proactive qui améliore la santé des cours d’eau tout en étant avantageuse économiquement à moyen et à long terme. Elle contribuera également à diminuer les risques pour les infrastructures et la sécurité publique en utilisant une cartographie basée sur la dynamique des cours d’eau pour déterminer les zones où les aménagements devraient être interdits à l’avenir.
Keywords: Ouvrage_Collectif_Numéro1

Spatialisation des processus d’embâcles dans le bassin versant de la rivière l’Acadie, Montérégie : une approche hydrogéomorphologique - Plante Lévesque, Valérie; Boucher, Étienne; Proulx, Guillaume (Revue des sciences de l’eau, 2019)
La rivière L’Acadie, située en Montérégie (Québec, Canada), est un affluent de la rivière Richelieu et s’écoule vers le nord. Des inondations hivernales ayant de lourds impacts sur les milieux habités des municipalités de Chambly et de Carignan sont fréquentes sur cette rivière. Alors qu’au Québec on privilégie une approche hydrologique basée sur la récurrence des inondations en eau libre pour aménager les rives et la plaine inondable, l’approche hydrogéomorphologique permet de spatialiser les processus fluviaux qui posent un risque pour les communautés à partir d’une étude détaillée et systématique des formes du paysage fluvial. Cette approche permet d’acquérir une meilleure idée de l’impact de certains processus fluviaux tels que les embâcles de glace sur l’environnement humain et naturel. La présente recherche a pour objectif de spatialiser les propriétés et les impacts géomorphologiques du régime d’embâcles de glace au sein du bassin versant de la rivière L’Acadie. Des caractérisations des propriétés du bassin versant, du chenal, puis des berges de la rivière sont effectuées afin de localiser les problèmes d’embâcles de glace et décrire l’intensité de leur empreinte morphologique sur le milieu. De ces résultats découle une typologie des berges à laquelle est jumelée une analyse de la fréquence des évènements par l’étude des cicatrices glacielles sur la végétation riveraine. L’analyse démontre comment la morphométrie du chenal, la présence d’agriculture ainsi que l’héritage de la dernière glaciation quaternaire affectent le dynamisme du régime d’embâcles de glace qui se concentre en aval de la rivière. , L’Acadie River is a tributary of the Richelieu River that flows northwards through the southwestern region of Montérégie (Quebec, Canada). The river is well known for its frequent winter floods that severely affect the nearby towns of Chambly and Carignan. Even though legislation in Quebec has an approach based on the frequency of open water floods to control riverbanks and floodplain development, the study of river forms, known as hydrogeomorphology, provides a more comprehensive understanding of the impact of fluvial processes such as river ice jams. The main objective of this research is to gain knowledge on river ice dynamics based on their spatialization within L’Acadie River watershed. The characterization of the watershed, channel, and river bank properties and features is based on a hydrogeomorphological approach to spatialize river ice activity along the river. The study emphasizes that watershed properties, the ubiquity of agriculture, and the legacy of the Quaternary ice period in the area are all factors that contribute to ice scouring activity in the downstream section of the main channel.
Keywords: Ouvrage_Collectif_Numéro1

Challenges to enabling and implementing Natural Flood Management in Scotland - Waylen, K. A.; Holstead, K. L.; Colley, K.; Hopkins, J. (Journal of Flood Risk Management, 2018)
We explore factors that constrain implementation of Natural Flood Management ( NFM ), based on qualitative analysis of interviews with those influencing and enabling flood risk management in Scotland. NFM entails collaboration by multiple individuals and organisations to plan and deliver measures such as re‐meandering or buffer strips. Our interviewees identified many interacting issues. They particularly focused on difficulties in securing resources, and evidence gaps and uncertainties associated with NFM . Co‐ordination was not simple, often requiring new types of skill, expertise, and resources. NFM is thus outside the ‘comfort zone’ of many leading or engaged with flood risk management. These experiences echo and elaborate on other studies of attempts to encourage sustainable flood management. To tackle these challenges, practitioners should reflect how pre‐existing ideas and practices may shape and constrain new approaches to managing floods, while research is needed on specific strategies that can assist in enabling change.
Keywords: Ouvrage_Collectif_Numéro1

Disaster risk, climate change, and poverty: assessing the global exposure of poor people to floods and droughts - Winsemius, Hessel C.; Jongman, Brenden; Veldkamp, Ted I.E.; Hallegatte, Stephane; Bangalore, Mook; Ward, Philip J. (Environment and Development Economics, 2018)
Abstract People living in poverty are particularly vulnerable to shocks, including those caused by natural disasters such as floods and droughts. This paper analyses household survey data and hydrological riverine flood and drought data for 52 countries to find out whether poor people are disproportionally exposed to floods and droughts, and how this exposure may change in a future climate. We find that poor people are often disproportionally exposed to droughts and floods, particularly in urban areas. This pattern does not change significantly under future climate scenarios, although the absolute number of people potentially exposed to floods or droughts can increase or decrease significantly, depending on the scenario and region. In particular, many countries in Africa show a disproportionally high exposure of poor people to floods and droughts. For these hotspots, implementing risk-sensitive land-use and development policies that protect poor people should be a priority.

Floods in future climates: a review - Whitfield, P.H. (Journal of Flood Risk Management, 2012)
Abstract At the global scale, the warming of the atmosphere will increase the capacity of the atmosphere to hold and accelerate the redistribution of water in the atmosphere. This suggests that flood‐generating processes linked to the atmosphere are likely to increase. However, the I ntergovernmental P anel on C limate C hange projections of future floods involve extremely complex issues that defy simple generalisations. Warming will alter other aspects of the water cycle increasing evaporation, changing precipitation patterns and intensity, and also affecting the processes involved in surface storage of water, including snowpack generation, snowmelt, river ice break‐up, and glacial melt. Many of these are active in flood generation, and changes may cause floods to decrease as well as increase. However, these processes take place not at the global scale but at relatively local scale, making generalisations about flooding in future climates difficult and uncertain. At the global scale, the role of land use is generally unresolved, but at a watershed scale, land‐use effects can be as important as changes in the meteorological processes. This review shows that while meteorologically driven flooding is expected to increase in a changed climate, making a precise pronouncement regarding all floods is unwise, as many types of floods will respond differently to changing climate and that because floods are watershed scale events, these local effects will remain important.
Keywords: Ouvrage_Collectif_Numéro1

Flood Spatial Modeling in Northern Iran Using Remote Sensing and GIS: A Comparison between Evidential Belief Functions and Its Ensemble with a Multivariate Logistic Regression Model - Tien Bui, Duie; Khosravi, Khabat; Shahabi, Himan; Daggupati, Prasad; Adamowski, Jan F.; M.Melesse, Assefa; Thai Pham, Binh; Pourghasemi, Hamid Reza; Mahmoudi, Mehrnoosh; Bahrami, Sepideh; Pradhan, Biswajeet; Shirzadi, Ataollah; et al. (Remote Sensing, 2019)
Floods are some of the most dangerous and most frequent natural disasters occurring in the northern region of Iran. Flooding in this area frequently leads to major urban, financial, anthropogenic, and environmental impacts. Therefore, the development of flood susceptibility maps used to identify flood zones in the catchment is necessary for improved flood management and decision making. The main objective of this study was to evaluate the performance of an Evidential Belief Function (EBF) model, both as an individual model and in combination with Logistic Regression (LR) methods, in preparing flood susceptibility maps for the Haraz Catchment in the Mazandaran Province, Iran. The spatial database created consisted of a flood inventory, altitude, slope angle, plan curvature, Topographic Wetness Index (TWI), Stream Power Index (SPI), distance from river, rainfall, geology, land use, and Normalized Difference Vegetation Index (NDVI) for the region. After obtaining the required information from various sources, 151 of 211 recorded flooding points were used for model training and preparation of the flood susceptibility maps. For validation, the results of the models were compared to the 60 remaining flooding points. The Receiver Operating Characteristic (ROC) curve was drawn, and the Area Under the Curve (AUC) was calculated to obtain the accuracy of the flood susceptibility maps prepared through success rates (using training data) and prediction rates (using validation data). The AUC results indicated that the EBF, EBF from LR, EBF-LR (enter), and EBF-LR (stepwise) success rates were 94.61%, 67.94%, 86.45%, and 56.31%, respectively, and the prediction rates were 94.55%, 66.41%, 83.19%, and 52.98%, respectively. The results showed that the EBF model had the highest accuracy in predicting flood susceptibility within the catchment, in which 15% of the total areas were located in high and very high susceptibility classes, and 62% were located in low and very low susceptibility classes. These results can be used for the planning and management of areas vulnerable to floods in order to prevent flood-induced damage; the results may also be useful for natural disaster assessment.
Keywords: Site_internet_RIISQ

How Flood Experience and Risk Perception Influences Protective Actions and Behaviours among Canadian Homeowners - Thistlethwaite, Jason; Henstra, Daniel; Brown, Craig; Scott, Daniel (Environmental Management, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Investigation of the mechanisms leading to the 2017 Montreal flood - Teufel, Bernardo; Sushama, Laxmi; Huziy, O.; Diro, G. T.; Jeong, Dae Il; Winger, Katja; Garnaud, Camille; de Elia, R.; Zwiers, Francis W.; Matthews, H. D.; Nguyen, Van-Thanh-Van (Climate Dynamics, 2019)
Significant flood damage occurred near Montreal in May 2017, as flow from the upstream Ottawa River basin (ORB) reached its highest levels in over 50years. Analysis of observations and experiments performed with the fifth generation Canadian Regional Climate Model (CRCM5) show that much above average April precipitation over the ORB, a large fraction of which fell as rain on an existing snowpack, increased streamflow to near record-high levels. Subsequently, two heavy rainfall events affected the ORB in the first week of May, ultimately resulting in flooding. This heavy precipitation during April and May was linked to large-scale atmospheric features. Results from sensitivity experiments with CRCM5 suggest that the mass and distribution of the snowpack have a major influence on spring streamflow in the ORB. Furthermore, the importance of using an appropriate frozen soil parameterization when modelling spring streamflows in cold regions was confirmed. Event attribution using CRCM5 showed that events such as the heavy April 2017 precipitation accumulation over the ORB are between two and three times as likely to occur in the present-day climate as in the pre-industrial climate. This increase in the risk of heavy precipitation is linked to increased atmospheric moisture due to warmer temperatures in the present-day climate, a direct consequence of anthropogenic emissions, rather than changes in rain-generating mechanisms or circulation patterns. Warmer temperatures in the present-day climate also reduce early-spring snowpack in the ORB, offsetting the increase in rainfall and resulting in no discernible change to the likelihood of extreme surface runoff.
Keywords: Ouvrage_Collectif_Numéro1

Emotions, Trust, and Perceived Risk: Affective and Cognitive Routes to Flood Preparedness Behavior - Terpstra, Teun (Risk Analysis, 2011)
Despite the prognoses of the effects of global warming (e.g., rising sea levels, increasing river discharges), few international studies have addressed how flood preparedness should be stimulated among private citizens. This article aims to predict Dutch citizens’ flood preparedness intentions by testing a path model, including previous flood hazard experiences, trust in public flood protection, and flood risk perceptions (both affective and cognitive components). Data were collected through questionnaire surveys in two coastal communities ( n = 169, n = 244) and in one river area community ( n = 658). Causal relations were tested by means of structural equation modeling (SEM). Overall, the results indicate that both cognitive and affective mechanisms influence citizens’ preparedness intentions. First, a higher level of trust reduces citizens’ perceptions of flood likelihood, which in turn hampers their flood preparedness intentions (cognitive route). Second, trust also lessens the amount of dread evoked by flood risk, which in turn impedes flood preparedness intentions (affective route). Moreover, the affective route showed that levels of dread were especially influenced by citizens’ negative and positive emotions related to their previous flood hazard experiences. Negative emotions most often reflected fear and powerlessness, while positive emotions most frequently reflected feelings of solidarity. The results are consistent with the affect heuristic and the historical context of Dutch flood risk management. The great challenge for flood risk management is the accommodation of both cognitive and affective mechanisms in risk communications, especially when most people lack an emotional basis stemming from previous flood hazard events.
Keywords: Ouvrage_Collectif_Numéro1

Balancing upstream–downstream interests in flood risk management: experiences from a catchment‐based approach in Austria - Seher, W.; Löschner, L. (Journal of Flood Risk Management, 2018)
River floods usually do not stop at administrative borders. The respective location of municipalities along a river creates different options and dependencies, commonly referred to as upstream–downstream relations. This regional dimension of flood risk calls for catchment‐based approaches in flood risk management as advocated by the EU Flood Directive. In this article, we present and assess the case of an intermunicipal cooperation in Austria which aims to alleviate flood risk and coordinate planning activities based on a catchment approach. The authors apply an established model of water governance to characterise the governance features and to assess the governance qualities and governance capacities of the intermunicipal cooperation. Findings show that the selected case qualifies as a suitable governance instrument to address the main policy objectives. Existing functional ties, shared (flooding) experiences, and mutual trust mark key success factors, indicating that proximity – in its many different forms – is crucial to overcome power asymmetries and spatial misfits in catchment‐based flood risk management. However, intermunicipal cooperation is weak when it comes to ensuring binding land use regulations, showing the need for a complementary use of governance arrangements and formal instruments of regional land use planning in flood risk management.

The future orientation of Austria’s flood policies: from flood control to anticipatory flood risk management - Nordbeck, Ralf; Steurer, Reinhard; Löschner, Lukas (Journal of Environmental Planning and Management, 2019)

Beyond ‘just’ flood risk management: the potential for—and limits to—alleviating flood disadvantage - O’Hare, Paul; White, Iain (Regional Environmental Change, 2018)
The threat of flooding poses a considerable challenge for justice. Not only are more citizens becoming exposed to risk, but they are expected to play increasingly active roles in flood risk management. However, until recently, few efforts have charted broader understandings of disadvantage relating to flood risk exposure. Drawing upon social science scholarship that has long been sensitive to concerns related to justice, we deploy and develop the notion of flood disadvantage as a means to assess the challenges to more ‘just’ flood risk management. We contend that the concept of flood disadvantage offers a useful lens to appreciate the constraints of technical approaches to flood risk management, in particular, its limited ability to incorporate complex social elements such as how individuals have differing vulnerabilities and sensitivities to flooding and uneven abilities to engage with risk agendas. The notion highlights the compounding interactions between flooding and other social disadvantages across multiple public policy areas and scales. We argue a fuller acknowledgement of the socio-spatial-temporal dimensions of intersecting disadvantages can help sensitise technical risk analyses that tend to see people and communities as homogeneous entities in a given spatiality. In doing so we can better reveal why some individuals or communities are more vulnerable to disasters or are slower to recover than others. Finally, we outline the challenges in turning more ‘just’ flood risk management from an abstract notion into one that could inform future practice.

Flood Risk Management: Exploring the Impacts of the Community Rating System Program on Poverty and Income Inequality - Noonan, Douglas S.; Sadiq, Abdul‐Akeem A. (Risk Analysis, 2018)
Abstract Flooding remains a major problem for the United States, causing numerous deaths and damaging countless properties. To reduce the impact of flooding on communities, the U.S. government established the Community Rating System (CRS) in 1990 to reduce flood damages by incentivizing communities to engage in flood risk management initiatives that surpass those required by the National Flood Insurance Program. In return, communities enjoy discounted flood insurance premiums. Despite the fact that the CRS raises concerns about the potential for unevenly distributed impacts across different income groups, no study has examined the equity implications of the CRS. This study thus investigates the possibility of unintended consequences of the CRS by answering the question: What is the effect of the CRS on poverty and income inequality? Understanding the impacts of the CRS on poverty and income inequality is useful in fully assessing the unintended consequences of the CRS. The study estimates four fixed‐effects regression models using a panel data set of neighborhood‐level observations from 1970 to 2010. The results indicate that median incomes are lower in CRS communities, but rise in floodplains. Also, the CRS attracts poor residents, but relocates them away from floodplains. Additionally, the CRS attracts top earners, including in floodplains. Finally, the CRS encourages income inequality, but discourages income inequality in floodplains. A better understanding of these unintended consequences of the CRS on poverty and income inequality can help to improve the design and performance of the CRS and, ultimately, increase community resilience to flood disasters.

Flood risk and adaptation strategies under climate change and urban expansion: A probabilistic analysis using global data. - Muis, Sanne; Güneralp, Burak; Jongman, Brenden; Aerts, Jeroen C. J. H.; Ward, Philip B.; Ward, Philip J. (Science of The Total Environment, 2015)

Are We Adapting to Floods? Evidence from Global Flooding Fatalities - Miao, Qing (Risk Analysis, 2019)
Abstract There has been a growing interest in understanding whether and how people adapt to extreme weather events in a changing climate. This article presents one of the first empirical analyses of adaptation to flooding on a global scale. Using a sample of 97 countries between 1985 and 2010, we investigate the extent and pattern of flood adaptation by estimating the effects of a country's climatological risk, recent flood experiences, and socioeconomic characteristics on its flood‐related fatalities. Our results provide mixed evidence on adaptation: countries facing greater long‐term climatological flooding risks do not necessarily adapt better and suffer fewer fatalities; however, after controlling for the cross‐country heterogeneity, we find that more recent flooding shocks have a significant and negative effect on fatalities from subsequent floods. These findings may suggest the short‐term learning dynamics of adaptation and potential inefficacy of earlier flood control measures, particularly those that promote increased exposure in floodplains. Our findings provide important implications for climate adaptation policy making and climate modeling.

Probabilistic depth–damage curves for assessment of flood-induced building losses - McGrath, Heather; Abo El Ezz, Ahmad; Nastev, Miroslav (Natural Hazards, 2019)

A comparison of simplified conceptual models for rapid web-based flood inundation mapping - McGrath, Heather; Bourgon, Jean-François; Proulx-Bourque, Jean-Samuel; Nastev, Miroslav; Abo El Ezz, Ahmad (Natural Hazards, 2018)

What determines flood risk perception? A review of factors of flood risk perception and relations between its basic elements - Lechowska, Ewa (Natural Hazards, 2018)
While the methods of risk analysis are generally based on objective measurements, the subjective assessment of risk, such as risk perception, is currently considered a crucial aspect in the context of flood risk management. Risk perception is regarded as an assessment of the perceived probability of hazard and the perceived probability of the results (most often—negative consequences). The work attempts to answer the question: What determines flood risk perception? The knowledge of the factors influencing flood risk perception can solve the issue of the society’s underestimation of flood risk. This issue was considered both in terms of the impact of particular factors on flood risk perception and the interrelationship between three characteristics of flood risk perception: preparedness, worry and awareness. The results were developed based on critical analysis of the empirical research. The review shows that the way particular characteristics determine flood risk perception is not clear and many authors show the diverse conclusions from the similar research. Taking into account various research results, the following factors were distinguished: primary (which clearly influence risk perception), secondary (which influence it unclearly and require further research) and intervening (often describing the context). The organization of the results of the research on the flood risk assessment conducted herein aims to improve the understanding of the human perception of flood risk and, as a result, will lead to the decrease in flood risk by improving the communication of the issue and motivating the residents of the endangered areas to take actions that reduce the negative effects of floods.

Ice‐jam flood risk assessment and mapping - Lindenschmidt, Karl‐Erich; Das, Apurba; Rokaya, Prabin; Chu, Thuan (Hydrological Processes, 2016)
Abstract In northern regions, river ice‐ jam flooding can be more severe than open‐water flooding causing property and infrastructure damages, loss of human life and adverse impacts on aquatic ecosystems. Very little has been performed to assess the risk induced by ice‐related floods because most risk assessments are limited to open‐water floods. The specific objective of this study is to incorporate ice‐jam numerical modelling tools (e.g. RIVICE, Monte‐Carlo simulation) into flood hazard and risk assessment along the Peace River at the Town of Peace River (TPR) in Alberta, Canada. Adequate historical data for different ice‐jam and open‐water flooding events were available for this study site and were useful in developing ice‐affected stage‐frequency curves. These curves were then applied to calibrate a numerical hydraulic model, which simulated different ice jams and flood scenarios along the Peace River at the TPR. A Monte‐Carlo analysis was then carried out to acquire an ensemble of water level profiles to determine the 1 : 100‐year and 1 : 200‐year annual exceedance probability flood stages for the TPR. These flood stages were then used to map flood hazard and vulnerability of the TPR. Finally, the flood risk for a 200‐year return period was calculated to be an average of $32/m 2 /a ($/m 2 /a corresponds to a unit of annual expected damages or risk). Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: Ouvrage_Collectif_Numéro1

Flood-induced mortality across the globe: Spatiotemporal pattern and influencing factors. - Hu, Pan; Zhang, Qiang; Shi, Peijun; Chen, Bo; Fang, Jiayi (Science of The Total Environment, 2018)
Abstract Impacts of floods on human society have been drawing increasing human concerns in recent years. In this study, flood observations from EM-DAT (Emergency Events Database) and DFO (Dartmouth Flood Observatory) datasets were analyzed to investigate frequency and intensity of floods, and flood-induced mortality, flood-affected population as well during 1975–2016 across the globe. Results indicated that: (1) occurrence rate of floods, flood-induced mortality and flood-affected population were generally increasing globally. However, flood-induced mortality and flood-affected people per flood event were in slight decrease, indicating that flood-induced mortality and flood-affected people due to increased floods exceeded those by individual flood event; (2) annual variation of mortality per flood event is highly related to floods with higher intensity. Specifically, the flood frequency and flood-induced mortality are the largest in Asia, specifically in China, India, Indonesia and Philippine; while significantly increased flood-affected population and mean annual mortality was detected in China, USA and Australia; (3) tropical cyclones (TC) are closely related to flood-induced mortality in parts of the countries along the western coast of the oceans. The frequency of channel floods in these regions is the largest and large proportion of flood-induced deaths and the highest flood-induced mortality can be attributed to TC-induced flash floods; (4) Population density and GDP per unit area are in significantly positive correlation with the number of flood-related victims per unit area, number of deaths and economic losses with exception of low-income countries. However, the flood-affected population and flood-induced mortality increase with decrease of per capita GDP; while the per capita economic loss increases with the increase of per capita GDP, indicating that the higher the population density and GDP per unit for a region, the higher sensitivity of this area to flood hazards.

Flooding Related Consequences of Climate Change on Canadian Cities and Flow Regulation Infrastructure - Gaur, Ayushi; Gaur, Abhishek; Yamazaki, Dai; Simonovic, Slobodan P. (Water, 2019)
This study discusses the flooding related consequences of climate change on most populous Canadian cities and flow regulation infrastructure (FRI). The discussion is based on the aggregated results of historical and projected future flooding frequencies and flood timing as generated by Canada-wide hydrodynamic modelling in a previous study. Impact assessment on 100 most populous Canadian cities indicate that future flooding frequencies in some of the most populous cities such as Toronto and Montreal can be expected to increase from 100 (250) years to 15 (22) years by the end of the 21st century making these cities highest at risk to projected changes in flooding frequencies as a consequence of climate change. Overall 40–60% of the analyzed cities are found to be associated with future increases in flooding frequencies and associated increases in flood hazard and flood risk. The flooding related impacts of climate change on 1072 FRIs located across Canada are assessed both in terms of projected changes in future flooding frequencies and changes in flood timings. Results suggest that 40–50% of the FRIs especially those located in southern Ontario, western coastal regions, and northern regions of Canada can be expected to experience future increases in flooding frequencies. FRIs located in many of these regions are also projected to experience future changes in flood timing underlining that operating rules for those FRIs may need to be reassessed to make them resilient to changing climate.

Superstorm Sandy and the Demographics of Flood Risk in New York City - Faber, Jacob William (Human Ecology, 2015)

A real-time hourly water index for flood risk monitoring: Pilot studies in Brisbane, Australia, and Dobong Observatory, South Korea - Deo, Ravinesh C.; Byun, Hi-Ryong; Kim, Ga-Byn; Adamowski, Jan F. (Environmental Monitoring and Assessment, 2018)

Environmental injustice and flood risk: a conceptual model and case comparison of metropolitan Miami and Houston, USA - Collins, Timothy W.; Grineski, Sara E.; Chakraborty, Jayajit (Regional Environmental Change, 2018)

Probable maximum flood in a changing climate: An overview for Canadian basins - Clavet-Gaumont, Jacinthe; Huard, David; Frigon, Anne; Koenig, Kristina A.; Slota, Phillip; Rousseau, Alain N.; Klein, Iris Maria; Thiémonge, Nathalie; Houdré, Fanny; Perdikaris, John; Turcotte, Richard; Lafleur, Julie; et al. (Journal of Hydrology: Regional Studies, 2017)
Abstract Study Region: In Canada, dams which represent a high risk to human loss of life, along with important environmental and financial losses in case of failure, have to accommodate the Probable Maximum Flood (PMF). Five Canadian basins with different physiographic characteristics and geographic locations, and where the PMF is a relevant metric have been selected: Nelson, Mattagami, Kenogami, Saguenay and Manic-5. Study Focus: One of the main drivers of the PMF is the Probable Maximum Precipitation (PMP). Traditionally, the computation of the PMP relies on moisture maximization of high efficiency observed storms without consideration for climate change. The current study attempts to develop a novel approach based on traditional methods to take into account the non-stationarity of the climate using an ensemble of 14 regional climate model (RCM) simulations. PMPs, the 100-year snowpack and resulting PMF changes were computed between the 1971-2000 and 2041-2070 periods. New Hydrological Insights for the Region: The study reveals an overall increase in future spring PMP with the exception of the most northern basin Nelson. It showed a projected increase of the 100-year snowpack for the two northernmost basins, Nelson (8%) and Manic-5 (3%), and a decrease for the three more southern basins, Mattagami (-1%), Saguenay (-5%) and Kenogami (-9%). The future spring PMF is projected to increase with median values between -1.5% and 20%.
Keywords: Rousseau_Alain

Dynamics of groundwater floodwaves and groundwater flood events in an alluvial aquifer - Buffin-Bélanger, Thomas; Cloutier, Claude-André; Tremblay, Catherine; Chaillou, Gwénaëlle; Larocque, Marie (2016)
In gravelly floodplains, streamflood events induce groundwater floodwaves that propagate through the alluvial aquifer. Understanding groundwater floodwave dynamics can contribute to groundwater ﬂood risk management. This study documents groundwater floodwaves on a flood event basis to fully assess environmental factors that control their propagation velocity, their amplitude and their extension in the floodplain, and examines the expression of groundwater flooding in the Matane River floodplain (Quebec, Canada). An array of 15 piezometers equipped with automated level sensors and a river stage gauge monitoring at 15-minute intervals from September 2011 to September 2014 were installed within a 0.04-km2 area of the floodplain. Cross-correlation analyses were performed between piezometric and river-level time series for 54 flood events. The results reveal that groundwater floodwave propagation occurs at all flood magnitudes. The smaller floods produced a clear groundwater floodwave through the floodplain, while the largest floods affected local groundwater flow orientation by generating an inversion of the hydraulic gradient. Propagation velocities ranging from 8 to 13 m/h, which are two to three orders of magnitude higher than groundwater velocity, were documented while the induced pulse propagated across the floodplain to more than 230 m from the channel. Propagation velocity and amplitude attenuation of the groundwater floodwaves depend both on flood event characteristics and the aquifer characteristics. Groundwater flooding events are documented at discharge below bankfull (< 0.5 Qbf). This study highlights the role of flood event hydrographs and environmental variables on groundwater floodwave properties and the complex relationship between flood event discharge and groundwater flooding. The role that groundwater floodwaves play in flood mapping and the ability of analytical solutions to reproduce them are also discussed.

Global exposure to river and coastal flooding: Long term trends and changes - Brenden Jongman; Jongman, Brenden; Philip J. Ward; Ward, Philip B.; Philip J. Ward; Ward, Philip J.; Jeroen C. J. H. Aerts; Aerts, Jeroen C. J. H. (Global Environmental Change-human and Policy Dimensions, 2012)

Is Flood Risk Capitalised Into Property Values? - Beltrán, Allan; Maddison, David; Elliott, Robert J. R. (Ecological Economics, 2018)
Keywords: Ouvrage_Collectif_Numéro1

A data-driven analysis of flash flood hazard, fatalities, and damages over the CONUS during 1996–2017 - Ahmadalipour, Ali; Moradkhani, Hamid (Journal of Hydrology, 2019)
Keywords: Ouvrage_Collectif_Numéro1

System dynamics and hydrodynamic modelling approaches for spatial and temporal analysis of flood risk - Ahmad, Shohan S.; Simonovic, Slobodan P. (International Journal of River Basin Management, 2015)
ABSTRACTTwo modelling approaches are presented in this article for spatial and temporal analysis of water resources risk. Major sources of uncertainty in water resources management are spatial and temporal variability. Spatial variability occurs when values fluctuate with the location of an area and temporal variability occurs when values fluctuate with time. System dynamics (SD) simulation and hydrodynamic modelling are presented in this article as tools for modelling the dynamic characteristics of flood risk and its spatial variability. The first modelling framework presents SD simulation coupled with 3D fuzzy set theory. Whereas the second modelling framework presents hydrodynamic modelling coupled with 3D fuzzy set theory. The two integrated modelling frameworks are illustrated and compared using the Red River flood of 1997 (Manitoba, Canada) as a case study. For the 1997 Red River case study, SD simulation proved to be efficient modelling approach for capturing the feedback-based dynamic processes oc...

La portée et les limites des approches participatives pour la gestion intégrée des inondations - Massé, Simon; Buffin-Bélanger, Thomas; Biron, Pascale; Ruiz, Julie (Revue des sciences de l’eau, 2019)
La gestion intégrée des risques d’inondation (GIRI) fait appel à la coordination de tous les niveaux et secteurs du gouvernement et de la société civile. Afin de favoriser la responsabilisation et l’appropriation des plans de GIRI par les communautés, l’implication des acteurs non gouvernementaux et des citoyens est de plus en plus valorisée. D’abord, l’émergence des approches participatives est exacerbée par l’optimisme face à la possibilité d’améliorer substantiellement la qualité et la portée des décisions, de gérer les conflits, de faciliter l'implantation des mesures non structurelles et de renforcer les capacités sociales au sein des communautés. Toutefois, certains avancent que l'intégration des non-experts dans le processus décisionnel brime l'impartialité de la procédure technocratique et que leur manque d’intérêt et de compétences limite la portée des démarches participatives. Des lacunes dans la représentativité des parties prenantes affectées et concernées au sein des instances peuvent aussi biaiser les aboutissants de la participation. De plus, la réticence des autorités à partager le pouvoir décisionnel limite l’institutionnalisation des approches participatives, tandis que la rigidité de l’appareil gouvernemental freine les élans participatifs des collectivités. Considérant l’intérêt grandissant des chercheurs, des décideurs et de la société civile envers les approches participatives dans le contexte de la gestion des inondations, cet article propose une synthèse de la littérature pour démêler les principales retombées et les limites de la participation. , In order to promote community accountability for flood risks, the involvement of non-governmental actors and citizens is increasingly valued. The emergence of participatory approaches is consolidated by optimism about the possibility of improving the quality and scope of decisions, managing conflicts, facilitating the implementation of non-structural measures and strengthening social capacity within communities. However, some argue that the integration of non-experts undermines the impartiality of the decision-making process and that their lack of interest and expertise limits the scope of participatory approaches. Moreover, the authorities’ reluctance to share decision-making power limits the institutionalization of participatory approaches, whereas the rigidity of the governmental framework hampers participatory impulses within communities. Lack of stakeholder representativeness within the decision-making framework may also bias the outcome of participation. In addition, the reluctance of the authorities to share decision-making power limits the institutionalization of participatory approaches, while the rigidity of the government apparatus hinders the participatory momentum of communities. Considering the growing interest of researchers, policymakers and civil society in participatory approaches in the context of flood management, this article provides a synthesis of the literature to unravel the major benefits and limitations of participation.
Keywords: Ouvrage_Collectif_Numéro1

Être jeune et exposé à un désastre technologique : le vécu des jeunes de la communauté de Lac-Mégantic - Maltais, Danielle; Pouliot, Ève; Petit, G. (2018)
A la suite de la tragedie ferroviaire de Lac-Megantic de 2013, des enquetes populationnelles ont permis de dresser un portrait de la sante des adultes vivant sur le territoire de la MRC du Granit, sans toutefois repertorier le vecu specifique des jeunes. Le present document vise a combler cette lacune en offrant un bilan de la realite et des besoins des jeunes âges de 10 a 25 ans demeurant au sein de la communaute de Lac-Megantic. Il presente les resultats d'une etude mixte realisee a l'hiver 2017 aupres d'eleves de second cycle de quatre ecoles primaires (5e et 6e annees), de la polyvalente Montignac, ainsi que d'etudiants frequentant le Centre de formation professionnelle Le Granit, le centre d'etudes collegiales de Lac-Megantic et le Centre d'education des adultes de la Commission scolaire des Hauts-Cantons, secteur Lac-Megantic. Cet ouvrage s'adresse aux chercheurs, aux etudiants ainsi qu'aux professionnels des milieux scolaires et du reseau de la sante et des services sociaux qui s'interessent au vecu des jeunes a la suite d'une catastrophe. Plus precisement, il permet de mieux connaitre les caracteristiques personnelles, familiales, scolaires et sociales des jeunes de la commmunaute de Lac-Megantic, tout en leur donnant la parole sur leurs attentes, leurs desirs et leurs besoins.
Keywords: Ouvrage_Collectif_Numéro1

Risk assessment strategies for early detection and prediction of infectious disease outbreaks associated with climate change - Rees, Ee; Ng, V; Gachon, P; Mawudeku, A; McKenney, D; Pedlar, J; Yemshanov, D; Parmely, J; Knox, J (Canada Communicable Disease Report, 2019)
Keywords: Gachon_Philippe

Stratégie d’évaluation des risques servant à la détection précoce et à la prédiction des éclosions de maladies infectieuses associées aux changements climatiques - Rees, Ee; Ng, V; Gachon, P; Mawudeku, A; McKenney, D; Pedlar, J; Yemshanov, D; Parmely, J; Knox, J (Relevé des maladies transmissibles au Canada, 2019)
Keywords: Gachon_Philippe

Which downscaled rainfall data for climate change impact studies in urban areas? Review of current approaches and trends - Gooré Bi, Eustache; Gachon, Philippe; Vrac, Mathieu; Monette, Frédéric (Theoretical and Applied Climatology, 2017)
Changes in extreme precipitation should be one of the primary impacts of climate change (CC) in urban areas. To assess these impacts, rainfall data from climate models are commonly used. The main goal of this paper is to report on the state of knowledge and recent works on the study of CC impacts with a focus on urban areas, in order to produce an integrated review of various approaches to which future studies can then be compared or constructed. Model output statistics (MOS) methods are increasingly used in the literature to study the impacts of CC in urban settings. A review of previous works highlights the non-stationarity nature of future climate data, underscoring the need to revise urban drainage system design criteria. A comparison of these studies is made difficult, however, by the numerous sources of uncertainty arising from a plethora of assumptions, scenarios, and modeling options. All the methods used do, however, predict increased extreme precipitation in the future, suggesting potential risks of combined sewer overflow frequencies, flooding, and back-up in existing sewer systems in urban areas. Future studies must quantify more accurately the different sources of uncertainty by improving downscaling and correction methods. New research is necessary to improve the data validation process, an aspect that is seldom reported in the literature. Finally, the potential application of non-stationarity conditions into generalized extreme value (GEV) distribution should be assessed more closely, which will require close collaboration between engineers, hydrologists, statisticians, and climatologists, thus contributing to the ongoing reflection on this issue of social concern.
Keywords: Gachon_Philippe

Quantitative and qualitative assessment of the impact of climate change on a combined sewer overflow and its receiving water body - Gooré Bi, Eustache; Monette, Frédéric; Gachon, Philippe; Gaspéri, Johnny; Perrodin, Yves (Environmental Science and Pollution Research, 2015)
Projections from the Canadian Regional Climate Model (CRCM) for the southern part of the province of Québec, Canada, suggest an increase in extreme precipitation events for the 2050 horizon (2041–2070). The main goal of this study consisted in a quantitative and qualitative assessment of the impact of the 20 % increase in rainfall intensity that led, in the summer of 2013, to overflows in the “Rolland-Therrien” combined sewer system in the city of Longueuil, Canada. The PCSWMM 2013 model was used to assess the sensitivity of this overflow under current (2013) and future (2050) climate conditions. The simulated quantitative variables (peak flow, QCSO, and volume discharged, VD) served as the basis for deriving ecotoxicological risk indices and event fluxes (EFs) transported to the St. Lawrence (SL) River. Results highlighted 15 to 500 % increases in VD and 13 to 148 % increases in QCSO by 2050 (compared to 2013), based on eight rainfall events measured from May to October. These results show that (i) the relationships between precipitation and combined sewer overflow variables are not linear and (ii) the design criteria for current hydraulic infrastructure must be revised to account for the impact of climate change (CC) arising from changes in precipitation regimes. EFs discharged into the SL River will be 2.24 times larger in the future than they are now (2013) due to large VDs resulting from CC. This will, in turn, lead to excessive inputs of total suspended solids (TSSs) and tracers for numerous urban pollutants (organic matter and nutrients, metals) into the receiving water body. Ecotoxicological risk indices will increase by more than 100 % by 2050 compared to 2013. Given that substantial VDs are at play, and although CC scenarios have many sources of uncertainty, strategies to adapt this drainage network to the effects of CC will have to be developed.
Keywords: Gachon_Philippe

The impact of flood risk on the price of residential properties: the case of England - Bélanger, Philippe; Bourdeau-Brien, Michael (Housing Studies, 2018)
Keywords: Bourdeau-Brien_Michael; Ouvrage_Collectif_Numéro1

Interannual kinetics (2010–2013) of large wood in a river corridor exposed to a 50-year flood event and fluvial ice dynamics - Boivin, Maxime; Buffin-Bélanger, Thomas; Piégay, Hervé (Geomorphology, 2017)
Keywords: Boivin_Maxime

“Sickenin’ in the rain” – increased risk of gastrointestinal and respiratory infections after urban pluvial flooding in a population-based cross-sectional study in the Netherlands - Mulder, Annemieke Christine; Pijnacker, Roan; De Man, Heleen; Van De Kassteele, Jan; Van Pelt, Wilfrid; Mughini-Gras, Lapo; Franz, Eelco (BMC Infectious Diseases, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Room for Rivers: Risk Reduction by Enhancing the Flood Conveyance Capacity of The Netherlands’ Large Rivers - Klijn, Frans; Asselman, Nathalie; Wagenaar, Dennis (Geosciences, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Global assessment report on disaster risk reduction 2019 - United Nations Office for Disaster Risk Reduction (UNDRR) (United Nations Office for Disaster Risk Reduction (UNDRR), 2019)
The 2019 Global Assessment Report on Disaster Risk Reduction (GAR) is informed by the latest data – including Sendai Framework target reporting by countries using the Sendai Framework Monitor
Keywords: Ouvrage_Collectif_Numéro1

Municipal flood risk sharing in Canada: A policy instrument analysis - Thistlethwaite, Jason; Henstra, Daniel (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2017)

Dendrohydrology in Canada’s western interior and applications to water resource management - Sauchyn, David J.; Vanstone, Jessica; St. Jacques, Jeannine-Marie; Sauchyn, Robert (Journal of Hydrology, 2015)
Summary Across the southern Canadian Prairies, annual precipitation is relatively low (200–400mm) and periodic water deficits limit economic and environmental productivity. Rapid population growth, economic development and climate change have exposed this region to increasing vulnerability to hydrologic drought. There is high demand for surface water, streamflow from the Rocky Mountains in particular. This paper describes the application of dendrohydrology to water resource management in this region. Four projects were initiated by the sponsoring organizations: a private utility, an urban municipality and two federal government agencies. The fact that government and industry would initiate and fund tree-ring research indicates that practitioners recognize paleohydrology as a legitimate source of technical support for water resource planning and management. The major advantage of tree-rings as a proxy of annual and seasonal streamflow is that the reconstructions exceed the length of gauge records by at least several centuries. The extent of our network of 180 tree-ring chronologies, spanning AD 549–2013 and ∼20° of latitude, with a high density of sites in the headwaters of the major river basins, enables us to construct large ensembles of tree-ring reconstructions as a means of expressing uncertainty in the inference of streamflow from tree rings. We characterize paleo-droughts in terms of modern analogues, translating the tree-ring reconstructions from a paleo-time scale to the time frame in which engineers and planners operate. Water resource managers and policy analysts have used our paleo-drought scenarios in their various forms to inform and assist drought preparedness planning, a re-evaluation of surface water apportionment policy and an assessment of the reliability of urban water supply systems.

Potential impact of climate change on the risk of windthrow in eastern Canada’s forests - Saad, Christian; Boulanger, Yan; Beaudet, Marilou; Gachon, Philippe; Ruel, Jean-Claude; Gauthier, Sylvie (Climatic Change, 2017)
Climate change is likely to affect windthrow risks at northern latitudes by potentially changing high wind probabilities and soil frost duration. Here, we evaluated the effect of climate change on windthrow risk in eastern Canada’s balsam fir (Abies balsamea [L.] Mill.) forests using a methodology that accounted for changes in both wind speed and soil frost duration. We used wind speed and soil temperature projections at the regional scale from the CRCM5 regional climate model (RCM) driven by the CanESM2 global climate model (GCM) under two representative concentration pathways (RCP4.5, RCP8.5), for a baseline (1976–2005) and two future periods (2041–2070, 2071–2100). A hybrid mechanistic model (ForestGALES) that considers species resistance to uprooting and wind speed distribution was used to calculate windthrow risk. An increased risk of windthrow (3 to 30%) was predicted for the future mainly due to an increased duration of unfrozen soil conditions (by up to 2 to 3 months by the end of the twenty-first century under RCP8.5). In contrast, wind speed did not vary markedly with a changing climate. Strong regional variations in wind speeds translated into regional differences in windthrow risk, with the easternmost region (Atlantic provinces) having the strongest winds and the highest windthrow risk. Because of the inherent uncertainties associated with climate change projections, especially regarding wind climate, further research is required to assess windthrow risk from the optimum combination of RCM/GCM ensemble simulations.
Keywords: Gachon_Philippe

A nested multivariate copula approach to hydrometeorological simulations of spring floods: the case of the Richelieu River (Québec, Canada) record flood - Saad, Christian; El Adlouni, Salaheddine; St-Hilaire, André; Gachon, Philippe (Stochastic Environmental Research and Risk Assessment, 2015)
Floods have potentially devastating consequences on populations, industries and environmental systems. They often result from a combination of effects from meteorological, physiographic and anthropogenic natures. The analysis of flood hazards under a multivariate perspective is primordial to evaluate several of the combined factors. This study analyzes spring flood-causing mechanisms in terms of the occurrence, frequency, duration and intensity of precipitation as well as temperature events and their combinations previous to and during floods using frequency analysis as well as a proposed multivariate copula approach along with hydrometeorological indices. This research was initiated over the Richelieu River watershed (Quebec, Canada), with a particular emphasis on the 2011 spring flood, constituting one of the most damaging events over the last century for this region. Although some work has already been conducted to determine certain causes of this record flood, the use of multivariate statistical analysis of hydrologic and meteorological events has not yet been explored. This study proposes a multivariate flood risk model based on fully nested Archimedean Frank and Clayton copulas in a hydrometeorological context. Several combinations of the 2011 Richelieu River flood-causing meteorological factors are determined by estimating joint and conditional return periods with the application of the proposed model in a trivariate case. The effects of the frequency of daily frost/thaw episodes in winter, the cumulative total precipitation fallen between the months of November and March and the 90th percentile of rainfall in spring on peak flow and flood duration are quantified, as these combined factors represent relevant drivers of this 2011 Richelieu River record flood. Multiple plausible and physically founded flood-causing scenarios are also analyzed to quantify various risks of inundation.
Keywords: Gachon_Philippe

The spatial variability of ice-jam bank morphologies along the Mistassini River (Quebec, Canada): an indicator of the ice-jam regime? - Morin, Stephanie; Boucher, Etienne; Buffin-Belanger, Thomas (Natural Hazards, 2015)
Keywords: Ouvrage_Collectif_Numéro1

The Influence of the Pacific Decadal Oscillation on Annual Floods in the Rivers of Western Canada - Gurrapu, Sunil; St-Jacques, Jeannine-Marie; Sauchyn, David J.; Hodder, Kyle R. (Journal of The American Water Resources Association, 2016)
We analyzed annual peak flow series from 127 naturally flowing or naturalized streamflow gauges across western Canada to examine the impact of the Pacific Decadal Oscillation (PDO) on annual flood risk, which has been previously unexamined in detail. Using Spearman's rank correlation ρ and permutation tests on quantile-quantile plots, we show that higher magnitude floods are more likely during the negative phase of the PDO than during the positive phase (shown at 38% of the stations by Spearman's rank correlations and at 51% of the stations according to the permutation tests). Flood frequency analysis (FFA) stratified according to PDO phase suggests that higher magnitude floods may also occur more frequently during the negative PDO phase than during the positive phase. Our results hold throughout much of this region, with the upper Fraser River Basin, the Columbia River Basin, and the North Saskatchewan River Basin particularly subject to this effect. Our results add to other researchers' work questioning the wholesale validity of the key assumption in FFA that the annual peak flow series at a site is independently and identically distributed. Hence, knowledge of large-scale climate state should be considered prior to the design and construction of infrastructure.

Supporting and Accompanying Young People After the Lac-Mégantic Train Derailment (Quebec, Canada) - Généreux, Mélissa; Maillet, Marie-Claude; Nault-Horvath, Elise; Stewart, Cindy (Prehospital and Disaster Medicine, 2019)
Introduction:In July 2013, a train transporting oil derailed and exploded in Lac-Mégantic, causing major human, environmental, and economic impacts. A community-based survey of people aged 10-25, conducted in 2017, revealed that many young people suffer in silence and report feeling isolated. These observations led to the conclusion that we must make room for young people, and that opportunities for engagement and participation must be provided within the community.Aim:The Public Health Direction of Estrie aimed to identify strategies to promote health and wellbeing for young people living in and around Lac-Mégantic.Methods:A collective reflection half-day was hosted with sixty key stakeholders (school board, other education institutions, health and social services, community sector, municipal/political sector, parents, youth). Throughout the event, participants were invited to build on and learn from accomplishments and experiential knowledge, and develop a common vision of the solutions to be pursued or implemented. All qualitative data sources (verbal and written data from large- and sub-group activities) were analyzed through a content analysis.Results:Several themes (i.e. potential solutions) emerged from the analysis: common venue, diversified activities, communication, collaboration, involvement, support for at-risk youth, intergenerational component, etc. Participants agreed on four priorities for action: 1) creating a gathering place, 2) establishing a Youth Committee, 3) supporting adults working with youth, and 4) fostering a better flow of information.Discussion:Several positive outcomes of the collective reflection half-day were observed, including the mobilization of the participants who greatly appreciated the event, and many promising ideas launched by stakeholders. A social worker is now fully dedicated to supporting youth wellbeing and engagement in Lac-Mégantic. A Youth Committee has been established and projects by and for youth are being implemented. Bottom-up approaches to identify solutions to complex situations are not only effective but also respectful of the local culture.
Keywords: Généreux_Mélissa

Modelling of future flood risk across Canada due to climate change - Gaur, Ayushi; Gaur, Abhishek; Simonovic, Slobodan P. (RISK ANALYSIS 2018, 2018)

Projected changes in the dynamics of flood hazard in the Grand River Basin, Canada. - Gaur, Abhishek; Simonovic, Slobodan P. (British Journal of Environment and Climate Change, 2015)
In this study future flooding frequencies have been estimated for the Grand River catchment located in south - western Ontario, Canada. Historical and future climatic projections made by fifteen Coupled Model Inter - comparison Project - 3 climate models are bias - corrected and downscaled before they are used to obtain mid - and end of 21 st century streamflow projections. By comparing the future projected and historically observed precipitation and temperature record s it is found that the mean and extreme temperature events will intensify in future across the catchment. The increase is more drastic in the case of extreme events than the mean events. The sign of change in future precipitation is uncertain. Further flow extremes are expected to increase in magnitude and frequency in future across the catchment. The confidence in the projection is more for low return period (<10 years) extreme events than higher return period (10 - 100 years) events. It can be expected that increases in temperature will play a dominant role in increasing the magnitude of low return period flooding events while precipitation seems to play an important role in shaping the high return period events.

Guide to identifying alert thresholds for heat waves in Canada based on evidence - Gachon, P.; Bussières, Louise; Gosselin, P.; Raphoz, M.; Bustinza, R.; Martin, Philippe H.; Dueymes, G.; Gosselin, Denis; Labrecque, Sylvain; Jeffers, S.; Yagouti, Abderrahmane (2016)
Among natural-disaster risks, heat waves are responsible for a large number of deaths, diseases and economic losses around the world. As they will increase in severity, duration and frequency over the decades to come within the context of climate change, these extreme events constitute a genuine danger to human health, and heat-warning systems are strongly recommended by public health authorities to reduce this risk of diseases and of excessive mortality and morbidity. Thus, evidence-based public alerting criteria are needed to reduce impacts on human health before and during persistent hot weather conditions. The goal of this guide is to identify alert thresholds for heat waves in Canada based on evidence, and to propose an approach for better defining heat waves in the Canadian context in order to reduce the risks to human health and contribute to the well-being of Canadians. This guide is the result of the collaboration among various research and public institutions working on: 1) meteorological and climate aspects, i.e. the Meteorological Service of Canada (MSC, Environment and Climate Change Canada), and the ESCER centre at the Universite du Quebec a Montreal, and 2) public health, i.e. Health Canada and the Institut National de Sante Publique du Quebec.
Keywords: Gachon_Philippe

Topography- and nightlight-based national flood risk assessment in Canada - Elshorbagy, Amin; Bharath, R.; Lakhanpal, Anchit; Ceola, Serena; Montanari, Alberto; Lindenschmidt, Karl-Erich (Hydrology and Earth System Sciences, 2016)
In Canada, flood analysis and water resource management, in general, are tasks conducted at the provincial level; therefore, unified national-scale approaches to water-related problems are uncommon. In this study, a national-scale flood risk assessment approach is proposed and developed. The study focuses on using global and national datasets available with various resolutions to create flood risk maps. First, a flood hazard map of Canada is developed using topography-based parameters derived from digital elevation models, namely, elevation above nearest drainage (EAND) and distance from nearest drainage (DFND). This flood hazard mapping method is tested on a smaller area around the city of Calgary, Alberta, against a flood inundation map produced by the city using hydraulic modelling. Second, a flood exposure map of Canada is developed using a land-use map and the satellite-based nightlight luminosity data as two exposure parameters. Third, an economic flood risk map is produced, and subsequently overlaid with population density information to produce a socioeconomic flood risk map for Canada. All three maps of hazard, exposure, and risk are classified into five classes, ranging from very low to severe. A simple way to include flood protection measures in hazard estimation is also demonstrated using the example of the city of Winnipeg, Manitoba. This could be done for the entire country if information on flood protection across Canada were available. The evaluation of the flood hazard map shows that the topography-based method adopted in this study is both practical and reliable for large-scale analysis. Sensitivity analysis regarding the resolution of the digital elevation model is needed to identify the resolution that is fine enough for reliable hazard mapping, but coarse enough for computational tractability. The nightlight data are found to be useful for exposure and risk mapping in Canada; however, uncertainty analysis should be conducted to investigate the effect of the overglow phenomenon on flood risk mapping.

Mental Disorder Symptoms among Public Safety Personnel in Canada - Carleton, R. Nicholas; Afifi, Tracie O.; Turner, Sarah; Taillieu, Tamara; Duranceau, Sophie; LeBouthillier, Daniel M.; Sareen, Jitender; Ricciardelli, Rose; MacPhee, Renee S.; Groll, Dianne; Hozempa, Kadie; Brunet, Alain; et al. (The Canadian Journal of Psychiatry, 2018)
Background: Canadian public safety personnel (PSP; e.g., correctional workers, dispatchers, firefighters, paramedics, police officers) are exposed to potentially traumatic events as a function of their work. Such exposures contribute to the risk of developing clinically significant symptoms related to mental disorders. The current study was designed to provide estimates of mental disorder symptom frequencies and severities for Canadian PSP. Methods: An online survey was made available in English or French from September 2016 to January 2017. The survey assessed current symptoms, and participation was solicited from national PSP agencies and advocacy groups. Estimates were derived using well-validated screening measures. Results: There were 5813 participants (32.5% women) who were grouped into 6 categories (i.e., call center operators/dispatchers, correctional workers, firefighters, municipal/provincial police, paramedics, Royal Canadian Mounted Police). Substantial proportions of participants reported current symptoms consistent with 1 (i.e., 15.1%) or more (i.e., 26.7%) mental disorders based on the screening measures. There were significant differences across PSP categories with respect to proportions screening positive based on each measure. Interpretation: The estimated proportion of PSP reporting current symptom clusters consistent with 1 or more mental disorders appears higher than previously published estimates for the general population; however, direct comparisons are impossible because of methodological differences. The available data suggest that Canadian PSP experience substantial and heterogeneous difficulties with mental health and underscore the need for a rigorous epidemiologic study and category-specific solutions.
Keywords: Brunet_Alain

La réduction des risques de désastres : défis et possibilités pour le Québec et le Canada. Université du Québec à Montréal, Chaire de recherche UQAM sur les risques hydrométéorologiques liés aux changements climatiques - Boyer-Villemaire, U.; Gachon, P.; Boucher, E.; Germain, D.; Raphoz, M.; Doré, M. C.; Martin, J. P. (2017)
En marge de la Cinquième Plateforme régionale pour la Réduction des risques de catastrophes des Amériques (PRA), le gouvernement du Canada a approché l’Institut des sciences de l’environnement(ISE) de l’Université du Québec à Montréal(UQAM) afin d’organiser un forum public. Les échanges de ce dernier devaient servir à alimenter les discussions de la PRA. Au total, 21 experts ont discuté avec une centaine de participants lors de panels organisés à l’UQAM sous les thèmes de la santé, de la sécurité civile et de l’aménagement du territoire. Plusieurs thèmes transversaux ont aussi émergé tout au long du forum. Il importe de pérenniser le rôle de la recherche et d’améliorer les capacités de formation technique et universitaire afin de former des spécialistes en mesure d’appréhender la complexité de la gestion du risque dans un contexte de changements environnementaux et climatiques. Ceci est également essentiel pour l’identification des facteurs de risque (multisources ou multidimensionnels), pour tirer des leçons apprises des événements majeurs passés et récents, et pour développer ou mettre à jour la connaissance sur les tendances en cours et à venir des aléas météorologiques, ainsi que des facteurs de vulnérabilité et d’exposition. Tous les panels ont discuté de l’importance de favoriser le décloisonnement intra/interorganisationnel pour promouvoir la transsectorialité et les retours d’expériences systématiques. Pour ce faire, il faut s’inspirer des modèles internationaux, notamment du système d’alertes hydrométéorologiques présenté par Météo-France. Celui-ci inclut une vigilance météorologique qui cible des populations et des autorités publiques, et les informe des comportements et des règles à suivre lors d’alertes plus problématiques (vigilance aux stades orange et rouge). Finalement, l’amélioration de la communication et le libre accès à l’information sont des éléments essentiels pour protéger les individus et développer une société plus résiliente.
Keywords: Gachon_Philippe

Climate Change Impacts on Catchment Hydrology in Eastern Canada - Aygün, O.; Kinnard, C.; Campeau, S. (2019)
Snowmelt dominated regions are receiving increasing attention due to their noticeably rapid response to ongoing climate change, which raises concerns about the altered hydrological risks under climate change scenarios. This study aims to assess the climate change impacts on hydrology over two contrasted catchments in southern Québec: Acadie River and Montmorency River catchments. These river catchments represent two predominant landscapes of the St. Lawrence River watershed; an intensive farming landscape in the south shore lowlands and the forested landscape on the Canadian Shield on the north shore, respectively. In this study, a physically based hydrological model has been developed using the Cold Regions Hydrological Model (CRHM) for both of the catchments. The hydrological model outputs showed that we were able to simulate snow surveys and discharge measurements with a reasonable accuracy for both catchments. The acceptable performance of the model along with the strong physical basis of structure suggested that this model could be used for climate change sensitivity simulations. Based on the climate scenarios reviewed, a temperature increase up to 8°C and an increase in total precipitation up to 20% were analysed for both of the catchments. Both catchments were found to be sensitive to climate change, however the degree of sensitivity was found to be catchment specific. Snow processes in the Acadie River catchment were simulated to be more sensitive to warming than in the Montmorency River catchment. In case of 2°C warming, reduction in peak SWE was not be able to be compensated even by increased precipitation scenario. Given that, the Acadie River has already a mixed flow regime, even if 2°C warming is combined with an increase in precipitation, pluvial regime kept becoming more dominant, resulting in higher peaks of rain events. On the other hand, even 3°C of warming did not modify the flow regime of the Montmorency River. While there is shift towards earlier peak spring flows in both catchments, the shift was found to be more pronounced in the Acadie River. An earlier occurrence of snowmelt floods and an overall increase in winter streamflow during winter have been simulated for both catchments, which calls for renewed assessments of existing water supply and flood risk management strategies.
Keywords: Kinnard_Christophe

Adaptation as an indicator of measuring low-impact-development effectiveness in urban flooding risk mitigation - Song, Jing; Yang, Rui; Chang, Zheng; Li, Weifeng; Wu, Jiansheng (Science of The Total Environment, 2019)

Observed and Projected Impacts from Extreme Weather Events: Implications for Loss and Damage - Bouwer, Laurens M. (2019)
This chapter presents current knowledge of observed and projected impacts from extreme weather events, based on recorded events and their losses, as well as studies that project future impacts from anthropogenic climate change. The attribution of past changes in such impacts focuses on the three key drivers: changes in extreme weather hazards that can be due to natural climate variability and anthropogenic climate change, changes in exposure and vulnerability, and risk reduction efforts. The chapter builds on previous assessments of attribution of extreme weather events, to drivers of changes in weather hazard, exposure and vulnerability. Most records of losses from extreme weather consist of information on monetary losses, while several other types of impacts are underrepresented, complicating the assessment of losses and damages. Studies into drivers of losses from extreme weather show that increasing exposure is the most important driver through increasing population and capital assets. Residual losses (after risk reduction and adaptation) from extreme weather have not yet been attributed to anthropogenic climate change. For the Loss and Damage debate, this implies that overall it will remain difficult to attribute this type of losses to greenhouse gas emissions. For the future, anthropogenic climate change is projected to become more important for driving future weather losses upward. However, drivers of exposure and especially changes in vulnerability will interplay. Exposure will continue to lead to risk increases. Vulnerability on the other hand may be further reduced through disaster risk reduction and adaptation. This would reduce additional losses and damages from extreme weather. Yet, at the country scale and particularly in developing countries, there is ample evidence of increasing risk, which calls for significant improvement in climate risk management efforts.

Extreme weather events in northeastern New Brunswick (Canada) for the period 1950–2012: Comparison of newspaper archive and weather station data - Mallet, Julie; Fortin, Guillaume; Germain, Daniel (Canadian Geographer, 2018)
In the context of global warming, changes in extreme weather and climate events are expected, particularly those associated with changes in temperature and precipitation regimes and those that will affect coastal areas. The main objectives of this study were to establish the number of extreme events that have occurred in northeastern New Brunswick, Canada in recent history, and to determine whether their occurrence has increased. By using archived regional newspapers and data from three meteorological stations in a national network, the frequency of extreme events in the study area was established for the time period 1950–2012. Of the 282 extreme weather events recorded in the newspaper archives, 70% were also identified in the meteorological time series analysis. The discrepancy might be explained by the synergistic effect of co-occurring non-extreme events, and increased vulnerability over time, resulting from more people and infrastructure being located in coastal hazard zones. The Mann Kendall and Pettitt statistical tests were used to identify trends and the presence of break points in the weather data time series. Results indicate a statistically significant increase in average temperatures and in the number of extreme events, such as extreme hot days, as well as an increase in total annual and extreme precipitation. A significant decrease in the number of frost-free days and extreme cold days was also found, in addition to a decline in the number of dry days.

Communicating Flood Risk to Canadians: Understanding the Challenges and Developing Best Practices - Partners for Action (2019)

Using Flood Maps for Community Flood Risk Communication - Minano, Andrea; Peddle, Shawna (Rapport préparé pour Ressources naturelles Canada, Partners for Action, 2018)
Keywords: Site_internet_RIISQ

Raising risk preparedness by flood risk communication - Maidl, E.; Buchecker, M. (Natural Hazards and Earth System Sciences, 2015)
Abstract. During the last decade, most European countries have produced hazard maps of natural hazards, but little is known about how to communicate these maps most efficiently to the public. In October 2011, Zurich's local authorities informed owners of buildings located in the urban flood hazard zone about potential flood damage, the probability of flood events and protection measures. The campaign was based on the assumptions that informing citizens increases their risk awareness and that citizens who are aware of risks are more likely to undertake actions to protect themselves and their property. This study is intended as a contribution to better understand the factors that influence flood risk preparedness, with a special focus on the effects of such a one-way risk communication strategy. We conducted a standardized mail survey of 1500 property owners in the hazard zones in Zurich (response rate main survey: 34 %). The questionnaire included items to measure respondents' risk awareness, risk preparedness, flood experience, information-seeking behaviour, knowledge about flood risk, evaluation of the information material, risk acceptance, attachment to the property and trust in local authorities. Data about the type of property and socio-demographic variables were also collected. Multivariate data analysis revealed that the average level of risk awareness and preparedness was low, but the results confirmed that the campaign had a statistically significant effect on the level of preparedness. The main influencing factors on the intention to prepare for a flood were the extent to which respondents evaluated the information material positively as well as their risk awareness. Respondents who had never taken any previous interest in floods were less likely to read the material. For future campaigns, we therefore recommend repeated communication that is tailored to the information needs of the target population.
Keywords: Ouvrage_Collectif_Numéro1

Communicating disaster risk? An evaluation of the availability and quality of flood maps - Henstra, Daniel; Minano, Andrea; Thistlethwaite, Jason (Natural Hazards and Earth System Sciences, 2019)
Abstract. One of the key priorities for disaster risk reduction is to ensure decision makers, stakeholders, and the public understand their exposure to disaster risk, so that they can take protective action. Flood maps are a potentially valuable tool for facilitating this understanding of flood risk, but previous research has found that they vary considerably in availability and quality. Using an evaluation framework comprising nine criteria grounded in existing scholarship, this study assessed the quality of flood maps available to the public in Canadian communities located in designated flood risk areas. It found that flood maps in most municipalities (62 %) are low quality (meeting less than 50 % of the criteria) and the highest score was 78 % (seven of nine criteria met). The findings suggest that a more concerted effort to produce high-quality, publicly accessible flood maps is required to support Canada's international commitment to disaster risk reduction. Further questions surround possible weighting of quality assessment criteria, whether and how individuals seek out flood maps, and how flood risk information could be better communicated using modern technology.
Keywords: Ouvrage_Collectif_Numéro1

Logistic models as a forecasting tool for snow avalanches in a cold maritime climate: northern Gaspésie, Québec, Canada - Gauthier, F.; Germain, Daniel; Hétu, Bernard (Natural Hazards, 2017)
Snow avalanches are a major natural hazard for road users and infrastructure in northern Gaspesie. Over the past 11 years, the occurrence of nearly 500 snow avalanches on the two major roads servicing the area was reported. No management program is currently operational. In this study, we analyze the weather patterns promoting snow avalanche initiation and use logistic regression (LR) to calculate the probability of avalanche occurrence on a daily basis. We then test the best LR models over the 2012–2013 season in an operational forecasting perspective: Each day, the probability of occurrence (0–100%) determined by the model was classified into five classes avalanche danger scale. Our results show that avalanche occurrence along the coast is best predicted by 2 days of accrued snowfall [in water equivalent (WE)], daily rainfall, and wind speed. In the valley, the most significant predictive variables are 3 days of accrued snowfall (WE), daily rainfall, and the preceding 2 days of thermal amplitude. The large scree slopes located along the coast and exposed to strong winds tend to be more reactive to direct snow accumulation than the inner-valley slopes. Therefore, the probability of avalanche occurrence increases rapidly during a snowfall. The slopes located in the valley are less responsive to snow loading. The LR models developed prove to be an efficient tool to forecast days with high levels of snow avalanche activity. Finally, we discuss how road maintenance managers can use this forecasting tool to improve decision making and risk rendering on a daily basis.

Buyer Beware: Evaluating Property Disclosure as a Tool to Support Flood Risk Management - Henstra, Daniel; Jason, Thistlethwaite (2017)

Exploring local risk managers' use of flood hazard maps for risk communication purposes in Baden-Württemberg - Kjellgren, S. (Natural Hazards and Earth System Sciences, 2013)
Abstract. In response to the EU Floods Directive (2007/60/EC), flood hazard maps are currently produced all over Europe, reflecting a wider shift in focus from "flood protection" to "risk management", for which not only public authorities but also populations at risk are seen as responsible. By providing a visual image of the foreseen consequences of flooding, flood hazard maps can enhance people's knowledge about flood risk, making them more capable of an adequate response. Current literature, however, questions the maps' awareness raising capacity, arguing that their content and design are rarely adjusted to laypeople's needs. This paper wants to complement this perspective with a focus on risk communication by studying how these tools are disseminated and marketed to the public in the first place. Judging from communication theory, simply making hazard maps publicly available is unlikely to lead to attitudinal or behavioral effects, since this typically requires two-way communication and material or symbolic incentives. Consequently, it is relevant to investigate whether and how local risk managers, who are well positioned to interact with the local population, make use of flood hazard maps for risk communication purposes. A qualitative case study of this issue in the German state of Baden-Württemberg suggests that many municipalities lack a clear strategy for using this new information tool for hazard and risk communication. Four barriers in this regard are identified: perceived disinterest/sufficient awareness on behalf of the population at risk; unwillingness to cause worry or distress; lack of skills and resources; and insufficient support. These barriers are important to address – in research as well as in practice – since it is only if flood hazard maps are used to enhance local knowledge resources that they can be expected to contribute to social capacity building.
Keywords: Ouvrage_Collectif_Numéro1

Perception and Communication of Flood Risks: A Systematic Review of Empirical Research - Kellens, Wim; Terpstra, Teun; De Maeyer, Philippe (Risk Analysis, 2013)
Flood hazards are the most common and destructive of all natural disasters. For decades, experts have been examining how flood losses can be mitigated. Just as in other risk domains, the study of risk perception and risk communication has gained increasing interest in flood risk management. Because of this research growth, a review of the state of the art in this domain is believed necessary. The review comprises 57 empirically based peer‐reviewed articles on flood risk perception and communication from the Web of Science and Scopus databases. The characteristics of these articles are listed in a comprehensive table, presenting research design, research variables, and key findings. From this review, it follows that the majority of studies are of exploratory nature and have not applied any of the theoretical frameworks that are available in social science research. Consequently, a methodological standardization in measuring and analyzing people's flood risk perceptions and their adaptive behaviors is hardly present. This heterogeneity leads to difficulties in comparing results among studies. It is also shown that theoretical and empirical studies on flood risk communication are nearly nonexistent. The article concludes with a summary on methodological issues in the fields of flood‐risk perception and flood‐risk communication and proposes an agenda for future research.
Keywords: Ouvrage_Collectif_Numéro1

Enhancing flash flood risk perception and awareness of mitigation actions through risk communication: A pre-post survey design - Bodoque, J.M.; Díez-Herrero, A.; Amerigo, M.; García, J.A.; Olcina, J. (Journal of Hydrology, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Conceptual Framework for Motivating Actions towards Disaster Preparedness Through Risk Communication - Abunyewah, Matthew; Gajendran, Thayaparan; Maund, Kim (Procedia Engineering, 2018)
Keywords: Ouvrage_Collectif_Numéro1

La résilience des personnes âgées à la suite de leur exposition à un sinistre - Maltais, Danielle; Gauthier, Simon (3e Congrès mondial sur la résilience, 2016)
Keywords: Ouvrage_Collectif_Numéro1

Socioeconomic development and the impact of natural disasters: some empirical evidences from China - Zhou, Yang; Li, Ning; Wu, Wenxiang; Liu, Haolong; Wang, Li; Liu, Guangxu; Wu, Jidong (Natural Hazards, 2014)
Significant advancements have been made in examining the relationship between economic development and disaster losses at the global and national scales, but very little research has been done at the sub-national level, especially in China. Based on socioeconomic and disaster impact data from 31 provinces (municipalities, and autonomous regions) in China from 1990 to 2010, ordinary least squares regression was used to determine the relationship between socioeconomic development and effects of natural disasters. Results showed that economic development played a distinct role in mitigating disaster damages in the whole China and its eastern, central and western regions. There existed a U-shaped relationship between economic growth and disaster losses in the whole China and its eastern region, and an inverted-U nonlinearity linkage in its central and western areas. These findings further confirmed the existence of a nonlinear relationship between economic development and disaster losses. Economic growth had played a more important role in mitigating disaster losses in the central region of China than that in the western one. Further investigations demonstrated that as economic develops, there were fewer deaths caused by natural hazards in whole China and all its three regions. The combination of the lower level of education, higher unemployment rate and greater gross dependence ratio has contributed to the increase in death toll caused by natural disasters, but this trend could be partly offset by wealth growth.

L'approche écosystémique de la santé des populations : le cas de l’exposition au mercure des communautés riveraines de l’Amazonie et du nord du Québec - Weissenberger, Sebastian; Silva, Delaine Sampaio Da; Schetagne, Roger (Développement durable et territoires, 2013)

Le citoyen au coeur de la résilience dans l’agglomération de Montréal : lorsque l’adaptation au risque devient la préoccupation de chacun - Francès, Nathalie (2019)
La résilience, cette capacité d’une ville ou d’un environnement à maintenir sa structure, à s’organiser, apprendre et s’adapter aux chocs et stress, participe au mouvement de responsabilisation accrue du citoyen dans la protection contre les risques naturels. Si les inondations sont un phénomène récurrent à Montréal depuis la création même de la ville, les citoyens n’y sont encore que peu préparés comme le démontre l’ampleur des dommages causés par les inondations du printemps de 2017. Depuis le début du 21e siècle, les agences internationales et les États cherchent à sensibiliser le citoyen afin de susciter une action de sa part. On suppose alors que le citoyen informé aura ainsi une perception accrue des risques, conduisant au comportement de protection. Ce lien entre information, perception et comportement n’est pourtant pas évident. En réalité, la littérature montre que le comportement dépend d’une multiplicité de facteurs tels que l’expérience, la fréquence du risque ainsi qu’une évaluation par la personne de l’efficacité des mesures de protection, de leur coût face à une évaluation de la probabilité de la menace. Le mémoire vise à répondre à la question de recherche suivante : comment inciter les individus à adopter des mesures de protection contre les inondations à Montréal ? Une enquête auprès de 237 citoyens de quatre secteurs de l’agglomération touchés par les inondations printanières de 2017 met en lumière un ensemble d’obstacles à l’adoption des mesures de protection contre les inondations aujourd’hui analysés grâce au Protective Action Decision Model de Lindell et Perry (2012). Ainsi, dans le cas de Montréal, le manque d’action relève à la fois d’un manque d’information et de connaissances sur les origines du risque et les mesures de prévention, de la perception d’inefficacité des mesures comme la trousse 72 heures, d’une perception d’incapacité à mettre en place soi-même les mesures de prévention, et d’un coût important en ressources de ces dernières. Le dernier élément est l’incertitude de ce type de risque et l’incapacité à prévoir avec précision le prochain événement de crue, qui, combiné à un sentiment de responsabilité élevé des autorités à assurer la protection, implique un manque d’urgence à agir. Face à ces constats et après une étude du cas de la Nouvelle Orléans aux États-Unis, une réflexion est proposée sur les moyens à mettre en place pour inciter les citoyens à adopter ces mesures, comprenant sensibilisation mais aussi des moyens coercitifs et incitatifs.
Keywords: Site_internet_RIISQ

The “Lac-Mégantic tragedy” seen through the lens of the EnRiCH Community Resilience Framework for High-Risk Populations - Généreux, Mélissa; Petit, Geneviève; Roy, Mathieu; Maltais, Danielle; O’Sullivan, Tracey (Canadian Journal of Public Health, 2018)
Keywords: Généreux_Mélissa

Resilience and disaster risk reduction: an etymological journey - Alexander, David (Natural Hazards and Earth System Sciences, 2013)
Abstract. This paper examines the development over historical time of the meaning and uses of the term resilience. The objective is to deepen our understanding of how the term came to be adopted in disaster risk reduction and resolve some of the conflicts and controversies that have arisen when it has been used. The paper traces the development of resilience through the sciences, humanities, and legal and political spheres. It considers how mechanics passed the word to ecology and psychology, and how from there it was adopted by social research and sustainability science. As other authors have noted, as a concept, resilience involves some potentially serious conflicts or contradictions, for example between stability and dynamism, or between dynamic equilibrium (homeostasis) and evolution. Moreover, although the resilience concept works quite well within the confines of general systems theory, in situations in which a systems formulation inhibits rather than fosters explanation, a different interpretation of the term is warranted. This may be the case for disaster risk reduction, which involves transformation rather than preservation of the "state of the system". The article concludes that the modern conception of resilience derives benefit from a rich history of meanings and applications, but that it is dangerous – or at least potentially disappointing – to read to much into the term as a model and a paradigm.

Psychosocial Stress, Sedentary Behavior, and Physical Activity during Pregnancy among Canadian Women: Relationships in a Diverse Cohort and a Nationwide Sample - Sinclair, Isabelle; St-Pierre, Myriane; Elgbeili, Guillaume; Bernard, Paquito; Vaillancourt, Cathy; Gagnon, Sonia; Dancause, Kelsey Needham (International Journal of Environmental Research and Public Health, 2019)
Background: Past research shows that psychosocial stress and distress predict sedentary behavior and physical activity, but few studies focus on pregnant women. Our objective was to analyze relationships between psychosocial stress and distress with sedentary behavior and physical activity among pregnant women in Canada. Methods: We analyzed objectively-measured sedentary behavior and physical activity at 16–18, 24–26, and 32–24 weeks pregnancy in a sociodemographically diverse cohort of 70 women in Montreal, Canada. Participants completed the Perceived Stress Questionnaire and wore an accelerometer for 3 days that quantified sitting time and steps per day. We used univariate general linear models to analyze relationships between perceived stress with sedentary behavior and physical activity at each evaluation. To assess generalizability, we analyzed relationships between psychological distress with self-reported leisure-time sedentary behavior and daily energy expenditure in transportation and leisure physical activities among a sample representative of 166,095 women in the Canadian Community Health Survey. Results: In the Montreal cohort, we observed a positive association between perceived stress and sitting time, with small to moderate effect sizes (partial η2 = 0.08–0.16). We observed negative relationships between perceived stress and steps per day at the first two evaluations only, with small to moderate effect sizes (partial η2 = 0.08–0.11). Relationships for sedentary behavior were similar in the nationwide sample, but with smaller effect sizes (partial η2 = 0.02). There were no relationships between distress and physical activity in the nationwide sample. Conclusion: Psychosocial stress represents one risk factor for sedentarity, with relationships evident throughout pregnancy and at the population level. Relationships with physical activity are less consistent, but stress might represent a risk factor for low physical activity in early to mid-pregnancy. Results might guide the development of more comprehensive interventions targeting stress, sedentarity, and physical activity. In particular, integrating psychosocial health into interventions to reduce sedentarity, and including concrete guidelines on sedentary behavior in psychosocial health interventions, might be prioritized.

Economic development and losses due to natural disasters: The role of hazard exposure - Schumacher, Ingmar; Strobl, Eric (Ecological Economics, 2011)

Les impacts des changements climatiques sur la santé au Québec : l’exemple de l’Estrie - Petit, Geneviève; Lachance, Éric; Généreux, Mélissa; Barbeau-Meunier, Charles-Antoine; Pinsonneault, Linda; Dao, Huy Hao; Milot, Marie-Christine; Baron, Geneviève; Carignan, Alex (Université de Sherbrooke, 2019)
L’Organisation mondiale de la Santé (OMS) soutient que les changements climatiques représentent la plus grande menace pour la santé dans le monde au 21e siècle. Ceux-ci influencent négativement plusieurs déterminants sociaux et environnementaux de la santé comme l’accessibilité à la nourriture et la qualité de cette dernière, l’eau et l’air. Blessures, impacts psychosociaux, aggravation de maladies respiratoires, malnutrition, maladies infectieuses, décès : les conséquences sanitaires sont susceptibles d’affecter les populations sur tous les continents. Le Canada se réchauffe deux fois plus rapidement que la moyenne mondiale en raison de sa proximité au pôle Arctique, où le réchauffement est accéléré comparativement à l’équateur (Bush et Lemmen, 2019). Ainsi, le Québec n’est certainement pas à l’abri des changements climatiques. Dans le Sud de la province, les températures moyennes observées ont augmenté de plus d’un degré depuis 1970 et des répercussions se font déjà sentir dans notre environnement. Ce réchauffement, accompagné d’une plus grande variabilité du climat (augmentation du risque d’orages, de tempêtes et d’extrêmes hydrométéorologiques en général), représente un défi grandissant pour les professionnel.le.s de la santé. Dans la région de l’Estrie, les professionnel.le.s de santé publique ont effectué une analyse qui leur ont permis d’identifier quatre principaux problèmes environnementaux associés aux changements climatiques, soit : les vagues de chaleur; les inondations; les tiques à pattes noires; le pollen de l’herbe à poux. Ces problèmes ont des impacts importants sur la santé, c’est-à-dire potentiellement graves ou qui touchent un grand nombre de personnes. Le stress et les pertes (humaines et matérielles) engendrées par ces différents problèmes environnementaux peuvent aussi représenter une source majeure de problèmes psychologiques significatifs pouvant persister dans le temps. De plus, ces impacts sont variables selon les différents contextes sociaux des individus et des communautés, générant des inégalités sociales de santé.
Keywords: Généreux_Mélissa

Health Risks of Flood Disasters - Paterson, David L; Wright, Hugh; Harris, Patrick N A (Clinical Infectious Diseases, 2018)
Keywords: Ouvrage_Collectif_Numéro1

Normalizing Economic Loss from Natural Disasters: A Global Analysis - Neumayer, Eric; Barthel, Fabian (Global Environmental Change-human and Policy Dimensions, 2011)
Abstract Climate change is likely to lead to an increase in the frequency and/or intensity of certain types of natural hazards, if not globally, then at least in certain regions. All other things equal, this should lead to an increase in the economic toll from natural disasters over time. Yet, all other things are not equal since affected areas become wealthier over time and rational individuals and governments undertake defensive mitigation measures, which requires normalizing economic losses if one wishes to analyze trends in economic loss from natural disasters for detecting a potential climate change signal. In this article, we argue that the conventional methodology for normalizing economic loss is problematic since it normalizes for changes in wealth over time, but fails to normalize for differences in wealth across space at any given point of time. We introduce an alternative methodology that overcomes this problem in theory, but faces many more problems in its empirical application. Applying, therefore, both methods to the most comprehensive existing global dataset of natural disaster loss, in general we find no significant upward trends in normalized disaster damage over the period 1980–2009 globally, regionally, for specific disasters or for specific disasters in specific regions. Due to our inability to control for defensive mitigation measures, one cannot infer from our analysis that there have definitely not been more frequent and/or more intensive weather-related natural hazards over the study period already. Moreover, it may still be far too early to detect a trend if human-induced climate change has only just started and will gain momentum over time.

Seniors Who Experienced the Lac-Mégantic Train Derailment Tragedy: What Are the Consequences on Physical and Mental Health? - Maltais, Danielle; Tremblay, Anne-Julie; Labra, Oscar; Fortin, Geneviève; Généreux, Mélissa; Roy, Mathieu; Lansard, Anne-Lise (Gerontology and Geriatric Medicine, 2019)
Introduction: In July 2013, a train derailment caused the death of 47 people and destroyed the downtown area in the city of Lac-Mégantic (Quebec, Canada). This tragedy had several impacts on this small community. Method: Three years after this disaster, we used a representative population-based survey conducted among 800 adults (including 265 seniors aged 65 or above) to assess the physical and mental health of seniors. Results: Several differences were observed in seniors’ physical and mental health based on their level of exposure to the tragedy. Nearly half of seniors highly exposed to the train derailment (41.7%) believe that their health has deteriorated in the past 3 years. The majority of seniors highly exposed to the train derailment (68.7%) also show symptoms of posttraumatic stress disorders. Seniors highly or moderately exposed to the tragedy were also more likely to have found positive changes in their personal and social life as compared with nonexposed seniors. Discussion: A technological disaster such as a train derailment still had negative impacts on seniors’ physical and mental health 3 years later. Conclusion: Public health authorities must tailor prevention and promotion programs to restore health and well-being in this population.
Keywords: Généreux_Mélissa

Lorsque le pire se produit : ce que les intervenants du domaine du social devraient savoir en ce qui a trait à l’intervention sociale en cas de catastrophe auprès des personnes âgées - Maltais, Danielle (5e Congrès de l'Association internationale pour la Formation, la Recherche et l'intervention sociale (AIFRIS), 2013)
Plus aucune communauté n’est à l’abri des catastrophes naturelles et technologiques et de plus en plus les intervenants du domaine du social sont appelés à intervenir lors de ces situations. Malheureusement, plusieurs d’entre eux interviennent pendant et après une catastrophe sans avoir reçu une formation de base sur l’intervention en situation de crise macrosociale. Pourtant, ce type d’intervention exige des habiletés de base qui doivent s’acquérir à la fois dans les maisons d’enseignement et lors de formations continues. De plus, en cas de désastre naturels ou technologiques, certains groupes d’individus, dont les personnes âgées, sont plus vulnérables que d’autres parce qu’elles n’ont pas facilement accès aux ressources de la communauté. Par exemple, plusieurs personnes âgées, surtout celles présentant des incapacités physiques ou cognitives et celles à faible revenu n’ont, en général, pas de voitures à leur disponibilité, ce qui peut nuire à leur évacuation lors d’inondations, de tremblements de terre ou d’ouragans. De plus, plusieurs aînés habitent dans de vieux logements moins bien construits pour faire face à des chocs de toutes sortes. Les personnes âgées et particulièrement celles présentant des incapacités physiques ou cognitives, celles à faibles revenus ou sans réseau de soutien social font parties des groupes à risque de subir des blessures, de mourir ou de développer des problèmes de santé post-désastre. Le décès d’un nombre important de personnes âgées pendant l’ouragan Katrina et la vague de chaleur de l’été 2003 en Europe, a malheureusement démontré que plusieurs communautés sont très mal préparées à protéger et secourir, en cas de catastrophe, les aînés et plus particulièrement les personnes âgées vulnérables. De plus, plusieurs études ont fait ressortir qu’à la suite d’un désastre, les personnes âgées reçoivent proportionnellement moins d’aide que les personnes plus jeunes (Fernandez et al 2002), soit parce qu’elles ne sont pas priorisées par les autorités locales ou parce qu’elles-mêmes hésitent à informer leurs proches et les organismes publics ou communautaires de leurs besoins de soutien. Tout individu, quel que soit son âge a un important besoin de soutien social pendant et après un désastre afin d’atténuer les effets du stress et surmonter les obstacles qui se présenteront. On pense par exemple à l’interruption des services essentiels comme l’eau potable ou l’électricité, la lourdeur démocratique, l’endettement, les négociations avec des entrepreneurs quelque peu malhonnêtes, etc. À ce sujet, plusieurs chercheurs considèrent les désastres comme une suite d’événements stressants pouvant occasionner de nombreuses difficultés aux individus (Murphy, 1986). Cette communication permettra de présenter les résultats de nos études effectuées sur les conséquences des désastres sur la santé physique et psychologique des aînés ainsi que sur divers aspects de leur vie (vie personnelle, conjugale, familiale et sociale). En explicitant les sentiments et les difficultés que ces personnes éprouvent lors de catastrophes, les intervenants du domaine du social seront alors mieux outiller pour intervenir auprès de ce groupe cible. Cette communication a donc pour but de présenter les principaux faits saillants et les recommandations de la recension des écrits scientifiques que nous avons dernièrement complété et des faits saillants des diverses études que nous avons réalisées jusqu’à maintenant auprès des personnes âgées à la suite de deux types de désastres : inondation et tempête de verglas. Cette communication a pour but de sensibiliser les participants à l’importance de tenir compte, pour les intervenants du social, des spécificités des aînés lors de l’application des mesures d’urgence et lors de la période de rétablissement des communautés.

An interdisciplinary perspective on social and physical determinants of seismic risk - Lin, K.-H. E.; Chang, Y.-C.; Liu, G.-Y.; Chan, C.-H.; Lin, T.-H.; Yeh, C.-H. (Natural Hazards and Earth System Sciences, 2015)
Abstract. While disaster studies researchers usually view risk as a function of hazard, exposure, and vulnerability, few studies have systematically examined the relationships among the various physical and socioeconomic determinants underlying disasters, and fewer have done so through seismic risk analysis. In the context of the 1999 Chi-Chi earthquake in Taiwan, this study constructs three statistical models to test different determinants that affect disaster fatality at the village level, including seismic hazard, exposure of population and fragile buildings, and demographic and socioeconomic vulnerability. The Poisson regression model is used to estimate the impact of these factors on fatalities. Research results indicate that although all of the determinants have an impact on seismic fatality, some indicators of vulnerability, such as gender ratio, percentages of young and aged population, income and its standard deviation, are the important determinants deteriorating seismic risk. These findings have strong social implications for policy interventions to mitigate such disasters.

Les perspectives temporelles : les connaître pour en tenir compte dans nos interventions en promotion de la santé - Lessard, Lily (Global Health Promotion, 2012)
Résumé La modification des habitudes de vie pour adopter des comportements sains repose notamment sur la capacité des individus et des populations à estimer les conséquences à long terme des gestes accomplis aujourd’hui. Cette capacité peut cependant varier d’une personne à l’autre, notamment en raison des perspectives temporelles (PT) adoptées. Les PT réfèrent à la tendance d’une personne ou d’un groupe de personnes à orienter ses décisions en fonction d’une vision tournée vers le passé, le présent ou le futur. Cet article vise à démystifier le concept de PT et à comprendre leur construit, afin d’identifier différentes façons d’en tenir compte dans les interventions en promotion de la santé. L’influence des PT sur la santé est principalement liée à leur capacité d’agir sur la motivation des personnes à adopter et à maintenir certains comportements. Une attention particulière doit être portée aux personnes et aux populations dont les PT sont orientées vers le présent. Elles présenteraient un plus grand risque d’adopter des comportements délétères et seraient susceptibles d’être moins sensibles aux messages qui visent la modification de ces comportements que les personnes qui adoptent une PT orientée vers le futur. En ce qui concerne leur construit, les PT sont le fruit de différentes dynamiques psychologiques et des facteurs individuels (âge, sexe, état de santé) et environnementaux (milieu familial, statut socioéconomique, éducation, culture). Parmi les moyens présentés pour tenir compte des PT dans les interventions en promotion de la santé figurent la mise en valeur des avantages à court terme d’un changement de comportement qui vise des bénéfices à long terme pour la santé, la modulation de l’intensité du soutien à l’empowerment des communautés en fonction des PT adoptées et la permutation d’une PT orientée vers le présent vers une PT orientée vers le futur.
Keywords: Lessard_Lily

Responding to a Changing Climate: An Investigation of the Psychosocial Consequences of Climate Change and Community-based Mental Health Responses in High River - Hayes, K. (2019)
This dissertation explores the psychosocial consequences of climate change and psychosocial adaptation opportunities in High River, Alberta. Influenced by the theoretical approach of Political Ecology, I investigate community impacts and community-based mental health responses in High River following the 2013 Southern Alberta floods. Research methods include: a desktop climate change and health vulnerability and adaptation assessment that includes over 116 data sources; telephone interviews with key informant health and social services leaders (n = 14); four focus group sessions with front-line health and social services workers (n = 14); and, semi-structured interviews (n = 18) with a sample of community-members exposed to the 2013 flood and who self-identify in any one or more ways: female, youth, elderly, non-white, someone living in a low socio-economic status, someone with pre-existing health concerns. A total of 46 participants were recruited in this research. Results of the empirical investigation in High River are showcased in three manuscripts. The first manuscript, informed by critical Political Ecology, is an investigation of sociopolitical conditions that influence health inequities and adaptation opportunities (or lack thereof) in a changing climate in High River. The second is an empirical exploration of the long-term psychosocial consequences of the 2013 flood, relating these

Flood- and Weather-Damaged Homes and Mental Health: An Analysis Using England’s Mental Health Survey - Graham, Hilary; White, Piran; Cotton, Jacqui; McManus, Sally (International Journal of Environmental Research and Public Health, 2019)
There is increasing evidence that exposure to weather-related hazards like storms and floods adversely affects mental health. However, evidence of treated and untreated mental disorders based on diagnostic criteria for the general population is limited. We analysed the Adult Psychiatric Morbidity Survey, a large probability sample survey of adults in England (n = 7525), that provides the only national data on the prevalence of mental disorders assessed to diagnostic criteria. The most recent survey (2014–2015) asked participants if they had experienced damage to their home (due to wind, rain, snow or flood) in the six months prior to interview, a period that included months of unprecedented population exposure to flooding, particularly in Southern England. One in twenty (4.5%) reported living in a storm- or flood-damaged home in the previous six months. Social advantage (home ownership, higher household income) increased the odds of exposure to storm or flood damage. Exposure predicted having a common mental disorder over and above the effects of other known predictors of poor mental health. With climate change increasing the frequency and severity of storms and flooding, improving community resilience and disaster preparedness is a priority. Evidence on the mental health of exposed populations is key to building this capacity.
Keywords: Ouvrage_Collectif_Numéro1

Risk and Protective Factors for Mental Health and Community Cohesion After the 2013 Calgary Flood - Hetherington, Erin; McDonald, Sheila; Wu, Muci; Tough, Suzanne (Disaster Medicine and Public Health Preparedness, 2018)
Abstract Objective To examine mental health and community cohesion in women living in Calgary after a natural disaster considering previously collected mental health data. Methods Data from an ongoing longitudinal cohort, the All Our Families study, were used to examine mental health and community cohesion 5 months after a major flood in Calgary, Canada. Participants who had completed a baseline questionnaire before the flood were eligible for inclusion in this study (N=923). Four multivariable logistic regression models were built to examine predictors of post-traumatic stress, depression, anxiety, and community cohesion. Results Elevated anxiety before the flood was associated with 2.49 (95% CI: 1.17, 5.26) increased odds of experiencing high levels of post-traumatic stress, regardless of whether respondents lived in a flood-risk community or not. Women who experienced damage to property, or who provided help to others, were more likely to perceive an increased sense of community cohesion (adjusted ods ratio (AOR): 1.67; 95% CI: 1.09, 2.54 and AOR: 1.68; 95% CI: 1.13, 2.52, respectively). Conclusions Women with underlying mental health conditions may be more vulnerable to the psychological impacts of a natural disaster regardless of their level of exposure. Natural disasters may bring communities together, especially those who were more tangibly impacted. ( Disaster Med Public Health Preparedness . 2018;12:470–477)
Keywords: Ouvrage_Collectif_Numéro1

The effectiveness of flood risk communication strategies and the influence of social networks—Insights from an agent-based model - Haer, Toon; Botzen, W.J. Wouter; Aerts, Jeroen C.J.H. (Environmental Science & Policy, 2016)
Keywords: Ouvrage_Collectif_Numéro1

An Exploration of the Link between Development, Economic Growth,and Natural Risk - Hallegatte, Stephane (2012)
This paper investigates the link between development, economic growth, and the economic losses from natural disasters in a general analytical framework, with an illustration on hurricane flood risks in New Orleans. It concludes that, where capital accumulates through increased density of capital at risk in a given area, (i) the probability of disaster occurrence decreases with income; (ii) capital at risk and thus economic losses in case of disaster -- increases faster than economic growth; (iii) increasing risk-taking reinforces economic growth. Economic growth and improved protection transfer risks from frequent low-intensity events to rarer high-impact events. In this context, average annual losses from disasters grow with income, and they grow faster than income at low levels of development and slower than income at high levels of development. These findings are robust to a broad range of modeling choices and parameter values, to the inclusion of risk aversion, and to variations in the decision-making framework (including the introduction of prospect theory's decision weights, biases in risk perception and myopic expectations). They show that risk-taking is both a driver and a consequence of economic development, that risk taking should not be indiscriminately suppressed, and that the world is very likely to experience fewer but more costly disasters in the future.

The Economics of Natural Disasters - Kellenberg, Derek; Mobarak, A. Mushfiq (Annual Review of Resource Economics, 2011)
This review discusses the ways in which countries are affected by natural disasters, depending on their socioeconomic characteristics, their level of development, and their inherent levels of natural disaster risk. We also explore various aspects of ex ante disaster mitigation such as improvements in natural disaster risk information and natural disaster insurance markets, as well as ex post responses to natural disaster in the form of postdisaster aid and long-run growth prospects. By highlighting some of the recent findings in this literature, we synthesize what we know about the economics of natural disasters and identify research areas of interest for future work.

Monitoring Adverse Psychosocial Outcomes One and Two Years After the Lac-Mégantic Train Derailment Tragedy (Eastern Townships, Quebec, Canada) - Généreux, Mélissa; Maltais, Danielle; Petit, Geneviève; Roy, Mathieu (Prehospital and Disaster Medicine, 2019)
Introduction:In July 2013, a train carrying 72 cars of crude oil derailed in the town of Lac-Mégantic (Eastern Townships, Quebec, Canada). This disaster provoked a major conflagration, explosions, 47 deaths, the destruction of 44 buildings, the evacuation of one-third of the local population, and an unparalleled oil spill. Notwithstanding the environmental impact, many citizens of this town and in surrounding areas have suffered and continue to suffer substantial losses as a direct consequence of this catastrophe.Problem:To tailor public health interventions and to meet the psychosocial needs of the community, the Public Health Department of Eastern Townships has undertaken repeated surveys to monitor health and well-being over time. This study focuses on negative psychosocial outcomes one and two years after the tragedy.Methods:Two cross-sectional surveys (2014 and 2015) were conducted among large random samples of adults in Lac-Mégantic and surrounding areas (2014: n = 811; 2015: n = 800), and elsewhere in the region (2014: n = 7,926; 2015: n = 800). A wide range of psychosocial outcomes was assessed (ie, daily stress, main source of stress, sense of insecurity, psychological distress, excessive drinking, anxiety or mood disorders, psychosocial services use, anxiolytic drug use, gambling habits, and posttraumatic stress symptoms [PSS]). Exposure to the tragedy was assessed using residential location (ie, six-digit postal code) and intensity of exposure (ie, intense, moderate, or low exposure; from nine items capturing human, material, or subjective losses). Relationships between such exposures and adverse psychosocial outcomes were examined using chi-squares and t-tests. Distribution of outcomes was also examined over time.Results:One year after the disaster, an important proportion of participants reported human, material, and subjective losses (64%, 23%, and 54%, respectively), whereas 17% of people experienced intense exposure. Participants from Lac-Mégantic, particularly those intensely exposed, were much more likely to report psychological distress, depressive episode, anxiety disorders, and anxiolytic drug use, relative to less-exposed ones. In 2015, 67% of the Lac-Mégantic participants (76% of intensely exposed) reported moderate to severe PSS. Surprisingly, the use of psychosocial services in Lac-Mégantic declined by 41% from 2014 to 2015.Conclusion:The psychosocial burden in the aftermath of the Lac-Mégantic tragedy is substantial and persistent. Public health organizations responding to large-scaling disasters should monitor long-term psychosocial consequences and advocate for community-based psychosocial support in order to help citizens in their recovery process.
Keywords: Généreux_Mélissa

From Science to Policy and Practice: A Critical Assessment of Knowledge Management before, during, and after Environmental Public Health Disasters - Généreux, Mélissa; Lafontaine, Marc; Eykelbosh, Angela (International Journal of Environmental Research and Public Health, 2019)
Canada regularly faces environmental public health (EPH) disasters. Given the importance of evidence-based, risk-informed decision-making, we aimed to critically assess the integration of EPH expertise and research into each phase of disaster management. In-depth interviews were conducted with 23 leaders in disaster management from Canada, the United States, the United Kingdom, and Australia, and were complemented by other qualitative methods. Three topics were examined: governance, knowledge creation/translation, and related barriers/needs. Data were analyzed through a four-step content analysis. Six critical success factors emerged from the analysis: blending the best of traditional and modern approaches; fostering community engagement; cultivating relationships; investing in preparedness and recovery; putting knowledge into practice; and ensuring sufficient human and financial resources. Several promising knowledge-to-action strategies were also identified, including mentorship programs, communities of practice, advisory groups, systematized learning, and comprehensive repositories of tools and resources. There is no single roadmap to incorporate EPH expertise and research into disaster management. Our findings suggest that preparation for and management of EPH disaster risks requires effective long-term collaboration between science, policy, and EPH practitioners at all levels in order to facilitate coordinated and timely deployment of multi-sectoral/jurisdictional resources when and where they are most needed.
Keywords: Généreux_Mélissa

Psychosocial Management Before, During, and After Emergencies and Disasters—Results from the Kobe Expert Meeting - Généreux, Mélissa; Schluter, Philip J.; Takahashi, Sho; Usami, Shiori; Mashino, Sonoe; Kayano, Ryoma; Kim, Yoshiharu (International Journal of Environmental Research and Public Health, 2019)
Emergencies and disasters typically affect entire communities, cause substantial losses and disruption, and result in a significant and persistent mental health burden. There is currently a paucity of evidence on safe and effective individual- and community-level strategies for improving mental health before, during, and after such events. In October 2018, the World Health Organization (WHO) Centre for Health Development (WHO Kobe Centre) convened a meeting bringing together leading Asia Pacific and international disaster research experts. The expert meeting identified key research needs in five major areas, one being “Psychosocial management before, during, and after emergencies and disasters”. Experts for this research area identified critical gaps in observational research (i.e., the monitoring of long-term psychological consequences) and interventional research (i.e., the development and evaluation of individual- and community-level interventions). Three key research issues were identified. First, experts underscored the need for a standardized and psychometrically robust instrument that classified the mental health/psychosocial risk of people within both a clinical and community setting. Then, the need for a standardization of methods for prevention, screening, diagnosis, and treatment for affected people was highlighted. Finally, experts called for a better identification of before, during, and after emergency or disaster assets associated with greater community resilience.
Keywords: Généreux_Mélissa

L’interdisciplinarité au service de la santé: le cas du Québec - Gachon, P.; Dueymes, G.; Gosselin, P.; Gagnon, O. (Territoires, incubateurs de santé. Les Cahiers de l’Institut d’Aménagement et d’Urbanisme (Ile de France), 2014)
Renforcer la capacité d’intervention et d’adaptation en santé publique nécessite d’améliorer l’efficacité des systèmes d’alerte précoce vis-à-vis des risques climatiques en évolution. Ceci implique des ajustements aux activités en cours, voire de modifier les façons de faire au sein des organisations et entre les organisations en augmentant, notamment, leurs collaborations. L’interdisciplinarité au service de la santé publique est donc de mise.
Keywords: Gachon_Philippe

Economic losses from US hurricanes consistent with an influence from climate change - Estrada, Francisco; Botzen, W. J. Wouter; Tol, Richard S.J. (Nature Geoscience, 2015)
The observed increases in hurricane losses are often thought to result solely from societal change. A regression-based analysis of US economic losses reveals an upward trend between 1900 and 2005 that is not explained by increasing vulnerability.

Health Effect on and Adaptation of the Elderly Affected by Floods - Chompunud, Somjinda; Inkaew, Wanpen (Health Emergency and Disaster Nursing, 2019)
Aim: The aim of the study was to investigate the health effect on and adaptation of the elderly affected by floods in the Lat Krabang District, Bangkok, Thailand in 2011.Methods: A cross-sectional descriptive study was conducted. Data were collected from 290 elderly participants who were affected by the floods using questionnaires.Results: The elderly participants had previous experience with flooding, but the massive flooding in 2011 was the most severe compared to any other experiences in the past. Physical health effects included muscle pain (35.2%), athlete’s foot (28.3%), and skin rash (23.1%). The psychological health effects (24.3%) encountered included insomnia, constant stress and tension, attention deficit, and discontentment. Most elderly (89.3%) decided not to relocate thinking they could still live at home, but they were concerned about the safety of their property. In regards to preparation for the flood, they prepared consumer goods, medication, and emergency kits. In addition, they kept abreast with news on television and public announcements in the community. They also helped clear the drainage system and prepared contact information of children, relatives, and government offices in case they needed assistance. Finally, to reduce possible damage to the property, they moved their belongings to high places, built sandbag walls, raised the house level, and prepared a water pump.Conclusion: The 2011 Thailand floods had adverse effects on physical and psychological health of the elderly people. To ensure better management for this vulnerable group, plans to respond to possible disasters need to be devised by relevant agencies to reduce flood-related health impacts.
Keywords: Ouvrage_Collectif_Numéro1; adaptation; elderly; flood; health effect

Social and spatial inequities in exposure to flood risk in Miami, Florida - Chakraborty, Jayajit; Collins, Timothy W.; Montgomery, Marilyn; Grineski, Sara E. (Natural Hazards Review, 2014)
AbstractAlthough environmental justice (EJ) research in the United States has traditionally focused on technological hazards such as air pollution or hazardous waste, the adverse and unequal impacts of Hurricane Katrina have prompted researchers to examine the EJ implications of natural events such as hurricanes and floods. This paper contributes to this emerging literature on EJ and social vulnerability to natural hazards by analyzing racial/ethnic and socioeconomic inequities in the distribution of flood risk exposure in the Miami Metropolitan Statistical Area (MSA), Florida—one of the most hurricane-prone areas in the world and one of the most ethnically and socioeconomically diverse MSAs in the United States. Although previous studies have relied exclusively on the 100-year floodplain to assess the spatial extent of flood exposure, this study makes a systematic distinction between different types of flood zones on the basis of both the probability (100-year versus 500-year versus low/no risk) of flood...

Health and social impacts of a flood disaster: responding to needs and implications for practice - Carroll, Bob; Balogh, Ruth; Morbey, Hazel; Araoz, Gonzalo (Disasters, 2010)
Carlisle in northwest England suffered its worse floods for more than 180 years in 2005. A study, reported here, was undertaken to assess the health and social impacts of these floods via in‐depth, taped individual and focus‐group interviews with people whose homes had been flooded and with agency workers who helped them. Respondents spoke of physical health ailments, psychological stress, water health‐and‐safety issues related to the floods, and disputes with insurance and construction companies, which they felt had caused and exacerbated psychological health problems. Support workers also suffered from psychological stress. Furthermore, it was found that people had low expectations of a flood and were not prepared. The findings are presented in five sections covering flood risk awareness, water contamination issues, physical health, mental health, and impact on frontline support workers. The discussion focuses on the implications of the findings for policy and practice vis‐à‐vis psychological health provision, contamination issues, training and support for frontline support workers, matters relating to restoration, and preparation for flooding.

Using FloodRisk GIS freeware for uncertainty analysis of direct economic flood damages in Italy - Albano, R.; Sole, A.; Adamowski, J.; Perrone, A.; Inam, A. (International Journal of Applied Earth Observation and Geoinformation, 2018)

Impacts psychosociaux négatifs des vagues de chaleur, des inondations, des feux de forêt et des tempêtes chez les travailleurs du Québec. - Adam-Poupart, A; Pouliot, L; Deger, L; Sassine, M.P; Coll, E.T (Institut national de santé publique du Québec (INSPQ), 2019)
Dans le cadre de la mise en œuvre du Plan d’action 2013-2020 sur les changements climatiques du Québec, le ministère de la Santé et des Services sociaux du Québec a mandaté l’Institut national de santé publique du Québec afin de mener une étude exploratoire portant sur les impacts psychosociaux vécus chez les travailleurs à la suite de quatre événements météorologiques extrêmes qui s’accentueront avec les changements climatiques, soit les vagues de chaleur, les inondations, les tempêtes et les feux de forêt. Cette étude exploratoire visait à examiner brièvement la littérature et les connaissances de différents acteurs-clés afin de proposer par la suite des projets de recherche plus importants et qui répondent aux besoins et aux enjeux des milieux de travail et de la santé publique au Québec. Elle a mis en évidence que les événements météorologiques extrêmes étudiés peuvent entraîner des impacts psychosociaux chez les travailleurs, mais les connaissances sur ces impacts varient grandement selon l’événement. Les impacts psychosociaux chez les travailleurs ont été plus documentés dans la littérature scientifique pour les tempêtes et l’ont été de façon moins importante pour les inondations et les feux de forêt et négligeable pour les vagues de chaleur. Les travailleurs des services de la première ligne (comme les intervenants municipaux, les policiers, les pompiers, et les professionnels de la santé qui interviennent auprès des sinistrés, le personnel des services de travaux publics, etc.) et les agriculteurs font partie des populations de travailleurs qui ont été les plus étudiées. Les impacts psychologiques négatifs comme de l’épuisement, de la fatigue, de la détresse psychologique, de l’anxiété, de la colère et de la tristesse ont été plus souvent rapportés dans la littérature que les impacts sociaux. Il existe des facteurs de risque organisationnels (ex. : surcharge de travail, le manque de formation, de ressources matérielles, de personnels disponibles) et personnels (ex. : le fait d’être sinistré, le manque de contact avec les membres de la famille), communs à plusieurs événements et types de travailleurs, et qui peuvent aggraver les impacts psychosociaux vécus chez les travailleurs. Il existe aussi des facteurs de protection (ex. : reconnaissance ou gratitude, résilience individuelle, soutien social et efficacité collective). Il est important de consulter des acteurs clés pour bonifier les connaissances de la littérature scientifique. Dans le cadre de cette étude, les consultations avec des acteurs clés ont permis d’identifier de nouveaux travailleurs vulnérables, d’en apprendre davantage sur les caractéristiques de certains événements météorologiques extrêmes et de réaliser que les impacts psychosociaux vécus à la suite de ceux-ci pouvaient être positifs. L’acquisition de connaissances sur les impacts psychosociaux vécus chez les travailleurs à la suite des inondations est un des sujets qui répond aux besoins et aux enjeux des milieux de travail et de la santé publique au Québec.

A review of the flood risk management governance and resilience literature - Morrison, A.; Westbrook, C.J.; Noble, B.F. (Journal of Flood Risk Management, 2018)
The environmental management literature suggests that resilience is key to managing complex systems and reducing vulnerability resulting from uncertainty and unexpected change. Yet, flood risk management (FRM) has emerged largely from a culture of resistance. This paper takes the pulse of the current state of FRM research, with a focus on how the scholarly community has approached governance for flood resilience. Our analysis of the FRM journal literature identified 258 articles addressing governance and flooding, resilience and adaptation. Five main research themes emerged from these articles, addressing a variety of issues, but mostly lacking the degree of integration needed to address the social‐ecological complexity of FRM. Overall, research supporting the governance of FRM for resilience lacks integration, and methods of mitigating this lack of integration are poorly studied. We conclude with a discussion about the nature and scope of FRM research for resilience, and identify opportunities for more integrative FRM research that is more tightly coupled with policy and practice.
Keywords: Ouvrage_Collectif_Numéro1

A decision-support tool to increase urban resilience to flood risk: from a theoretical concept to operational urban managers re-appropriation. A France-Quebec comparative approach - Heinzlef, Charlotte; Robert, Benoît; Hémond, Yannick; Serre, Damien (2019)
Keywords: Hémond_Yannick

Collaborative governance of essential systems risk assessment approach - Lépine, C.; Baril, G.; Therrien, M.-C.; Hémond, Yannick; Robert, Benoît (Canadian Association for Programs in Public Administration Annual Research Conference in Public Administration, Policy, and Management, Montréal, 2019)
Keywords: Hémond_Yannick

Gouvernance collaborative d'appréciation des risques des systèmes essentiels en contexte de changements climatiques : cas de deux MRC au Québec - Lépine, Caroline; Baril, Geneviève; Hémond, Yannick; Therrien, M.-C.; Robert, Benoît (87e Congrès de l'ACFAS, 2019)
Keywords: Hémond_Yannick

Changes in flood risk governance in France: a David and Goliath story? - Fournier, M.; Larrue, C.; Schellenberger, T. (Journal of Flood Risk Management, 2018)
When analysing flood risk governance in France since the beginning of the 1980s, central government appears as a predominant actor. However, to understand contemporary French flood risk governance ( FRG ), it is also important to highlight how this domination has progressively been undermined since 1982. First, a decentralisation movement has been initiated whose main characteristics are an increasing involvement of local governments and a difficulty for national authorities to maintain their predominant role. The second main change is a diversification in flood risk strategies going together with a diversification in the definition of the flood risk issue. FRG is not a sole matter of protection through defence, preparation, and recovery strategies anymore. Both prevention and mitigation strategies have progressively gained in legitimacy. It is in the latter that local governments and stakeholders have increasingly got involved and have taken up responsibilities and initiatives. The paper focuses on the explanatory factors behind both stability and change, and especially on the ongoing tension, between path dependency factors (i.e. state power and role) and organisational capability of local actors.
Keywords: Ouvrage_Collectif_Numéro1

Managing the Risks of Extreme Events and Disasters to Advance Climate Change Adaptation, A Special Report of Working Groups I and II of the Intergovernmental Panel on Climate Change - Intergovernmental Panel on Climate Change (IPCC) (Cambridge University Press, 2012)
Keywords: Ouvrage_Collectif_Numéro1

Participatory approaches for disaster risk governance? Exploring participatory mechanisms and mapping to close the communication gap between population living in flood risk areas and authorities in Nova Friburgo Municipality, RJ, Brazil - Bustillos Ardaya, A.; Evers, M.; Ribbe, L. (Land Use Policy, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Changes in mortality and economic vulnerability to climatic hazards under economic development at the provincial level in China - Wu, Jidong; Li, Ying; Ye, Tao; Li, Ning (Regional Environmental Change, 2019)

Flood Hazards Impact on Neighborhood House Prices - Zhang, Lei; Leonard, Tammy (The Journal of Real Estate Finance and Economics, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Economic development and declining vulnerability to climate-related disasters in China - Wu, Jidong; Han, Guoyi; Zhou, Hongjian; Li, Ning (Environmental Research Letters, 2018)
Exposure and vulnerability are the main contributing factors of growing impact from climate-related disasters globally. Understanding the spatiotemporal dynamic patterns of vulnerability is important for designing effective disaster risk mitigation and adaptation measures. At national scale, most cross-country studies have suggested that economic vulnerability to disasters decreases as income increases, especially for developing countries. Research covering sub-national climate-related natural disasters is indispensable to obtaining a comprehensive understanding of the effect of regional economic growth on vulnerability reduction. Taking China as a case, this subnational scale study shows that economic development is correlated with the significant reduction in human fatalities but increase in direct economic losses (DELs) from climate-related disasters since 1949. The long-term trend in climate-related disaster vulnerability, reflected by mortality (1978–2015) and DELs (1990–2015) as a share of the total population and Gross Domestic Product, has seen significant decline among all economic regions in China. While notable differences remain among its West, Central and East economic regions, the temporal vulnerability change has been converging. The study further demonstrated that economic development level is correlated with human and economic vulnerability to climate-related disasters, and this vulnerability decreased with the increase of per-capita income. This study suggested that economic development can have nuanced effects on overall human and economic vulnerability to climate-related disasters. We argue that climate change science needs to acknowledge and examine the different pathways of vulnerability effects related to economic development.

Economic inequality and institutional adaptation in response to flood hazards: a historical analysis - Van Bavel, Bas; Curtis, Daniel R.; Soens, Tim (Ecology and Society, 2018)

Disaster risk, social vulnerability, and economic development - Ward, Patrick S.; Shively, Gerald (Disasters, 2017)
This paper examines the extent to which economic development decreases a country's risk of experiencing climate-related disasters as well as the societal impacts of those events. The paper proceeds from the underlying assumption that disasters are not inherently natural, but arise from the intersection of naturally-occurring hazards within fragile environments. It uses data from the International Disaster Database (EM-DAT),(1) representing country-year-level observations over the period 1980-2007. The study finds that low-income countries are significantly more at risk of climate-related disasters, even after controlling for exposure to climate hazards and other factors that may confound disaster reporting. Following the occurrence of a disaster, higher income generally diminishes a country's social vulnerability to such happenings, resulting in lower levels of mortality and morbidity. This implies that continued economic development may be a powerful tool for lessening social vulnerability to climate change.© 2016 The Author(s). Disasters © Overseas Development Institute, 2016. Language: en

Changements climatiques, changements du littoral et évolution de la vulnérabilité côtière au fil du temps : comparaison de territoires français, canadien et sénégalais - Weissenberger, Sebastian; Noblet, Mélinda; Plante, Steve; Chouinard, Omer; Guillemot, Julie; Aubé, Mélanie; Meur-Ferec, Catherine; Michel-Guillou, Élisabeth; Gaye, Ndickou; Kane, Alioune; Kane, Coura; Niang, Awa; et al. (2016)

On the relation between weather-related disaster impacts, vulnerability and climate change - Visser, Hans; Petersen, Arthur C.; Ligtvoet, Willem (Climatic Change, 2014)
Disasters such as floods, storms, heatwaves and droughts can have enormous implications for health, the environment and economic development. In this article, we address the question of how climate change might have influenced the impact of weather-related disasters. This relation is not straightforward, since disaster burden is not influenced by weather and climate events alone—other drivers are growth in population and wealth, and changes in vulnerability. We normalized disaster impacts, analyzed trends in the data and compared them with trends in extreme weather and climate events and vulnerability, following a 3 by 4 by 3 set-up, with three disaster burden categories, four regions and three extreme weather event categories. The trends in normalized disaster impacts show large differences between regions and weather event categories. Despite these variations, our overall conclusion is that the increasing exposure of people and economic assets is the major cause of increasing trends in disaster impacts. This holds for long-term trends in economic losses as well as the number of people affected. We also found similar, though more qualitative, results for the number of people killed; in all three cases, the role played by climate change cannot be excluded. Furthermore, we found that trends in historic vulnerability tend to be stable over time, despite adaptation measures taken by countries. Based on these findings, we derived disaster impact projections for the coming decades. We argue that projections beyond 2030 are too uncertain, not only due to unknown changes in vulnerability, but also due to increasing non-stationarities in normalization relations.

Flood risk, vulnerability and environmental justice: Evidence and evaluation of inequality in a UK context - Walker, Gordon; Burningham, Kate (Critical Social Policy, 2011)
Flooding has only relatively recently been considered as an environmental justice issue. In this paper we focus on flooding as a distinct form of environmental risk and examine some of the key evidence and analysis that is needed to underpin an environmental justice framing of flood risk and flood impacts. We review and examine the UK situation and the body of existing research literature on flooding to fill out our understanding of the patterns of social inequality that exist in relation to both flood risk exposure and vulnerability to the diverse impacts of flooding. We then consider the various ways in which judgements might be made about the injustice or justice of these inequalities and the ways in which they are being sustained or responded to by current flood policy and practice. We conclude that there is both evidence of significant inequalities and grounds on which claims of injustice might be made, but that further work is needed to investigate each of these. The case for pursuing the framing of flooding as an environmental justice issue is also made.

Psychosocial vulnerability and demographic characteristics in extreme flash floods: The case of Mandra 2017 flood in Greece - Speis, Phoebe-Demeter; Andreadakis, Emmanuel; Diakakis, Michalis; Daidassi, Evanthia; Sarigiannis, Georgios (International Journal of Disaster Risk Reduction, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Coaticook : Analyse scientifique de la vulnérabilité intégrant l’implication des acteurs locaux et citoyens pour une ville et une communauté plus résiliente - Thomas, Isabelle; Gagnon, Alexandre (Risques urbains, 2019)
Keywords: Ouvrage_Collectif_Numéro1; Thomas_Isabelle

Weaponizing vulnerability to climate change - Thomas, Kimberley Anh; Warner, Benjamin P. (Global Environmental Change, 2019)

Qualitative Assessment of Social Vulnerability to Flood Hazards in Romania - Török, Ibolya (Sustainability, 2018)
This paper investigates local-scale social vulnerability to flood hazards in Romania, aiming to identify the most vulnerable social and demographic groups across a wide range of geographical locations by considering three dimensions: demographic, socioeconomic, and the built environment. The purpose of the paper is threefold: first, it strives to improve the Social Vulnerability model (SoVI®) by applying a different weighting method adapted to the Romanian context, taking into consideration the municipalities exposed to flood movements. Second, it aims to develop an assessment model for the most vulnerable communities by measuring the heterogeneity according to local indicators related to disaster risks. Third, it aims to facilitate emergency managers to identify community sub-groups that are more susceptible to loss and to increase the resilience of local communities. To perform local-level vulnerability mapping, 28 variables were selected and three aggregated indexes were constructed with the help of the ArcGIS software. Moreover, a model of Geographically Weighted Regression (GWR) between communities directly affected by floods and localities with high- and very high values of the Local Social Vulnerability Index (LoSoVI) was used to explore the spatial relationship among them and to compare the appropriateness of Ordinary Least Square (OLS) and GWR for such modelling. The established GWR model has revealed that the negative effects of flood hazards are often associated with communities with a high degree of social vulnerability. Thus, the analysis is able to provide a more comprehensive picture on communities in desperate need of financial resources in order to have the ability to diminish the negative impacts of flood hazards and to provide a more sustainable society.

Analyser la vulnérabilité sociétale et territoriale aux inondations en milieu urbain dans le contexte des changements climatiques, en prenant comme cas d'étude la Ville de Montréal - Thomas, I.; Bleau, N. (2018)
28 Figure 7 : limites de la zone inondable et la zone inondée historiquement de la rive de Montréal de la rivière des prairies. [...] 68 Figure 27 : Aperçu de la table d’attributs de la base des données de la description de la sensibilité territoriale. [...] 41 Graphique 3 : Distribution des degrés de la sensibilité sociale par nombre d’aires de diffusion (206 AD au total) du secteur de la rivière des Prairies à Montréal à partir des résultats de l’indice ISSAIP des groupes de l’atelier de travail. [...] Cette analyse implique plusieurs étapes et le développement de plusieurs outils dont : la collecte des données disponibles et nécessaires pour réaliser un état des lieux des zones inondées historiquement pour une partie de la Ville de Montréal, la modélisation de l'espace occupé par l'eau selon différents niveaux d'eau possiblement atteints lors de débordement de la rivière, la collecte des donnée. [...] : la formation de réseaux de communication, la prise de décision, la création de consensus), qu’il est possible de mesurer, mais pas au moyen de données d’archives secondaires.
Keywords: Thomas_Isabelle

Adaptation policy and community discourse: risk, vulnerability, and just transformation - Schlosberg, David; Collins, Lisette B.; Niemeyer, Simon (Environmental Politics, 2017)

Social vulnerability to floods: Review of case studies and implications for measurement - Rufat, Samuel; Tate, Eric; Burton, Christopher G.; Maroof, Abu Sayeed (International journal of disaster risk reduction, 2015)
Abstract A leading challenge in measuring social vulnerability to hazards is for output metrics to better reflect the context in which vulnerability occurs. Through a meta-analysis of 67 flood disaster case studies (1997–2013), this paper profiles the leading drivers of social vulnerability to floods. The results identify demographic characteristics, socioeconomic status, and health as the leading empirical drivers of social vulnerability to damaging flood events. However, risk perception and coping capacity also featured prominently in the case studies, yet these factors tend to be poorly reflected in many social vulnerability indicators. The influence of social vulnerability drivers varied considerably by disaster stage and national setting, highlighting the importance of context in understanding social vulnerability precursors, processes, and outcomes. To help tailor quantitative indicators of social vulnerability to flood contexts, the article concludes with recommendations concerning temporal context, measurability, and indicator interrelationships.

Looking for capacities rather than vulnerabilities: The moderating effect of health assets on the associations between adverse social position and health - Roy, Mathieu; Levasseur, Mélanie; Doré, Isabelle; St-Hilaire, France; Michallet, Bernard; Couturier, Yves; Maltais, Danielle; Lindström, Bengt; Généreux, Mélissa (Preventive Medicine, 2018)
Keywords: Généreux_Mélissa

Elderly People With Disabilities And Natural Disasters: Vulnerability Of Seniors And Post Trauma - Maltais, Danielle (Gerontology & Geriatric Medicine, 2019)
Keywords: Site_internet_RIISQ

Disparities of population exposed to flood hazards in the United States. - Qiang, Yi (Journal of Environmental Management, 2019)

Spatial Analysis of Social Vulnerability to Floods Based on the MOVE Framework and Information Entropy Method: Case Study of Katsushika Ward, Tokyo - Lianxiao; Morimoto, Takehiro (Sustainability, 2019)
Tokyo is located in a lowland area that is vulnerable to flooding. Due to global climate change, the scalability and frequency of flooding is increasing. On the other hand, population aging and family structural changes, as well as the lack of adaptation measures, would accelerate flooding vulnerability. The key factors involved in social vulnerability must be studied to reduce the risk of flooding. In this study, we refer to the MOVE framework (a disaster vulnerability assessment framework) and analyze it from three perspectives: Exposure to social vulnerability, susceptibility, and resilience. We subsequently develop an index system to complete the evaluation using 11 indicators. The collected data will help reveal social vulnerability to floods in the Katsushika Ward, Tokyo, using the information entropy method and GIS. We found that the western region of the Katsushika Ward is at more risk than the eastern region during flooding. Additionally, the possibility of a serious crisis erupting is greater in the southwestern region than in the northwestern region. Consequently, we conclude that the spatial distribution of flooding varies in the region. The results of this study will help in understanding social vulnerability, in selecting and combining adaptation measures suited to the characteristics of the area, and in the effective and efficient implementation of these measures by the local government’s disaster department.

Risk to Residential Property Values from Climate Change-Related Flooding Hazards: A Mixed Methods Approach - Nguyen, Quyen; Diaz-Rainey, Ivan; Moore, Tony; Thorsnes, Paul; Cox, Simon; McKenzie, Leigh; Stirk-Wang, Leon (SSRN Electronic Journal, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Global-scale river flood vulnerability in the last 50 years. - Masahiro Tanoue; Tanoue, Masahiro; Yukiko Hirabayashi; Hirabayashi, Yukiko; Hiroaki Ikeuchi; Ikeuchi, Hiroaki (Scientific Reports, 2016)
The impacts of flooding are expected to rise due to population increases, economic growth and climate change. Hence, understanding the physical and spatiotemporal characteristics of risk drivers (hazard, exposure and vulnerability) is required to develop effective flood mitigation measures. Here, the long-term trend in flood vulnerability was analysed globally, calculated from the ratio of the reported flood loss or damage to the modelled flood exposure using a global river and inundation model. A previous study showed decreasing global flood vulnerability over a shorter period using different disaster data. The long-term analysis demonstrated for the first time that flood vulnerability to economic losses in upper-middle, lower-middle and low-income countries shows an inverted U-shape, as a result of the balance between economic growth and various historical socioeconomic efforts to reduce damage, leading to non-significant upward or downward trends. We also show that the flood-exposed population is affected by historical changes in population distribution, with changes in flood vulnerability of up to 48.9%. Both increasing and decreasing trends in flood vulnerability were observed in different countries, implying that population growth scenarios considering spatial distribution changes could affect flood risk projections.

Exposure to flood hazards in Miami and Houston: are Hispanic immigrants at greater risk than other social groups? - Maldonado, Alejandra; Collins, Timothy W.; Grineski, Sara E.; Chakraborty, Jayajit (International Journal of Environmental Research and Public Health, 2016)
Although numerous studies have been conducted on the vulnerability of marginalized groups in the environmental justice (EJ) and hazards fields, analysts have tended to lump people together in broad racial/ethnic categories without regard for substantial within-group heterogeneity. This paper addresses that limitation by examining whether Hispanic immigrants are disproportionately exposed to risks from flood hazards relative to other racial/ethnic groups (including US-born Hispanics), adjusting for relevant covariates. Survey data were collected for 1283 adult householders in the Houston and Miami Metropolitan Statistical Areas (MSAs) and flood risk was estimated using their residential presence/absence within federally-designated 100-year flood zones. Generalized estimating equations (GEE) with binary logistic specifications that adjust for county-level clustering were used to analyze (separately) and compare the Houston (N = 546) and Miami (N = 560) MSAs in order to clarify determinants of household exposure to flood risk. GEE results in Houston indicate that Hispanic immigrants have the greatest likelihood, and non-Hispanic Whites the least likelihood, of residing in a 100-year flood zone. Miami GEE results contrastingly reveal that non-Hispanic Whites have a significantly greater likelihood of residing in a flood zone when compared to Hispanic immigrants. These divergent results suggest that human-flood hazard relationships have been structured differently between the two MSAs, possibly due to the contrasting role that water-based amenities have played in urbanization within the two study areas. Future EJ research and practice should differentiate between Hispanic subgroups based on nativity status and attend to contextual factors influencing environmental risk disparities.

Hispanic Immigrants' Vulnerabilities to Flood and Hurricane Hazards in Two United States Metropolitan Areas - Maldonado, Alejandra; Collins, Timothy W.; Grineski, Sara E. (Geographical Review, 2016)
INTRODUCTION A substantial body of research has focused on the vulnerability of racial/ethnic minorities to hazards and disasters. This work has lumped people with diverse characteristics into general groups, such as "Hispanic" or "Latino/a" (Bolin 2007). Today, Hispanic immigrants represent an important group in U.S. society due to their large and increasing population. According to American Community Survey estimates, as of 2013 there were 21 million foreign-born Hispanics in the U.S., representing 52.5 percent of the total foreign-born population and 6 percent of the U.S. population. Hispanic immigrants are distinguishable from U.S.--born Hispanics due to their concerns about immigration status as well as cultural and linguistic differences. Treating Hispanics as a homogenous group may mask important differences between foreign-born and U.S.--born Hispanics and lead to erroneous conclusions about their disaster vulnerabilities. In order to address the particular risks experienced by foreign-born Hispanics in the U.S., more research characterizing salient dimensions of their vulnerability to hazards and disasters is needed. This study highlights particular vulnerabilities of foreign-born Hispanics living at risk to flooding and hurricanes in the Houston, Texas, and Miami, Florida, Metropolitan Statistical Areas (MSAs) by examining their self-protective actions, and their perceptions of and knowledge about flood risks, in comparison to both U.S.--born non-Hispanic whites and U.S.--born Hispanics. It addresses two research questions: what differences exist in self-protective actions and perceptions of risk between Hispanic immigrants, U.S.--born Hispanics, and U.S.--born white residents who live at high risk to flooding and hurricanes; and why do differences in self-protective actions and perceptions of risk exist between Hispanic immigrants, U.S.--born Hispanics, and U.S.--born white residents who live at high risk to flooding and hurricanes? Approaching these questions, we analyze primary structured survey and semistructured interview data using a mixed-method analysis approach, which enables us to clarify particular factors that place Hispanic immigrants at increased risk to flood and hurricane disasters. LITERATURE REVIEW The last three decades have marked the emergence of a social-vulnerability perspective on hazards and disasters, which emphasizes the influence of inequalities on differential risks (Hewitt 1983, 1997; Peacock and others 1997; Wisner and others 2004; Tierney 2006; Thomas and others 2013). From this perspective, risk is determined partly by human exposure to a hazard and partly by people's social vulnerability. While there is debate about the meaning and measurement of social vulnerability, the following definition is useful: "the characteristics of a person or group and their situation that influence their capacity to anticipate, cope with, resist and recover from the impact of a natural hazard" (Wisner and others 2004, 11). In this study, we analyze the social vulnerability of Hispanic immigrants in terms of self-protection from flood/hurricane hazards, and perceptions of and knowledge about flood/hurricane risks. Here, self-protection is defined as any structural or nonstructural strategy used by households to minimize loss and enable recovery from the impacts of flood or hurricane hazard exposures (NRC 2006). Self-protection strategies in the context of flood and hurricane hazards include home structural as well as nonstructural actions. Structural mitigation actions include elevating home structures, flood-proofing homes, and installing hurricane shutters (FEMA 2014). They also include nonstructural actions, such as maintaining flood insurance. In terms of nonstructural self-protection strategies, in the U.S., flood insurance plays an important protective role, since it provides compensation for property losses. Disaster preparedness is another dimension of nonstructural self-protection that has been examined extensively (Mulilis and Lippa 1990; Faupel and others 1992; Norris and others 1999; Sattler and others 2000; Miceli and others 2008; Borque and others 2013), and can include evacuation planning, maintaining basic supplies (for example, a first aid kit) and being alert (for example, being attentive to hazard reports). …

Risques d’inondation et vulnérabilité : l’exemple du bassin versant de la rivière Kennebecasis, Nouveau-Brunswick, Canada. - Fortin, Guillaume; Poirier, Charlotte; Duhamel, Françis; Germain, Daniel (2019)
La province du Nouveau-Brunswick, situee dans l’est du Canada, est tres affectee par les inondations. Bien que moins documentee que l’alea, la dimension humaine du risque que represente la vulnerabilite est importante pour l’adaptation des populations. Cet article fait un survol des principaux concepts lies a la vulnerabilite et presente leur application a l’echelle d’un bassin versant de taille moyenne. Les resultats montrent la necessite de considerer simultanement la perception et la preparation au risque d’inondation. En effet, si certains residents dans les zones a risque ont une bonne connaissance des inondations et une perception realiste du risque, cela ne se traduit pas necessairement par une preparation adaptee et adequate face au risque. La reduction du risque passe indeniablement par une meilleure sensibilisation et education de la population.

Empirical evidence of declining global vulnerability to climate-related hazards - Formetta, Giuseppe; Feyen, Luc (Global Environmental Change, 2019)

Future Changes in Flood Hazards across Canada under a Changing Climate - Gaur, Ayushi; Gaur, Abhishek; Simonovic, Slobodan P. (Water, 2018)
Climate change has induced considerable changes in the dynamics of key hydro-climatic variables across Canada, including floods. In this study, runoff projections made by 21 General Climate Models (GCMs) under four Representative Concentration Pathways (RCPs) are used to generate 25 km resolution streamflow estimates across Canada for historical (1961–2005) and future (2061–2100) time-periods. These estimates are used to calculate future projected changes in flood magnitudes and timings across Canada. Results obtained indicate that flood frequencies in the northernmost regions of Canada, and south-western Ontario can be expected to increase in the future. As an example, the historical 100-year return period events in these regions are expected to become 10–60 year return period events. On the other hand, northern prairies and north-central Ontario can be expected to experience decreases in flooding frequencies in future. The historical 100-year return period flood events in these regions are expected to become 160–200 year return period events in future. Furthermore, prairies, parts of Quebec, Ontario, Nunavut, and Yukon territories can be expected to experience earlier snowmelt-driven floods in the future. The results from this study will help decision-makers to effectively manage and design municipal and civil infrastructure in Canada under a changing climate.

Appréciation et traitement du risque – Aléas géologiques et hydrométéorologiques dans le secteur de Rigaud-sur-le-Lac pour le chemin du Bas-de-la-Rivière à Rigaud - Gachon, P; Dueymes, G; Benoit, C; Raphoz, M; Boyer-Villemaire, U (Université du Québec à Montréal, Chaire sur les risques hydrométéorologiques dans le contexte des changements climatiques, 2018)
Keywords: Gachon_Philippe; Ouvrage_Collectif_Numéro1

Ice-block fall and snow avalanche hazards in northern Gaspésie (eastern Canada): Triggering weather scenarios and process interactions - Graveline, Marie-Hélène; Germain, Daniel (Cold Regions Science and Technology, 2016)
Abstract The database of the Quebec Ministry of Transport allowed us to analyze the occurrence of ice-block falls and snow avalanches for the past decades along national road 132. The results show that ice structure collapse may be categorized into three distinct phases by using daily temperatures (minimum, maximum, and average) and the cumulative degree day (temperatures above 0°C) since the March 1 st , corresponding to the beginning of the ice wall melting period: 1) a short and intense period of ice-block falls from the mid-April to the beginning of May; 2) a period of constant activity, mainly during the two first weeks of May; and 3) isolated residual activity, with a low frequency of ice-block falls until the month of June. The snow avalanche days were mainly characterized by significant snowfalls or rain-on-snow events with temperature>0°C. The multi-hazard probability was then evaluated based on the timing and relative frequency of ice-block fall and the modeling of sufficient snowpack for avalanching. This simple method to assess the synergistic effect of hillslope processes allows a better understanding of the spring avalanche regime related to the collapse of ice structures. These findings are expected to assist in the management of natural hazards and to improve our knowledge of spatiotemporal dynamics of mass-wasting events on highways.

Mapping the vulnerability hotspots over Hindu-Kush Himalaya region to flooding disasters - Elalem, Shada; Pal, Indrani (Weather and climate extremes, 2015)
Abstract A disproportionate share of the global economic and human losses caused by environmental shocks is borne by people in the developing nations. The mountain region of Hindu-Kush Himalaya (HKH) in South Asia is threatened by numerous flooding events annually. An efficient disaster risk reduction often needs to rest upon location-based synoptic view of vulnerability. Resolving this deficit improves the ability to take risk reduction measures in a cost-effective way, and in doing so, strengthens the resilience of societies to flooding disasters. The central aim of this research is to identify the vulnerable locations across HKH boundary from the perspective of reported history of economic and human impacts due to occurrence of flooding disasters. A detailed analysis indicates a very high spatial heterogeneity in flooding disaster occurrence in the past 6 decades. The most recent decade reported highest number of disasters and greater spatial coverage as compared to the earlier decades. The data indicates that, in general, economic impacts of flooding disasters were notably higher in Pakistan, Afghanistan and Nepal. On the other hand, vulnerability scenarios with respect to human impacts were diverse for different countries. In terms of morbidity and mortality, Bangladesh, Pakistan, Bhutan and India were detected to be most susceptible to human impacts. Although Bhutan had seen lesser number of flooding disasters, higher population living within disaster prone region make them vulnerable. In summary, complex interactions between natural and socio-economic conditions play a dominant role to define and characterize the type and magnitude of vulnerability of HKH countries to disaster occurrence and their economic and human impacts.

Application of Social Vulnerability Index (SoVI) and delineation of natural risk zones in Greater Lisbon, Portugal - Guillard-Gonçalves, Clémence; Cutter, Susan L.; Emrich, Christopher T.; Zêzere, José Luís (Journal of Risk Research, 2015)

Declining vulnerability to river floods and the global benefits of adaptation - Jongman, Brenden; Bierkens, Marc F. P.; Winsemius, Hessel; Aerts, Jeroen C. J. H.; de Perez, Erin Coughlan; van Aalst, Maarten; Kron, Wolfgang; Ward, Philip B.; Ward, Philip J. (Proceedings of the National Academy of Sciences of the United States of America, 2015)
The global impacts of river floods are substantial and rising. Effective adaptation to the increasing risks requires an in-depth understanding of the physical and socioeconomic drivers of risk. Whereas the modeling of flood hazard and exposure has improved greatly, compelling evidence on spatiotemporal patterns in vulnerability of societies around the world is still lacking. Due to this knowledge gap, the effects of vulnerability on global flood risk are not fully understood, and future projections of fatalities and losses available today are based on simplistic assumptions or do not include vulnerability. We show for the first time (to our knowledge) that trends and fluctuations in vulnerability to river floods around the world can be estimated by dynamic high-resolution modeling of flood hazard and exposure. We find that rising per-capita income coincided with a global decline in vulnerability between 1980 and 2010, which is reflected in decreasing mortality and losses as a share of the people and gross domestic product exposed to inundation. The results also demonstrate that vulnerability levels in low- and high-income countries have been converging, due to a relatively strong trend of vulnerability reduction in developing countries. Finally, we present projections of flood losses and fatalities under 100 individual scenario and model combinations, and three possible global vulnerability scenarios. The projections emphasize that materialized flood risk largely results from human behavior and that future risk increases can be largely contained using effective disaster risk reduction strategies.

Combining hazard, exposure and social vulnerability to provide lessons for flood risk management - Koks, Elco; Jongman, Brenden; Husby, Trond; Botzen, W. J. Wouter (Environmental Science & Policy, 2015)
Flood risk assessments provide inputs for the evaluation of flood risk management (FRM) strategies. Traditionally, such risk assessments provide estimates of loss of life and economic damage. However, the effect of policy measures aimed at reducing risk also depends on the capacity of households to adapt and respond to floods, which in turn largely depends on their social vulnerability. This study shows how a joint assessment of hazard, exposure and social vulnerability provides valuable information for the evaluation of FRM strategies. The adopted methodology uses data on hazard and exposure combined with a social vulnerability index. The relevance of this state-of-the-art approach taken is exemplified in a case-study of Rotterdam, the Netherlands. The results show that not only a substantial share of the population can be defined as socially vulnerable, but also that the population is very heterogeneous, which is often ignored in traditional flood risk management studies. It is concluded that FRM measures, such as individual mitigation, evacuation or flood insurance coverage should not be applied homogenously across large areas, but instead should be tailored to local characteristics based on the socioeconomic characteristics of individual households and neighborhoods.

Integrating social vulnerability into federal flood risk management planning - Cutter, S.L.; Emrich, C.T.; Morath, D.P.; Dunning, C.M. (Journal of Flood Risk Management, 2013)
Abstract While flood risk management planning in the U nited S tates has focused on flood control structures designed to protect the economic value of property, it has consistently undervalued other social impacts associated with flooding. The US A rmy C orps of E ngineers ( USACE ) recently initiated research aimed at understanding how to incorporate social characteristics into the measures currently utilised in flood control project evaluation and consideration. This paper proposes a methodology for incorporating a known measure of social vulnerability, the S ocial V ulnerability I ndex ( SoVI ), into USACE civil works planning. Using the USACE S outh A tlantic D ivision as the study area, this paper evaluates eight different variations of the social vulnerability metric and their potential deployment in USACE projects. Each formulation is compared with the original‐computed SoVI as a means to test its spatial and statistical sensitivity, including an assessment of each variant's robustness, reducibility, scalability, and transferability. Results indicate that while it is possible to create simplified, yet robust, versions of SoVI for individual places, such ‘lite’ metrics tend to fall short in areas of scalability and transferability in relation to the original SoVI formulation.

A GIS Tool for Mapping Dam-Break Flood Hazards in Italy - Albano, Raffaele; Mancusi, Leonardo; Adamowski, Jan; Cantisani, Andrea; Sole, Aurelia (ISPRS International Journal of Geo-Information, 2019)
Mapping the delineation of areas that are flooded due to water control infrastructure failure is a critical issue. Practical difficulties often present challenges to the accurate and effective analysis of dam-break hazard areas. Such studies are expensive, lengthy, and require large volumes of incoming data and refined technical skills. The creation of cost-efficient geospatial tools provides rapid and inexpensive estimates of instantaneous dam-break (due to structural failure) flooded areas that complement, but do not replace, the results of hydrodynamic simulations. The current study implements a Geographic Information System (GIS) based method that can provide useful information regarding the delineation of dam-break flood-prone areas in both data-scarce environments and transboundary regions, in the absence of detailed studies. Moreover, the proposed tool enables, without advanced technical skills, the analysis of a wide number of case studies that support the prioritization of interventions, or, in emergency situations, the simulation of numerous initial hypotheses (e.g., the modification of initial water level/volume in the case of limited dam functionality), without incurring high computational time. The proposed model is based on the commonly available data for masonry dams, i.e., dam geometry (e.g., reservoir capacity, dam height, and crest length), and a Digital Elevation Model. The model allows for rapid and cost-effective dam-break hazard mapping by evaluating three components: (i) the dam-failure discharge hydrograph, (ii) the propagation of the flood, and (iii) the delineation of flood-prone areas. The tool exhibited high accuracy and reliability in the identification of hypothetical dam-break flood-prone areas when compared to the results of traditional hydrodynamic approaches, as applied to a dam in Basilicata (Southern Italy). In particular, the over- and under-estimation rates of the proposed tool, for the San Giuliano dam, Basilicata, were evaluated by comparing its outputs with flood inundation maps that were obtained by two traditional methods whil using a one-dimensional and a two-dimensional propagation model, resulting in a specificity value of roughly 90%. These results confirm that most parts of the flood map were correctly classified as flooded by the proposed GIS model. A sensitivity value of over 75% confirms that several zones were also correctly identified as non-flooded. Moreover, the overall effectiveness and reliability of the proposed model were evaluated, for the Gleno Dam (located in the Central Italian Alps), by comparing the results of literature studies concerning the application of monodimensional numerical models and the extent of the flooded area reconstructed by the available historical information, obtaining an accuracy of around 94%. Finally, the computational efficiency of the proposed tool was tested on a demonstrative application of 250 Italian arch and gravity dams. The results, when carried out using a PC, Pentium Intel Core i5 Processor CPU 3.2 GHz, 8 GB RAM, required about 73 min, showing the potential of such a tool applied to dam-break flood mapping for a large number of dams.

Determinants of Risk: Exposure and Vulnerability - Cardona, Omar-Dario; Van Aalst, Maarten K.; Birkmann, Jörn; Fordham, Maureen; McGregor, Glenn; Perez, Rosa; Pulwarty, Roger S.; Schipper, E. Lisa F.; Sinh, Bach Tan; Décamps, Henri; Keim, Mark; Davis, Ian; et al. (Managing the Risks of Extreme Events and Disasters to Advance Climate Change Adaptation, 2012)
Keywords: Ouvrage_Collectif_Numéro1